Printed matter, method for producing printed matter, and printing medium for laser printing

By coating titanium oxide on the sheet medium and using ultraviolet laser technology, the problems of high ink consumption and poor printing quality in the prior art are solved, and high-quality and low-cost printing effects are achieved.

CN115666956BActive Publication Date: 2025-04-22OJI HLDG CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202180036542.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-22
Filing Date
2021-05-21
Publication Date
2025-04-22
Estimated Expiration
2041-05-21

AI Technical Summary

Technical Problem

In the prior art, the ink tape and ink liquid used in thermal printing presses and inkjet printers consume higher ink ribbons and inkjet printers, resulting in increased operating costs and prone to printing leakage and blurring problems. At the same time, offset printing based on UV curing ink also has problems of pollution and uneven thickness, resulting in poor printing quality.

Method used

High-quality printing is achieved by using laser printing technology that coats titanium oxide on the sheet medium, using ultraviolet laser light to discolor the titanium oxide in the printing area. This technology ensures visibility and distinctness of the printing area by controlling the content of titanium oxide and the Raman strength ratio.

Benefits of technology

High-quality printing is achieved, reducing ink consumption and running costs, avoiding printing leakage and blurring problems, and improving solvent resistance and visibility of the printed matter.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003952113570000691
    Figure BDA0003952113570000691
  • Figure BDA0003952113570000701
    Figure BDA0003952113570000701
  • Figure BDA0003952113570000711
    Figure BDA0003952113570000711
Patent Text Reader

Abstract

The object of the present invention is to provide: a printed matter having a printing area printed by ultraviolet laser and excellent visibility, a method for producing a printed matter by irradiating ultraviolet laser, and a laser printing printing medium used in the printed matter and the method for producing a printed matter. The printed matter of the present invention has a printing area containing discolored titanium oxide on at least a portion of a sheet medium, the sheet medium being selected from paper or film having a printable area containing titanium oxide, titanium oxide being added to the sheet medium, and when the sheet medium is paper, the content of titanium oxide in the printable area of ​​the sheet medium is 1.0% by mass or more, the length-weighted average fiber length and average fiber width of the pulp constituting the paper are within a specific range, and the mass per unit area of ​​the paper is 20 g / m 2 As mentioned above, when the sheet medium is a thin film, the content of titanium oxide in the printable area of ​​the sheet medium is greater than 0.3 mass %, the thickness of the film is greater than 15 μm, the resin constituting the film contains a specific resin, and the ratio of the Raman intensity of titanium oxide originating from the printing area to the Raman intensity of titanium oxide originating from the non-printing area is less than 0.70.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a printed matter, a method for producing the printed matter, and a printing medium for laser printing. Background Art

[0002] Conventionally, label marking or inkjet printing has been performed to mark dates such as the date of manufacture and the date of shipment, or variable information such as a barcode, on packaging such as a container for storing stored items.

[0003] In addition, a method of printing by laser irradiation has also been proposed. For example, in order to provide a laser printing laminate and its printing that can perform clear printing at high speed by laser irradiation and has excellent various resistances of the printed part, a laser printing laminate is disclosed, which is manufactured by coating white ink, black ink and overprint varnish (OP varnish) on the aluminum vapor-deposited surface of aluminum vapor-deposited paper.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 9-123607 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] As a means of printing on the surface of a package, label, adhesive tape, etc., there is a method of using a thermal printer or inkjet printer to directly place ink on the surface of the package, which is currently commonly used. However, consumables such as the ink ribbon of a thermal printer and the ink of an inkjet printer are expensive, and there is a problem that the running cost becomes expensive in order to print a large amount of variable information. In addition, if these consumables are not replaced, printing leakage may occur. Furthermore, direct printing of variable information on the package based on offset printing using UV curing ink is also carried out, but due to contaminants on the surface of the package and uneven thickness of the package, printing is sometimes blurred or text is missing.

[0009] In addition, the method described in Patent Document 1 is a technology that can achieve high speed, but removes the upper layer that easily absorbs laser light by irradiation of CO2 laser, exposes the lower layer, and forms visible text and the like by the difference in color between the upper layer and the lower layer. Therefore, the upper layer is limited to materials that easily absorb laser light, while the lower layer is not easy to absorb laser light and is limited to materials that have a contrast with the color of the upper layer. That is, the carbon black-based material (black) that easily absorbs laser light becomes the upper layer, and the titanium oxide-based material (white) becomes the lower layer, and the text and the like formed by irradiation of laser light become black text and white text, and the visibility is poor. In addition, when removing the upper layer, there is a problem that the toner of the upper layer becomes dusty, causing pollution to the working environment.

[0010] The object of the present invention is to provide: a printed matter having a printed area containing discolored titanium oxide and excellent visibility, a method for producing a printed matter by irradiating an ultraviolet laser, and a laser printing printing medium used in the printed matter and the method for producing the printed matter.

[0011] Solutions for solving problems

[0012] First, the present inventors have discovered that a printed material with excellent visibility can be obtained by using a specific sheet medium in which the content of titanium oxide in the printable area is greater than a specific value and by making the ratio of the Raman intensity derived from titanium oxide between the printing area and the non-printing area less than a specific value, thereby completing the present invention. The first present invention relates to the following <1> to <15>.

[0013] Second, the present inventors have discovered that a printed matter with excellent visibility can be obtained by using a recording medium having a coating layer containing titanium oxide in a specific range as a printable area on a specific paper substrate and by making the ratio of the Raman intensity derived from titanium oxide in the printing area to that in the non-printing area less than a specific value, thereby completing the present invention. The second present invention relates to the following <16> to <32>.

[0014] Thirdly, the present inventors have found that a printed material with excellent visibility can be obtained by setting the content of titanium oxide in the printable area to a specific value or more, setting the content of titanium oxide in the laminated layer to a specific range, and further setting the thickness of the laminated layer to a specific range, and setting the ratio of the Raman intensity derived from titanium oxide in the printed area to that in the non-printed area to a specific value or less, thereby completing the present invention. The present invention relates to the following <33> to <43>.

[0015] <1> A printed article having a printed area containing discolored titanium oxide on at least a portion of a sheet medium, wherein the sheet medium is selected from paper or film having a printable area containing titanium oxide,

[0016] Titanium oxide is added to the sheet medium.

[0017] When the sheet medium is paper, the content of titanium oxide in the printable area of ​​the sheet medium is 1.0 mass % or more, the length-weighted average fiber length of the pulp constituting the paper is 0.5 mm or more and 3.0 mm or less, the average fiber width of the pulp constituting the paper is 14.0 μm or more and 35.0 μm or less, and the mass per unit area of ​​the paper is 20 g / m 2 above,

[0018] When the sheet medium is a film, the content of titanium oxide in the printable area of ​​the sheet medium is 0.3 mass % or more, the thickness of the film is 15 μm or more, and the resin constituting the film includes at least one selected from the group consisting of polyethylene, polypropylene, ethylene-propylene copolymer, polyethylene terephthalate, polylactic acid and polybutylene succinate,

[0019] The ratio of the Raman intensity derived from titanium oxide in the printed area to the Raman intensity derived from titanium oxide in the non-printed area is 0.70 or less.

[0020] <2> according to <1> In the printed matter, the sheet medium is a film, and the content of titanium oxide in the printable region of the sheet medium is 0.5 mass % or more and 7.5 mass % or less.

[0021] <3> according to <1> or <2> The printed matter, wherein the titanium oxide is at least one selected from rutile titanium oxide and anatase titanium oxide.

[0022] <4> according to <1> ~ <3> The printed matter described in any one of the above aspects, wherein the printed matter is selected from the group consisting of a package, a label, and an adhesive tape.

[0023] <5> according to <1> ~ <4> The printed matter described above further comprises a transparent resin layer on the printable area.

[0024] <6> according to <5> In the printed matter, the resin constituting the transparent resin layer is at least one selected from polyethylene, polypropylene, polyethylene terephthalate, polyvinyl alcohol and starch.

[0025] <7> according to <5> or <6> In the printed matter, the transparent resin layer is formed by bonding a transparent resin film to a sheet medium via an adhesive layer, or by laminating a transparent resin film on a sheet medium.

[0026] <8> according to <5> ~ <7> The printed article described in any one of the above aspects, wherein the transparent resin layer has a thickness of 5 μm or more and 100 μm or less.

[0027] <9> A method for producing a printed matter, comprising the following steps:

[0028] Printing is performed by irradiating a sheet medium selected from paper or film with ultraviolet laser light to change the color of the irradiated area.

[0029] Titanium oxide is added to the above-mentioned sheet medium.

[0030] When the sheet medium is paper, the content of titanium oxide in the printable area of ​​the sheet medium is 1.0 mass % or more, the length-weighted average fiber length of the pulp constituting the paper is 0.5 mm or more and 3.0 mm or less, the average fiber width of the pulp constituting the paper is 14.0 μm or more and 35.0 μm or less, and the mass per unit area of ​​the paper is 20 g / m 2 above,

[0031] When the above-mentioned sheet medium is a film, the content of titanium oxide in the printable area of ​​the sheet medium is greater than 0.3 mass%, the thickness of the film is greater than 15 μm, and the resin constituting the film contains at least one selected from the group consisting of polyethylene, polypropylene, ethylene-propylene copolymer, polyethylene terephthalate, polylactic acid and polybutylene succinate.

[0032] <10> according to <9> The method for producing printed matter, wherein the power of the irradiated ultraviolet laser is above 0.8W.

[0033] <11> according to <9> or <10> In the method for producing a printed article, the step of performing the printing is a step of irradiating with ultraviolet laser light in such a way that the ratio of the Raman intensity of titanium oxide in the printed area to the Raman intensity of titanium oxide in the non-printed area becomes 0.70 or less.

[0034] <12> according to <9> ~ <11> The method for producing a printed article as described above further comprises a transparent resin layer on the printable area.

[0035] <13> according to <9> ~ <12> The method for producing a printed article described in any one of the above, wherein the sheet medium is selected from a package, a label, and an adhesive tape.

[0036] <14> according to <9> ~ <13> The method for producing a printed matter described in any one of the above aspects is characterized in that the step of printing is performed online.

[0037] <15> A printing medium for laser printing, comprising a sheet medium, wherein the sheet medium is selected from paper or film having a printable area that can be printed by ultraviolet laser,

[0038] When the sheet medium is paper, the content of titanium oxide in the printable area of ​​the sheet medium is 1.0 mass % or more, the length-weighted average fiber length of the pulp constituting the paper is 0.5 mm or more and 3.0 mm or less, the average fiber width of the pulp constituting the paper is 14.0 μm or more and 35.0 μm or less, and the mass per unit area of ​​the paper is 20 g / m 2 above,

[0039] When the above-mentioned sheet medium is a film, the content of titanium oxide in the printable area of ​​the sheet medium is greater than 0.3 mass%, the thickness of the film is greater than 15 μm, and the resin constituting the film contains at least one selected from the group consisting of polyethylene, polypropylene, ethylene-propylene copolymer, polyethylene terephthalate, polylactic acid and polybutylene succinate.

[0040] <16> A printed matter having a printed area containing discolored titanium oxide on at least a portion of a recording medium, wherein the recording medium has a printable area containing titanium oxide,

[0041] The printable area of ​​the recording medium has a coating layer containing titanium oxide on a paper substrate.

[0042] The length-weighted average fiber length of the pulp constituting the paper substrate is 0.6 mm or more and 3.5 mm or less,

[0043] The content of titanium oxide in the coating layer is 0.6 g / m 2 Above and 30g / m 2 the following,

[0044] The content of titanium oxide in the coating layer is Ag / m 2 , when the thickness of the coating layer is set to B μm, A / B is greater than or equal to 0.01 and less than or equal to 2.00,

[0045] The ratio of the Raman intensity derived from titanium oxide in the printed area to the Raman intensity derived from titanium oxide in the non-printed area is 0.70 or less.

[0046] <17> according to <16> The printed article, wherein the coating layer has a thickness of 0.4 μm or more and 30.0 μm or less.

[0047] <18> according to <16> or <17> In the printed article, the coating layer contains a thermoplastic resin in addition to titanium oxide.

[0048] <19> according to <18> The printed matter, wherein the thermoplastic resin is selected from the group consisting of starch derivatives, casein, shellac, polyvinyl alcohol, polyvinyl alcohol derivatives, acrylic resins and maleic acid resins.

[0049] <20> according to <16> ~ <19> The printed article described in any one of the above aspects, wherein the titanium oxide is at least one selected from the group consisting of rutile titanium oxide and anatase titanium oxide.

[0050] <21> according to <16> ~ <20> The printed matter described in any one of the preceding claims, wherein the ratio of the number of fine fibers having a fiber length of 0.2 mm or less in the pulp constituting the paper base material is 6% or more and 16% or less.

[0051] <22> according to <16> ~ <21> The printed matter described above, wherein the recording medium is selected from the group consisting of a package, a label, and an adhesive tape.

[0052] <23> according to <16> ~ <22> The printed matter described above, wherein the recording medium further comprises a transparent resin layer on the coating layer.

[0053] <24> according to <23> In the printed matter, the resin constituting the transparent resin layer is at least one selected from polyethylene, polypropylene, polyethylene terephthalate, polyvinyl alcohol and starch.

[0054] <25> according to <23> or <24> In the printed matter, the transparent resin layer is formed by bonding a transparent resin film to a sheet medium via an adhesive layer, or by laminating a transparent resin film on a sheet medium.

[0055] <26> according to <23> ~ <25> The printed article described in any one of the above aspects, wherein the transparent resin layer has a thickness of 5 μm or more and 100 μm or less.

[0056] <27> A method for producing a printed matter, comprising the following steps:

[0057] Printing is performed by irradiating the recording medium with ultraviolet light to change the color of the irradiated area.

[0058] The printable area of ​​the recording medium has a coating layer containing titanium oxide on a paper substrate.

[0059] The length-weighted average fiber length of the pulp constituting the paper substrate is 0.6 mm or more and 3.5 mm or less,

[0060] The content of titanium oxide in the coating layer is 0.6 g / m 2 Above and 30g / m 2 the following,

[0061] The content of titanium oxide in the coating layer is Ag / m 2 When the thickness of the coating layer is B μm, A / B is greater than or equal to 0.01 and less than or equal to 2.00.

[0062] <28> according to <27> The method for producing printed matter, wherein the power of the irradiated ultraviolet laser is above 0.8W.

[0063] <29> according to <27> or <28> In the method for producing a printed article, the step of performing the printing is a step of irradiating with ultraviolet laser light in such a way that the ratio of the Raman intensity of titanium oxide in the printed area to the Raman intensity of titanium oxide in the non-printed area becomes 0.70 or less.

[0064] <30> according to <27> ~ <29> The method for producing a printed matter described in any one of the above, wherein the recording medium is selected from a package, a label, and an adhesive tape.

[0065] <31> according to <27> ~ <30> The method for producing a printed matter described in any one of the above is characterized in that the step of printing is performed online.

[0066] <32> A laser printing medium having a printable area that can be printed using ultraviolet laser,

[0067] The printable area of ​​the printing medium has a coating layer containing titanium oxide on a paper substrate.

[0068] The length-weighted average fiber length of the pulp constituting the paper substrate is 0.6 mm or more and 3.5 mm or less,

[0069] The content of titanium oxide in the coating layer is 0.6 g / m 2 Above and 30g / m 2 the following,

[0070] The content of titanium oxide in the coating layer is Ag / m 2 When the thickness of the coating layer is B μm, A / B is greater than or equal to 0.01 and less than or equal to 2.00.

[0071] <33> A printed matter having a printed area containing discolored titanium oxide on at least a portion of a sheet medium, wherein the sheet medium has a printable area containing titanium oxide,

[0072] The printable area of ​​the sheet medium has a laminate layer containing titanium oxide on a paper substrate.

[0073] The content of titanium oxide in the laminate layer is 0.1 g / m 2 above,

[0074] The content of titanium oxide in the laminate layer is 1 mass % or more and 45 mass % or less,

[0075] The thickness of the laminate layer is 10 μm or more and 200 μm or less,

[0076] The ratio of the Raman intensity derived from titanium oxide in the printed area to the Raman intensity derived from titanium oxide in the non-printed area is 0.70 or less.

[0077] <34> according to <33> In the printed matter, the laminate layer is formed of a film of a thermoplastic resin containing titanium oxide.

[0078] <35> according to <34> The printed matter, wherein the thermoplastic resin is selected from the group consisting of polyethylene, polypropylene, polyethylene terephthalate, polylactic acid and polybutylene succinate.

[0079] <36> according to <33> ~ <35> The printed article described in any one of the above aspects, wherein the titanium oxide is at least one selected from the group consisting of rutile titanium oxide and anatase titanium oxide.

[0080] <37> according to <33> ~ <36> The printed matter described in any one of the above aspects, wherein the printed matter is selected from the group consisting of a package, a label, and an adhesive tape.

[0081] <38> A method for producing a printed matter, comprising the following steps:

[0082] The printable area of ​​the sheet medium is irradiated with ultraviolet laser light to change the color of the irradiated area, thereby printing.

[0083] The printable area of ​​the sheet medium has a laminate layer containing titanium oxide on a paper substrate.

[0084] The content of titanium oxide in the laminate layer is 0.1 g / m 2 above,

[0085] The content of titanium oxide in the laminate layer is 1 mass % or more and 45 mass % or less,

[0086] The thickness of the laminate layer is 10 μm or more and 200 μm or less.

[0087] <39> according to <38> The method for producing printed matter, wherein the power of the irradiated ultraviolet laser is above 0.8W.

[0088] <40> according to <38> or <39> In the method for producing a printed article, the step of performing the printing is a step of irradiating with ultraviolet laser light in such a way that the ratio of the Raman intensity of titanium oxide in the printed area to the Raman intensity of titanium oxide in the non-printed area becomes 0.70 or less.

[0089] <41> according to <38> ~ <40> The method for producing a printed article according to any one of the above aspects, wherein the printed article is selected from the group consisting of a package, a label, and an adhesive tape.

[0090] <42> according to <38> ~ <41> The method for producing a printed matter described in any one of the above aspects is characterized in that the step of printing is performed online.

[0091] <43> A printing medium for laser printing, comprising a sheet medium having a printable area that can be printed by ultraviolet laser,

[0092] The printable area of ​​the sheet medium has a laminate layer containing titanium oxide on a paper substrate.

[0093] The content of titanium oxide in the laminate layer is 0.1 g / m 2 above,

[0094] The content of titanium oxide in the laminate layer is 1 mass % or more and 45 mass % or less,

[0095] The thickness of the laminate layer is 10 μm or more and 200 μm or less.

[0096] Effects of the Invention

[0097] According to the present invention, there can be provided: a printed matter having a printed area containing discolored titanium oxide and having excellent visibility; a method for producing a printed matter by irradiating an ultraviolet laser; and a laser printing printing medium used in the printed matter and the method for producing the printed matter. BRIEF DESCRIPTION OF THE DRAWINGS

[0098] Figure 1 It is the barcode printed in the embodiment.

[0099] Figure 2 This is an explanatory diagram showing an example of Raman intensity measurement in the first printed matter.

[0100] Figure 3 This is an explanatory diagram showing an example of Raman intensity measurement in the second printed material.

[0101] Figure 4 This is an explanatory diagram showing an example of Raman intensity measurement in the third printed material.

[0102] Figure 5 This is a conceptual perspective view of an example of a liquid container having a printed area. DETAILED DESCRIPTION

[0103] [First Printing]

[0104] The first printed matter of the present invention (hereinafter, also referred to as the "first printed matter") has a printed area containing discolored titanium oxide on at least a portion of a sheet medium, the sheet medium being selected from a paper or a film having a printable area containing titanium oxide, titanium oxide being added to the sheet medium, and when the sheet medium is paper, the content of titanium oxide in the printable area of ​​the sheet medium is 1.0 mass % or more, the length-weighted average fiber length of the pulp constituting the paper is 0.5 mm or more and 3.0 mm or less, the average fiber width of the pulp constituting the paper is 14.0 μm or more and 35.0 μm or less, and the mass per unit area of ​​the paper is 20 g / m 2 When the sheet medium is a thin film, the content of titanium oxide in the printable area of ​​the sheet medium is greater than 0.3% by mass, the thickness of the film is greater than 15 μm, the resin constituting the film comprises at least one selected from the group consisting of polyethylene, polypropylene, ethylene-propylene copolymer, polyethylene terephthalate, polylactic acid, and polybutylene succinate, and the ratio of the Raman intensity of titanium oxide originating from the printing area to the Raman intensity of titanium oxide originating from the non-printing area is less than 0.70.

[0105] According to the present invention, a printed matter having a printed area containing discolored titanium oxide and excellent visibility can be provided. In addition, the printed matter of the present invention has excellent print clarity and excellent solvent resistance. It should be noted that excellent print clarity (print clarity) is also referred to as excellent visibility.

[0106] The detailed reasons for obtaining the above-mentioned effects are not clear, but a part of them is considered as follows. In the present invention, a printing medium having a sheet medium selected from a paper or a film having a printable area in which titanium oxide is added at least inside and the content of titanium oxide is greater than a specific amount is used. It is believed that the printing area contains discolored titanium oxide, and the ratio of the Raman intensity of the titanium oxide in the printing area to the Raman intensity of the titanium oxide in the non-printing area is made to be less than 0.70, thereby obtaining a printed matter with excellent visibility. It is believed that for the discoloration of the above-mentioned titanium oxide, the ion valence of the titanium oxide contained in the sheet medium changes from 4 valences to 3 valences, and oxygen deficiency occurs, thereby changing from white to black, thereby becoming visible. Furthermore, the above-mentioned change in ion valence can be detected as a change in Raman intensity, and by making the ratio of the Raman intensity of the titanium oxide in the printing area to the Raman intensity of the titanium oxide in the non-printing area less than a specific value, a printing area with high visibility is obtained. It is believed that the ion valence of titanium oxide changes when irradiated with light energy equivalent to the band gap of titanium oxide. The band gap of titanium oxide varies depending on the crystal system, but is generally about 3.0 to 3.2 eV, and the wavelength of light corresponding to this is 420 nm or less. Therefore, even if a laser with a wavelength exceeding 420 nm (e.g., 532 nm, 1064 nm, 10600 nm) is used, it is difficult to implement printing caused by the change in the ion valence of titanium oxide as in the present invention.

[0107] In addition, it is considered that the sheet medium develops color due to titanium oxide contained in the sheet medium, and therefore has excellent solvent resistance.

[0108] It should be noted that the color change of titanium oxide is preferably performed by irradiation with ultraviolet laser. It should be noted that irradiation with ultraviolet laser sometimes generates smoke. It is believed that when titanium oxide is heated by irradiation with ultraviolet laser, the surrounding moisture is instantly vaporized, resulting in the phenomenon that the discolored titanium oxide and paper dust are separated from the sheet medium, and it is believed that smoke is generated along with this separation. When the sheet medium contains moisture, smoke becomes a problem, so when the sheet medium is a paper sheet medium, there is a tendency for smoke to occur.

[0109] In this embodiment, the printable area refers to the area (portion) where the titanium oxide contained in the sheet medium changes color, preferably the area (portion) where the titanium oxide irradiated by the ultraviolet laser changes from white to black by irradiation of the ultraviolet laser, and the printing area refers to the area in the printable area where the titanium oxide actually changes color, preferably the area in the printable area where the titanium oxide changes color and becomes visible by irradiation of the ultraviolet laser, that is, the area irradiated by the ultraviolet laser. In addition, the non-printing area refers to the area (portion) in the printable area where the titanium oxide does not change color, for example, the area (portion) where the ultraviolet laser is not irradiated.

[0110] Hereinafter, the first printed matter of the present invention will be described in further detail.

[0111] 〔Sheet Media〕

[0112] The printing medium to be printed includes at least a sheet medium selected from paper or film having a printable area containing titanium oxide, and at least a portion of the sheet medium has a print area containing discolored titanium oxide. In the present invention, the printing medium may be the sheet medium itself containing titanium oxide, or a transparent resin layer may be provided on the sheet medium. That is, the "printing medium" refers to both the sheet medium itself and the sheet medium having a transparent resin layer provided thereon.

[0113] When the sheet medium is paper, the content of titanium oxide in the printable area is, from the viewpoint of obtaining sufficient printing density, not less than 1.0 mass %, preferably not less than 8.0 mass %, more preferably not less than 15 mass %, further preferably not less than 25 mass %, and further preferably not less than 35 mass %, and from the viewpoint of maximizing the printing density and suppressing the cost increase caused by containing titanium oxide more than the required amount, it is preferably not more than 50 mass %, and more preferably not more than 45 mass %.

[0114] In addition, when the sheet medium is a thin film, the content of titanium oxide in the printable area is, from the viewpoint of obtaining a sufficient printing concentration, not less than 0.3 mass %, preferably not less than 0.5 mass %, preferably not less than 2.0 mass %, and more preferably not less than 4.0 mass %; and from the viewpoint of maximizing the printing concentration, suppressing the increase in cost caused by containing titanium oxide more than the required amount, and suppressing the reduction in the strength of the thin film, it is preferably not more than 50 mass %, more preferably not more than 45 mass %, further preferably not more than 35 mass %, further preferably not more than 25 mass %, further preferably not more than 15 mass %, further preferably not more than 10 mass %, and further preferably not more than 7.5 mass %.

[0115] It should be noted that at least the printable area of ​​the sheet medium only needs to contain titanium oxide, and the unprinted area may also contain an area with a titanium oxide content below the above lower limit. From the perspective of ease of production, it is preferred that the entire area of ​​the sheet medium contains titanium oxide above the above lower limit.

[0116] <Titanium oxide>

[0117] Titanium oxide is added to (encapsulated in) the sheet medium, and more preferably, titanium oxide is added to a sheet medium raw material and then formed into paper or a sheet.

[0118] The titanium oxide contained in the sheet medium is represented by the composition formula TiO2, also known as titanium dioxide or Titania.

[0119] Titanium oxide may be a crystalline structure or an amorphous structure. It is preferably at least one selected from rutile titanium oxide, anatase titanium oxide, brookite titanium oxide, and amorphous titanium oxide. From the viewpoint of availability and stability, it is more preferred that titanium oxide be at least one selected from rutile titanium oxide and anatase titanium oxide, and rutile titanium oxide is further preferred.

[0120] The crystal form of titanium oxide can be determined by a known method, specifically, by analysis of Raman spectroscopy, XRD spectra, etc. For example, in the case of identification by Raman spectroscopy, in general, in the rutile type, the crystal form of titanium oxide is determined at 447±3 cm -1 、609cm -1 A peak was confirmed at 395±3cm in anatase type. -1 、516±3cm -1 、637±3cm -1 The peak was confirmed.

[0121] The titanium oxide may be used alone or in combination of two or more.

[0122] The shape of titanium oxide is not particularly limited, and may be any shape such as amorphous, spherical, rod-like, or needle-like.

[0123] When the titanium oxide is amorphous or spherical, the particle size of the titanium oxide is not particularly limited. From the viewpoint of being easy to stay on paper during the papermaking process and obtaining a sheet with excellent surface smoothness, it is preferably 0.01 μm or more, more preferably 0.10 μm or more, and further preferably 0.15 μm or more, and is preferably 20.0 μm or less, more preferably 10.0 μm or less, and further preferably 5.0 μm or less.

[0124] The particle size of titanium oxide added to paper and film is calculated from an SEM image obtained by a scanning electron microscope (SEM, manufactured by Hitachi High-Technologies Corporation, S5200, etc.) of ash obtained by burning a sheet medium or printed matter in a muffle furnace.

[0125] The sample of ash content under the scanning electron microscope can be made as follows: applied to an ultrasonic homogenizer (Yamato Scientific Co., Ltd. system, LUH150, etc.) with a power of 50W for 5 minutes, and dispersed in ethanol to obtain a 0.01% by mass slurry, 0.1mL is cast into an aluminum dish, and dried at 60°C, so that it can be made. Visually select those that can be clearly distinguished from adjacent particles, and the major diameter of one particle is used as the particle size. At this time, even if the primary particles are mixed with the secondary particles in the aggregated state and can be clearly distinguished, they are counted as one particle, and the average diameter of 100 randomly selected particles is used as the particle size. The magnification during SEM image observation can be appropriately selected according to the particle size of titanium oxide, preferably about 20,000 times. In addition, in the case of particles other than titanium oxide, the energy dispersive X-ray analyzer attached to SEM (manufactured by Horiba, Ltd., EMAX, etc.) is used to measure the particles containing titanium element.

[0126] It should be noted that the average particle size of the titanium oxide particles used as a raw material can be obtained as a median particle size measured by a laser diffraction / scattering particle size distribution meter (manufactured by Horiba, Ltd., LA-300, etc.). The measurement conditions are preferably the following conditions. It should be noted that the average particle size obtained by the laser diffraction / scattering particle size distribution meter sometimes deviates from the particle size calculated from the scanning electron microscope photograph by about ±50%.

[0127] Dispersion medium: ion exchange water,

[0128] Determine the refractive index of particles: 2.75-0.01i,

[0129] Solvent refractive index: 1.333,

[0130] Built-in ultrasonic irradiation (30W): 3 minutes,

[0131] Cycle speed: 3

[0132] In addition, when the titanium oxide is needle-shaped, the major diameter of the titanium oxide is not particularly limited. From the perspective of being easy to stay on the paper in the papermaking process and obtaining a sheet with excellent surface smoothness, it is preferably 0.1 μm or more, more preferably 0.5 μm or more, and further preferably 1.5 μm or more, and preferably 50.0 μm or less, more preferably 30.0 μm or less, and further preferably 15.0 μm or less. In addition, the minor diameter is preferably 0.01 μm or more, more preferably 0.03 μm or more, and further preferably 0.05 μm or more, and preferably 3.0 μm or less, more preferably 1.5 μm or less, and further preferably 1.0 μm or less. In addition, when the titanium oxide is needle-shaped, the aspect ratio (major diameter / minor diameter) is preferably 5 or more, more preferably 10 or more, and further preferably 15 or more, and preferably 300 or less, more preferably 100 or less, and further preferably 30 or less.

[0133] The major and minor diameters of titanium oxide added to paper and film can be measured by treating the ash obtained by burning a sheet medium or printed matter in a muffle furnace in the same manner as described above, and then measuring the ash from a scanning electron microscope (SEM, manufactured by Hitachi High-Technologies Corporation, S5200, etc.). The powder tested under the scanning electron microscope is obtained in the same manner as described above.

[0134] The major axis and minor axis of titanium oxide used as a raw material can also be measured from a SEM image obtained using a scanning electron microscope.

[0135] <Paper>

[0136] When the sheet medium is paper, the sheet medium is also referred to as paper sheet medium.

[0137] As the raw material pulp constituting the paper sheet medium, for example, wood pulp, non-wood pulp, and deinked pulp can be cited. As the wood pulp, there is no particular limitation, and for example, chemical pulps such as broadleaf bleached kraft pulp (LBKP), broadleaf unbleached kraft pulp (LUKP), conifer bleached kraft pulp (NBKP), conifer unbleached kraft pulp (NUKP), sulfite pulp (SP), dissolving pulp (DP), alkaline pulp (AP), oxygen bleached kraft pulp (OKP), semi-chemical pulps such as semi-chemical pulp (SCP), chemical groundwood pulp (CGP), groundwood pulp (GP), thermomechanical pulp (TMP), chemical thermomechanical pulp (CTMP) and other mechanical pulps can be cited. As the non-wood pulp, there is no particular limitation, and for example, cotton pulps such as cotton lint and lint, and non-wood pulps such as hemp, straw, bamboo, and bagasse can be cited. The deinked pulp is not particularly limited, and examples thereof include deinked pulp made from waste paper. The raw material pulp may be one of the above-mentioned pulps alone, or two or more of the above-mentioned pulps may be mixed. It should be noted that the raw material pulp may be mixed with organic synthetic fibers such as polyamide fibers and polyester fibers, recycled fibers such as polynosic fibers, and inorganic fibers such as glass fibers, ceramic fibers, and carbon fibers.

[0138] As for the raw material pulp, wood pulp and deinked pulp are preferred from the viewpoint of easy availability. In addition, among wood pulps, chemical pulp is preferred from the viewpoint of uniformity of texture, and kraft pulp is more preferred. The raw material pulp is preferably one or more selected from kraft pulp of broadleaf trees such as eucalyptus and acacia, and kraft pulp of coniferous trees such as pine and cedar, and is further preferably one or more selected from bleached kraft pulp of broadleaf trees (LBKP) and bleached kraft pulp of coniferous trees (NBKP). Among these, the one with a higher ratio of LBKP is more preferred, for example, the mixing ratio of LBKP and NBKP LBKP / NBKP is more preferably 75 / 25 to 100 / 0 (mass %).

[0139] The length-weighted average fiber length of the pulp constituting the paper sheet medium is 0.5 mm or more, preferably 0.6 mm or more, and 3.0 mm or less, preferably 2.8 mm or less, more preferably 2.5 mm or less, further preferably 2.0 mm or less, further preferably 1.5 mm or less, further preferably 1.0 mm or less.

[0140] If the length-weighted average fiber length of the pulp constituting the paper sheet medium is 3.0 mm or less, the pulps are densely entangled with each other, so that the pores of the paper sheet medium are reduced, and when irradiated with ultraviolet laser, the scattering of titanium oxide can be suppressed, smoke generation is suppressed, and a printed matter with excellent visibility is obtained, which is preferred. In addition, if the length-weighted average fiber length is 0.5 mm or more, the strength of the paper sheet medium is improved, and when irradiated with ultraviolet laser, the fibers are not easily detached from the paper sheet medium, the generation of paper dust is suppressed, the amount of smoke generation is suppressed, and the print clarity is excellent, which is preferred.

[0141] The length-weighted average fiber length of the pulp constituting the sheet medium was measured according to the method described in Examples.

[0142] The average fiber width of the pulp constituting the paper sheet medium is 14.0 μm or more, preferably 15.0 μm or more, more preferably 15.5 μm or more, and further preferably 16.0 μm or more, and is 35.0 μm or less, preferably 33.0 μm or less, more preferably 31.0 μm or less, further preferably 28.0 μm or less, further preferably 24.0 μm or less, and further preferably 21.0 μm or less.

[0143] If the average fiber width of the pulp constituting the paper sheet medium is 35.0 μm or less, the pulp is densely entangled with each other, so that the pores of the paper sheet medium are reduced, and when irradiated with ultraviolet laser, the scattering of titanium oxide can be suppressed, smoke generation is suppressed, and a printed matter with excellent visibility is obtained, which is preferred. In addition, if the average fiber width is 14.0 μm or more, the strength of the paper sheet medium is improved, and when irradiated with ultraviolet laser, the fibers are not easily detached from the paper sheet medium, the generation of paper dust is suppressed, the amount of smoke generation is suppressed, and the print clarity is excellent, which is preferred.

[0144] The average fiber width of the pulp constituting the sheet medium can be measured by the method described in Examples.

[0145] In the pulp constituting the paper sheet medium, the number ratio of fine fibers with a fiber length of 0.2 mm or less is preferably 6.2% or more, more preferably 6.5% or more, further preferably 6.8% or more, and is preferably 30% or less, more preferably 24% or less, further preferably 16% or less.

[0146] If the ratio of the number of fine fibers is 6.2% or more, the fine fibers are arranged in the sheet in the form of filling the pores between the fibers, and the scattering of titanium oxide when irradiated with ultraviolet laser is suppressed. As a result, the smoke generated when irradiated with ultraviolet laser is suppressed, and the visibility is improved, which is preferred. In addition, if the ratio of the number of fine fibers is 30% or less, the smoke generated by the scattering of fine fibers when irradiated with ultraviolet laser is suppressed due to the increase in the number of fine fibers, which is preferred.

[0147] The ratio of the number of fine fibers having a fiber length of 0.2 mm or less in the pulp of the fibers constituting the sheet medium is calculated as follows: the sheet medium is disintegrated by the method described in the Examples, and the fiber length of the obtained pulp slurry is measured using a fiber length measuring device (e.g., Valmet, Model FS-5, with UHD base unit) to calculate the ratio of the number of fine fibers to the measured number of pulp fibers, wherein fibers having a fiber length of 0.2 mm or less and a fiber width of 75 μm or less are formed into fine fibers.

[0148] The Canadian standard freeness (CSF) of the wood pulp used in the sheet medium is preferably 150 to 500 mL. If the wood pulp is within this range, the uniformity of titanium oxide added thereto is excellent. Here, CSF is based on the Canadian standard freeness of JIS P8121-2:2012.

[0149] The sheet medium is obtained by making paper from pulp slurry to which titanium oxide particles and, if necessary, internal additives are added.

[0150] Fillers other than titanium oxide may be added to the paper medium as needed. Examples of fillers other than titanium oxide include kaolin, talc, heavy calcium carbonate, light calcium carbonate, calcium sulfite, gypsum, calcined kaolin, white carbon, amorphous silica, delaminated kaolin, diatomaceous earth, magnesium carbonate, aluminum hydroxide, calcium hydroxide, magnesium hydroxide, zinc hydroxide, and the like.

[0151] In addition to pulp, titanium oxide and fillers, the paper sheet medium may also contain sizing agents, drying enhancers, paper wet strength agents (e.g., polyamide polyamine epichlorohydrin), yield improvers (e.g., aluminum sulfate), filterability improvers, pH adjusters, softeners, antistatic agents, defoamers, dyes / pigments and other known internal additives for papermaking as needed.

[0152] Examples of the sizing agent include rosin-based, alkyl ketene dimer-based, alkenyl succinic anhydride-based, styrene-acrylic, higher fatty acid-based, and petroleum resin-based sizing agents.

[0153] The mass per unit area of ​​the paper medium is 20 g / m from the perspective of visibility. 2 Above, preferably 40g / m 2 More preferably 50 g / m 2 More preferably 60g / m 2 More than, and preferably 600g / m 2 Below, more preferably 400g / m2 Below, more preferably 200g / m 2 Below, more preferably 100g / m 2 the following.

[0154] If the mass per unit area of ​​the paper medium is 20g / m 2 If the above value is used, the opacity of the paper sheet medium is high, and a printed material with high visibility can be obtained. In addition, the upper limit of the mass per unit area of ​​the paper sheet medium can be appropriately selected according to the strength required for the application and the like.

[0155] The mass per unit area is measured by the method specified in JIS P 8124:2011.

[0156] The thickness of the paper sheet medium is not particularly limited, but is preferably 10 μm or more, more preferably 25 μm or more, and further preferably 40 μm or more from the viewpoint of stiffness of the sheet medium and good operability, and is preferably 700 μm or less, more preferably 500 μm or less, and further preferably 400 μm or less from the viewpoint of good economy and operability. The thickness of the paper sheet medium can be measured by the method described in JIS P 8118:2014.

[0157] The whiteness of the sheet medium or the printing medium having the sheet medium can be appropriately selected according to the application, and is not particularly limited. From the viewpoint of easily providing contrast between the printed area and the non-printed area and improving visibility, it is preferably 9% or more, more preferably 50% or more, and further preferably 80% or more, and from the viewpoint of ease of production, it is preferably 95% or less, and more preferably 92% or less. The whiteness of the sheet medium can be measured using a spectroscopic whiteness colorimeter (manufactured by SUGA TEST INSTRUMENTS CO., LTD.) according to the method described in JIS P 8148:2018.

[0158] In papermaking of paper sheet media, a known wet paper machine, such as a fourdrinier paper machine, a gap-wire paper machine, a cylinder paper machine, a short-wire paper machine, etc., can be appropriately selected and used. Next, the paper layer formed by the paper machine is conveyed to a felt and dried in a dryer. A multi-stage drum dryer can also be used as a pre-dryer before drying in the dryer.

[0159] In addition, the paper sheet medium obtained as described above may be subjected to a surface treatment by calendering to achieve uniformity of thickness and profile and improve printability. For the calendering treatment, a known calendering machine may be appropriately selected and used.

[0160] <Film>

[0161] When the sheet medium is a film, the sheet medium is also referred to as a film medium.

[0162] The resin constituting the thin film medium is not particularly limited as long as it can encapsulate titanium oxide and be processed into a thin film. It can be appropriately selected from known thermoplastic resins. Specifically, polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyolefin resins such as polyvinyl chloride, polyvinylidene chloride, polybutene, polybutadiene, ethylene-vinyl acetate copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, and polymethylpentene; polycarbonate; polyurethane; polyamide; polyacrylonitrile; poly(meth)acrylate, etc.

[0163] Among these, the resin constituting the film medium preferably contains polyolefins such as polyethylene, polypropylene, and ethylene-propylene copolymers, and polyesters such as polyethylene terephthalate, polybutylene terephthalate, polylactic acid, and polybutylene succinate, from the viewpoints of being generally usable, having high ultraviolet transmittance, and being able to discolor titanium oxide to the inside of the film medium. It is more preferable to contain at least one selected from the group consisting of polyethylene, polypropylene, ethylene-propylene copolymers, polyethylene terephthalate, polylactic acid, and polybutylene succinate, and it is further preferable to contain at least one selected from the group consisting of polyethylene, polypropylene, ethylene-propylene copolymers, polyethylene terephthalate, polylactic acid, and polybutylene succinate. The resin constituting the film medium is further preferably a polyolefin, and further preferably at least one selected from the group consisting of polyethylene and polypropylene.

[0164] These resins may be used alone or in combination of two or more.

[0165] The film medium can be produced by appropriately selecting from conventionally known production methods, for example, a method appropriately selected from melt extrusion, melt casting, calendaring, and the like.

[0166] The thin film may be prepared by mixing titanium oxide with the above-mentioned resin so that the content of titanium oxide in the printing area of ​​the thin film medium is within the above-mentioned range.

[0167] As the film medium, synthetic paper having a titanium oxide content within the range of the present invention may be used.

[0168] From the viewpoint of obtaining a printed material with excellent strength, the thickness of the film medium is 15 μm or more, preferably 20 μm or more, more preferably 40 μm or more, further preferably 50 μm or more, further preferably 55 μm or more, and is preferably 700 μm or less, more preferably 500 μm or less, further preferably 350 μm or less, further preferably 250 μm or less.

[0169] It should be noted that if the thickness of the film medium is within the above range, when the film medium is irradiated with ultraviolet laser, degradation of the resin near the surface of the film is observed, but the sufficient thickness of the film medium is preferred to suppress the reduction in the strength of the printed matter.

[0170] 〔Raman intensity〕

[0171] In the first printed material of the present invention, the printed area refers to the area (portion) containing the discolored titanium oxide in the printable area, preferably the area (portion) printed by ultraviolet laser. The non-printed area refers to the area (portion) not printed in the printable area.

[0172] The ratio of the Raman intensity of titanium oxide in the printed area to the Raman intensity of titanium oxide in the non-printed area (Raman intensity in the printed area / Raman intensity in the non-printed area) is 0.70 or less. By making the Raman intensity ratio within the above range, a printed material with excellent visibility can be obtained.

[0173] Regarding the above Raman intensity ratio (Raman intensity of the printed area / Raman intensity of the non-printed area), when rutile titanium oxide is used as titanium oxide, the Raman intensity derived from titanium oxide is 447±3 cm -1 In addition, when anatase titanium oxide is used as titanium oxide, the Raman intensity derived from titanium oxide is compared with 516±3 cm -1 The maximum Raman intensity in the wavenumber range.

[0174] In addition, when rutile titanium oxide and anatase titanium oxide coexist, the Raman intensity derived from rutile titanium oxide is used for comparison.

[0175] The printed matter of the present invention preferably has a non-printing area in white and a printing area in black.

[0176] The non-printed area preferably has a lightness of 10 in the Munsell color system, that is, white. On the other hand, the printed area preferably has a lightness of 0 to 8 in the Munsell color system, more preferably 0 to 6, and even more preferably 0 to 4.

[0177] In order to obtain the color in the above-mentioned Munsell colorimetric system, it is preferred to appropriately adjust the titanium oxide content in the sheet medium, other properties of the sheet medium (the length-weighted average fiber length of the pulp constituting the sheet medium in the case of a paper sheet medium, the average fiber width, the weight per square meter of the paper sheet medium; the type of resin in the case of a film medium, the thickness of the film medium, etc.), and the irradiation conditions of the ultraviolet laser (such as average power, repetition frequency, wavelength, etc.).

[0178] The first printed matter of the present invention is suitable for use in packaging, labels, adhesive tapes, and the like.

[0179] Examples of packaging bodies include inner lining paper of corrugated cardboard (especially the outermost inner lining paper), outer boxes, milk bags, liquid containers for beverages such as paper cups (preferably liquid paper containers for beverages), food trays, and skin packaging. Examples of labels include label paper, adhesive labels, and adhesive sheets. Examples of adhesive tapes include adhesive tapes and kraft paper tapes.

[0180] like Figure 5 As shown, a liquid container 10 as an example of a package has, for example, a printed area 20 on its surface. The printed area 20 is irradiated with ultraviolet laser light to print characters such as a date.

[0181] 〔Transparent resin layer〕

[0182] The printed article of the present invention preferably further includes a transparent resin layer on the printable region of the sheet medium.

[0183] That is, it is preferable to use a printing medium in which a transparent resin layer is provided in advance on a sheet medium containing a predetermined amount or more of titanium oxide in a printable region.

[0184] The invention has been found that the above-mentioned configuration can provide a higher print density and a clearer printed image. The detailed reason for this is not clear, but it is partially estimated as follows.

[0185] It is believed that when titanium oxide is heated by ultraviolet laser irradiation, the surrounding moisture vaporizes instantly, causing the discolored titanium oxide to separate from the sheet medium. It is believed that by pre-arranging a transparent resin layer on the sheet medium, the separation of the discolored titanium oxide is suppressed, and the printing density becomes higher.

[0186] In view of the fact that the effect of providing a transparent resin layer is high when the sheet medium contains moisture, it is particularly preferable to have a transparent resin layer when the sheet medium is a paper sheet medium.

[0187] The total light transmittance of the transparent resin layer is 80% or more, preferably 85% or more, more preferably 90% or more, and further preferably 91% or more, and is 100% or less. The upper limit is not particularly limited.

[0188] The total light transmittance is measured in accordance with JIS K 7361-1:1997.

[0189] The resin constituting the transparent resin layer is not particularly limited as long as it has a total light transmittance of 80% or more and can be arranged on a sheet substrate. From the viewpoint of transparency and ease of setting the transparent resin layer, when the transparent resin layer and the sheet medium are adhered to each other with the aid of an adhesive layer or laminated by lamination, it is preferably selected from at least one of polyethylene, polypropylene, polyethylene terephthalate, polyvinyl alcohol, and starch, more preferably selected from at least one of polyethylene, polypropylene, polyethylene terephthalate, and polyvinyl alcohol, further preferably polyethylene and polypropylene, and particularly preferably polyethylene.

[0190] When the transparent resin layer is provided by coating, examples thereof include acrylic resins, styrene-maleic acid resins, water-soluble polyurethane resins, and water-soluble polyester resins.

[0191] Examples of acrylic resins include resins obtained by copolymerizing (meth)acrylic acid, its alkyl ester, styrene, unsaturated carboxylic acids other than (meth)acrylic acid, ethylene, propylene and other monomers. Specifically, examples include ethylene-(meth)acrylic acid copolymers and styrene-acrylic acid-maleic acid resins, among which ethylene-(meth)acrylic acid copolymers are preferred.

[0192] The transparent resin layer and the sheet medium may be laminated by any method without particular limitation, but from the viewpoint of ease of production, it is preferred that the transparent resin layer and the sheet medium are adhered to each other via an adhesive layer, or laminated, or coated with a transparent coating in the form of a liquid coating.

[0193] When the transparent resin layer is provided locally, it is preferably pasted with an adhesive from the viewpoint of ease of production. In addition, when the transparent resin layer is provided over a wide range, it is preferably laminated.

[0194] The adhesive layer is not particularly limited, and may be appropriately selected from known adhesive layers and used. Specifically, the adhesive layer disclosed in Japanese Unexamined Patent Application Publication No. 2012-57112 may be exemplified.

[0195] The thickness of the transparent resin layer is not particularly limited, but is preferably 5 μm or more, more preferably 10 μm, and further preferably 15 μm or more, and is preferably 100 μm or less, more preferably 75 μm or less, and further preferably 50 μm or less, from the perspective of obtaining clear printing and the operability of printed materials and printed media.

[0196] [Method for producing first printed matter]

[0197] The first method for manufacturing printed matter of the present invention comprises the following steps: irradiating a sheet medium selected from paper or film, or a printing medium having a transparent resin layer on the sheet medium, with ultraviolet laser light to discolor the irradiated area, thereby performing printing, wherein titanium oxide is added to the sheet medium, and the content of titanium oxide in the sheet medium is greater than a specified amount.

[0198] As the sheet medium and the print medium used in the method for manufacturing the first printed matter of the present invention, the same sheet medium and the print medium as those in the first printed matter can be exemplified, and the preferred ranges are the same. In addition, in the method for manufacturing the first printed matter of the present invention, as long as the titanium oxide content in at least the ultraviolet laser irradiation area is greater than or equal to a prescribed amount, there is no particular limitation on the titanium oxide content in the non-irradiation area. Since titanium oxide is added internally to the sheet medium, it is preferred that the titanium oxide content in the non-irradiation area is greater than or equal to the prescribed amount.

[0199] The ultraviolet laser irradiation is preferably performed so that the ratio of the Raman intensity derived from titanium oxide in the printed area to the Raman intensity derived from titanium oxide in the non-printed area becomes 0.70 or less.

[0200] The Raman intensities in the printed area and the non-printed area are as described above in the printed matter.

[0201] [Ultraviolet laser irradiation conditions]

[0202] From the viewpoint of improving the visibility of the printed area, the wavelength of the ultraviolet laser is preferably 370 nm or less, more preferably 365 nm or less, further preferably 360 nm or less, and is preferably 260 nm or more, more preferably 340 nm or more, further preferably 350 nm or more.

[0203] The average power of the ultraviolet laser is preferably 0.3 W or more, more preferably 0.8 W or more, further preferably 1.2 W or more, and further preferably 1.8 W or more from the viewpoint of improving the visibility of the printed area, and is preferably 30 W or less, more preferably 25 W or less, further preferably 20 W or less, further preferably 15 W or less, further preferably 10 W or less, and further preferably 6 W or less from the viewpoint of economy.

[0204] The repetition frequency of the ultraviolet laser is preferably 10 kHz or more, more preferably 20 kHz or more, further preferably 30 kHz or more, and is preferably 100 kHz or less, more preferably 80 kHz or less, further preferably 60 kHz or less, from the viewpoint of improving the visibility of the printed area.

[0205] The spot diameter of the ultraviolet laser is preferably 10 μm or more, more preferably 20 μm or more, further preferably 30 μm or more, and is preferably 300 μm or less, more preferably 240 μm or less, further preferably 180 μm or less, further preferably 120 μm or less, from the viewpoint of obtaining a clear image and easiness of printing.

[0206] The scanning speed of the ultraviolet laser is preferably 500 mm / second or more, more preferably 1000 mm / second or more, further preferably 2000 mm / second or more, and preferably 7000 mm / second or less, more preferably 6000 mm / second or less, further preferably 5000 mm / second or less, from the viewpoint of high-speed printing and visibility of the printed area.

[0207] From the viewpoint of obtaining a clear image and the ease of obtaining the device, the line pitch of the ultraviolet laser is preferably greater than 10 μm, more preferably greater than 20 μm, and further preferably greater than 30 μm, and is preferably less than 300 μm, more preferably less than 250 μm, and further preferably less than 200 μm.

[0208] [Method for producing the first printed matter]

[0209] The method for producing the first printed matter of the present invention can be performed in various ways.

[0210] Various embodiments to which the method for producing the first printed matter of the present invention can be applied are exemplified below, but the method for producing the first printed matter of the present invention is not limited to the embodiments described below. The information to be printed is not particularly limited, but variable information is preferred.

[0211] The method for producing the first printed matter of the present invention is preferably performed online.

[0212] (1) Direct printing on packaging

[0213] A first embodiment of the method for producing a first printed article of the present invention is a method for printing information on a package containing titanium oxide, and includes the step of directly printing on a package that is moving or intermittently stopped on a packaging line under ultraviolet laser.

[0214] In the method for producing printed matter of the first embodiment, a package is made of a printing medium having a sheet medium containing a predetermined amount or more of titanium oxide, and is directly printed under ultraviolet laser light. It should be noted that at least the outermost layer of the package is made of a printing medium having a sheet medium containing a predetermined amount or more of titanium oxide.

[0215] In addition, as a packaging body, corrugated cardboard, a box, etc. can be exemplified, and it is preferable to directly print on the side surface or the upper surface of the packaging body under ultraviolet laser.

[0216] (2) Printing of labels

[0217] A second embodiment of the method for producing the first printed matter of the present invention is a method for printing information on a label containing titanium oxide. The printing medium constituting the printing surface of the label has a sheet medium containing a predetermined amount or more of titanium oxide.

[0218] The printed label is preferably affixed to the package using a label affixing device. Various label affixing devices have been proposed as the label affixing device.

[0219] As the first label sticking device, an adhesive is applied to the label base paper wound into a roll and then affixed to an article. More specifically, the following roll labeling machine can be exemplified, which comprises: a cutting unit that cuts each sheet of the label base paper wound into a roll into a predetermined length; an adhesive conveying unit that receives the label base paper cut by the cutting unit by a label base paper holder coated with an adhesive, and makes the adhesive adhere to the back of the label base paper; and an attaching unit that receives the label base paper (label) to which the adhesive is applied by the adhesive conveying unit and affixes it to an article such as a container, wherein a rotating conveying unit having a label holding surface on the outer surface is provided between the cutting unit and the adhesive conveying unit, and an example of which can be given is Japanese Patent Publication No. 6-64637.

[0220] In addition, there can be exemplified a roller labeling machine having a cutting unit for cutting each sheet of label paper wound into a roll into a specified length, a delivery roller for delivering to a pasting roller, and an adhesive roller for applying glue to the label paper held by the pasting roller; a method without the aforementioned delivery roller.

[0221] The ultraviolet laser irradiation is preferably performed before the label base paper wound into a roll is cut into a predetermined length, or after being cut and before being handed over to the next roll, etc. According to the method of the roll labeling machine, the surface or back side of the label base paper wound into a roll becomes the surface or back side when attached to the package body, and therefore, the ultraviolet laser irradiation is performed accordingly.

[0222] The second label sticking device uses an adhesive label roll as a label.

[0223] When using an adhesive label roll with release paper, for example, the following adhesion device can be exemplified, which has: a release paper separation unit for separating the adhesive label from the release paper; a handover roller for receiving the adhesive label separated from the release paper; and an adhesion roller for sucking the adhesive label by the handover roller and affixing it to an article (package). Preferably, the irradiation based on ultraviolet laser is performed before separating the release paper, or after the release paper is separated and before being loaded on the adhesion roller.

[0224] In addition, the following device can be exemplified: a device having an adhesive label roll with a release paper attached, a mechanism for separating the adhesive label from the release paper, a mechanism for pasting the label just after separation, and a device for printing by an ultraviolet laser during the period until the installed adhesive label roll is separated from the release paper. The method of pasting the above-mentioned adhesive label is also referred to as unidirectional installation (in Japanese: 流し貼り).

[0225] Furthermore, the following label adhesion device can be exemplified: a device having an adhesive label roll with a release paper attached, a mechanism for separating the release paper from the adhesive label, and a mechanism for pasting the adhesive label onto an article (package), wherein the aforementioned pasting mechanism is a syringe method, an air jet method, or a robotic arm method. Irradiation with an ultraviolet laser is preferably performed during the period until the installed adhesive label roll with the release paper is separated from the release paper.

[0226] As the label, a label without a liner can also be used. A label without a liner is a label without a release paper and has the following characteristics compared to the case of using an adhesive label roll with a release paper: the number of label sheets per roll is large, there is no release paper, and thus it is inexpensive.

[0227] As a label adhesion device using a label without a liner, the following device can be exemplified: a device having a mechanism for installing a roll of labels without a liner, a cutting mechanism for cutting each label without a liner into one sheet, and a pasting mechanism for pasting the cut label without a liner onto an article (package), wherein the aforementioned pasting mechanism is a barrel method or a robotic arm method. Printing by irradiation with an ultraviolet laser is preferably performed between the mechanism for installing the roll of labels without a liner and the cutting mechanism, or during the period when the cut label without a liner is conveyed to the pasting mechanism.

[0228] For the third label adhesion device, after pasting a printing medium having a sheet medium containing a predetermined amount or more of titanium oxide onto an article (package), printing is performed under an ultraviolet laser.

[0229] As a method of pasting a label, refer to the first device and the second device described above.

[0230] (3) Printing on the adhesive tape

[0231] The third embodiment of the method for manufacturing the first printed matter of the present invention is a method using a printing medium having a sheet medium containing a predetermined amount or more of titanium oxide as an adhesive tape.

[0232] That is, the method for manufacturing the printed matter of the third embodiment includes the following steps: a step of pasting an adhesive tape made of a printing medium having the aforementioned sheet medium onto an article (package), and a step of printing by an ultraviolet laser before or after the aforementioned pasting step.

[0233] Alternatively, a printing device in which a printing device based on ultraviolet laser is installed in a corrugated cardboard wrapping machine may be used. Specifically, the printing device has a mechanism for installing a tape winding device, a conveyor for conveying corrugated cardboard, a mechanism for folding a baffle of the corrugated cardboard, a mechanism for attaching the tape to wrap the corrugated cardboard, and a mechanism for printing on the tape under ultraviolet laser during or after attaching the tape.

[0234] The first printed article and the method for producing the first printed article of the present invention are not limited to the above-mentioned aspects, and can be used for various applications requiring printing.

[0235] [First Laser Printing Printing Medium]

[0236] The first laser printing medium of the present invention comprises a sheet medium selected from paper or film having a printable area that can be printed using an ultraviolet laser, wherein when the sheet medium is paper, the content of titanium oxide in the printable area of ​​the sheet medium is 1.0 mass % or more, the length-weighted average fiber length of the pulp constituting the paper is 0.5 mm or more and 3.0 mm or less, the average fiber width of the pulp constituting the paper is 14.0 μm or more and 35.0 μm or less, and the mass per unit area of ​​the paper is 20 g / m 2 When the sheet medium is a film, the content of titanium oxide in the printable region of the sheet medium is 0.3 mass % or more, the thickness of the film is 15 μm or more, and the resin constituting the film includes at least one selected from the group consisting of polyethylene, polypropylene, ethylene-propylene copolymer, polyethylene terephthalate, polylactic acid, and polybutylene succinate. The first laser printable print medium of the present invention can be printed by irradiating it with ultraviolet laser.

[0237] Preferred embodiments of the first laser printable printing medium are the same as preferred embodiments of the sheet medium in the first printed matter, and preferred embodiments of the printing method for the first laser printable printing medium are the same as the method for manufacturing the first printed matter.

[0238] [Second Printing]

[0239] The second printed matter of the present invention (hereinafter, also referred to as the "second printed matter") has a printed region containing discolored titanium oxide on at least a portion of a recording medium (hereinafter, also referred to as the "printing medium") having a printable region containing titanium oxide, the printable region of the recording medium having a coating layer containing titanium oxide on a paper substrate, the length-weighted average fiber length of the pulp constituting the paper substrate being 0.6 mm or more and 3.5 mm or less, and the content of titanium oxide in the coating layer being 0.6 g / m 2 Above and 30g / m 2Hereinafter, the content of titanium oxide in the coating layer is denoted as Ag / m 2 When the thickness of the coating layer is set to B μm, A / B is greater than or equal to 0.01 and less than or equal to 2.00, and the ratio of the Raman intensity of titanium oxide in the printed area to the Raman intensity of titanium oxide in the non-printed area is less than or equal to 0.70.

[0240] According to the present invention, a printed matter having a printed area containing discolored titanium oxide can be provided. In addition, the printed matter of the present invention has excellent print clarity and excellent solvent resistance. It should be noted that excellent print clarity (print clarity) is also referred to as excellent visibility.

[0241] The detailed reasons for obtaining the above effects are not clear, but part of them are considered as follows. In the present invention, it is considered that the titanium oxide content on the substrate is 0.6 g / m 2 Above and 30g / m 2 The following coating layer serves as a recording medium for a printable area. The printing area has discolored titanium oxide, and the ratio of the Raman intensity of the titanium oxide in the printing area to the Raman intensity of the titanium oxide in the non-printing area is made to be 0.70 or less, thereby obtaining a print with excellent visibility. For the discoloration of the aforementioned titanium oxide, it is believed that the ionic valence of the titanium oxide contained in the coating layer changes from 4 valences to 3 valences, resulting in oxygen deficiency, thereby changing from white to black, thereby becoming visible. Furthermore, the aforementioned change in ionic valence can be detected as a change in Raman intensity, and a print with high visibility is obtained by making the ratio of the Raman intensity of the titanium oxide in the printing area to the Raman intensity of the titanium oxide in the non-printing area below a specific value. It is believed that the ionic valence of titanium oxide changes when irradiated with light energy equivalent to the band gap of titanium oxide. The band gap of titanium oxide varies depending on the crystal system, and is generally around 3.0 to 3.2 eV, and the wavelength of light corresponding to it is 420 nm or less. Therefore, even if a laser beam having a wavelength exceeding 420 nm (eg, 532 nm, 1064 nm, or 10600 nm) is used, it is difficult to perform printing due to a change in the ion valence of titanium oxide as in the present invention.

[0242] In addition, it is considered that the coating layer is colored due to titanium oxide contained in the coating layer, and therefore has excellent solvent resistance.

[0243] It should be noted that the color change of titanium oxide is preferably performed by irradiation with ultraviolet laser.

[0244] It is considered that by setting the length-weighted average fiber length of the pulp constituting the paper substrate to a specific range, coating unevenness is suppressed, and a printed material having excellent print clarity is obtained.

[0245] Furthermore, it is considered that the content of titanium oxide in the coating layer is Ag / m 2When the thickness of the coating layer is set to Bμm, A / B is greater than 0.01 and less than 2.00, so that the concentration of titanium oxide in the coating layer is controlled to be within an appropriate range. As a result, by irradiation with ultraviolet laser, the scattering of titanium oxide in the irradiated part is suppressed, and a printed material with better visibility is obtained.

[0246] In this embodiment, the printable area refers to an area (portion) where the titanium oxide contained in the coating layer changes color, preferably by irradiation of ultraviolet laser, and the titanium oxide in the portion irradiated by the ultraviolet laser changes from white to black, so that printing can be performed. The printing area refers to a portion of the printable area where the titanium oxide actually changes color, preferably by irradiation of ultraviolet laser, and the titanium oxide changes color and becomes visible, that is, the portion irradiated by the ultraviolet laser. In addition, the non-printing area refers to an area (portion) where the titanium oxide does not change color, such as an area (portion) not irradiated by the ultraviolet laser, in the printable area.

[0247] Hereinafter, the present invention will be described in further detail.

[0248] 〔Recording medium〕

[0249] The recording medium to be printed has a printable area containing titanium oxide, and at least a portion of the printable area has a printing area containing discolored titanium oxide.

[0250] The recording medium has a coating layer containing titanium oxide on a paper substrate. It should be noted that the coating layer only needs to be formed on one side of the paper substrate, or on both sides. Preferably, the recording medium has a coating layer only on one side. In addition, the coating layer may be formed on the entire surface of the recording medium, or may be formed on a portion (part) where printing is desired.

[0251] <Coating layer>

[0252] The content of titanium oxide in the coating layer constituting the printable area is 0.6 g / m 2 Above and 30g / m 2 the following.

[0253] The content of titanium oxide in the coating layer was 0.6 g / m2 from the viewpoint of obtaining a sufficient printing density. 2 Above, preferably 0.8g / m 2 More preferably 1.0 g / m 2 More preferably 1.2 g / m 2 In addition, from the viewpoint of maximizing the printing density, suppressing the cost increase caused by containing more titanium oxide than required, and suppressing printing unevenness and smoke generation, 30 g / m 2 Below, preferably 25g / m 2Below, more preferably 20g / m 2 Below, more preferably 15g / m 2 Below, more preferably 10g / m 2 the following.

[0254] It should be noted that at least the printable area of ​​the recording medium only needs to contain titanium oxide in the above-mentioned content, and there may be a portion where no coating layer is provided in the non-printed area, and there may also be a portion where the content of titanium oxide is set to less than 0.6 g / m 2 or more than 30g / m 2 From the viewpoint of manufacturing simplicity, it is preferred that the entire area of ​​the sheet medium is provided with a titanium oxide content of 0.6 g / m 2 Above and 30g / m 2 The following coating layers.

[0255] With regard to the content of titanium oxide in the coating layer (solid component), from the viewpoint of obtaining sufficient printing concentration, it is preferably 1 mass % or more, more preferably 3 mass % or more, further preferably 5 mass % or more, and further preferably 7 mass % or more. From the viewpoint of maximizing the printing concentration, suppressing the cost increase caused by containing titanium oxide more than required, and easiness of forming the coating layer, it is preferably 95 mass % or less, more preferably 85 mass % or less, further preferably 75 mass % or less, further preferably 60 mass % or less, further preferably 50 mass % or less, further preferably 40 mass % or less, and further preferably 30 mass % or less.

[0256] As for the thickness of the coating layer, from the viewpoint of obtaining sufficient printing concentration and the ease of coating, it is preferably above 0.4 μm, more preferably above 0.6 μm, and further preferably above 0.8 μm, and from the viewpoint of achieving the maximum printing concentration and the ease of forming the coating layer, it is preferably below 40.0 μm, more preferably below 30.0 μm, further preferably below 20.0 μm, further preferably below 15.0 μm, and further preferably below 10.0 μm.

[0257] The thickness of the coating layer is measured from an electron microscope (SEM) observation image of a cross section of the recording medium.

[0258] The content of titanium oxide in the coating layer is Ag / m 2 , when the thickness of the coating layer is set to Bμm, A / B is greater than 0.01, preferably greater than 0.03, more preferably greater than 0.05, and is less than 2.00, preferably less than 1.95, more preferably less than 1.80, further preferably less than 1.50, further preferably less than 1.20, further preferably less than 1.00.

[0259] By making the above-mentioned A / B in the coating layer within the above-mentioned range, the content of titanium oxide in the coating layer is made within an appropriate range, and the scattering of titanium oxide from the coating layer when irradiated with ultraviolet rays is prevented, thereby suppressing smoke generation, and further obtaining a printed matter with excellent print clarity, which is preferred.

[0260] The substrate of the recording medium is a paper substrate as described below, and the paper substrate itself may contain titanium oxide. When the paper substrate contains titanium oxide, there is a tendency to produce a clearer image.

[0261] The content of titanium oxide as a whole is 0.6 g / m 2 Above, preferably 0.8g / m 2 More preferably 1.0 g / m 2 From the viewpoint of maximizing the printing density, 35 g / m 2 Below, more preferably 30g / m 2 Below, more preferably 25g / m 2 The content of titanium oxide in the entire recording medium is the total amount of the content of titanium oxide in the substrate and the content of titanium oxide in the coating layer when the substrate contains titanium oxide.

[0262] When the substrate contains titanium oxide, the content of titanium oxide in the substrate is preferably 1 g / m 2 More preferably 2.5 g / m 2 More preferably 5g / m 2 More preferably 10g / m 2 above.

[0263] The coating layer preferably contains a thermoplastic resin in addition to titanium oxide.

[0264] (Titanium Oxide)

[0265] Titanium oxide is preferably contained in a coating liquid for the coating layer and applied, and the coating liquid is more preferably an aqueous coating liquid.

[0266] Examples of the titanium oxide contained in the coating layer include the same titanium oxide as used in the first printed material, and the preferred crystal structure and shape are also the same.

[0267] When the titanium oxide is amorphous or spherical, the particle size of the titanium oxide is preferably in the same range as that of the titanium oxide used in the first printed material from the viewpoint of obtaining a sheet medium having excellent surface smoothness.

[0268] The particle size of titanium oxide in the coating layer is calculated from an SEM image obtained by a scanning electron microscope (SEM, manufactured by Hitachi High-Technologies Corporation, S5200, etc.) of ash obtained by burning a recording medium or printed matter at 525° C. in a muffle furnace.

[0269] The sample of ash content tested in scanning electron microscope is made as follows: applied to an ultrasonic homogenizer (Yamato Scientific Co., Ltd. system, LUH150, etc.) with a power of 50W for 5 minutes, and dispersed in ethanol to obtain 0.01% by mass slurry, 0.1mL is cast into an aluminum dish, and after drying at 60°C, the aluminum dish is cut out to the appropriate size tested in SEM to make. The particles that can be clearly distinguished from the adjacent particles are selected visually, and the major diameter of one particle is used as the particle size. At this time, even if the primary particles are mixed with the secondary particles in the aggregated state and can be clearly distinguished, they are counted as one particle, and the average diameter of 100 randomly selected particles is used as the particle size. The magnification during SEM image observation can be appropriately selected according to the particle size of titanium oxide, preferably about 20,000 times. In addition, in the case of particles other than titanium oxide, the energy dispersive X-ray analyzer (manufactured by Horiba, Ltd., EMAX, etc.) attached to SEM is used to measure the particles containing titanium element.

[0270] When the substrate is a paper containing titanium oxide, the coating layer is transferred to a transparent adhesive tape (309SN manufactured by 3M Co., Ltd.) that does not contain titanium oxide or inorganic pigments to prepare an ash sample. Specifically, a pressure-bonding roller with a roller mass of 2 kg (manufactured by Yasuda Seiki Co., Ltd., No. 349, etc.) is used to adhere the adhesive tape to the upper layer of the coating layer. After that, after being immersed in a copper ethylenediamine solution (manufactured by Merck) for cellulose viscosity measurement for 24 hours, the adhesive tape containing the coating layer is thoroughly cleaned with ion exchange water. Wipe off the moisture of the obtained adhesive tape containing the coating layer and dry it in a dryer at 60°C for 1 hour. After that, it is burned in a muffle furnace at 525°C to prepare ash for particle size measurement, and the particle size is measured in the same way as above.

[0271] In addition, the average particle diameter of the titanium oxide particles used as a raw material was measured by the same method as the measurement method in the first printed material.

[0272] When the titanium oxide is needle-shaped, the preferred ranges of the major axis, minor axis, and aspect ratio (major axis / minor axis) of the titanium oxide are preferably the same ranges as those of the titanium oxide used in the first printed material.

[0273] The major and minor axes of titanium oxide contained in the coating layer can be measured by treating the ash obtained by burning the recording medium or printed matter in a muffle furnace in the same manner as described above, and measuring it based on the SEM image obtained by a scanning electron microscope (SEM, manufactured by Hitachi High-Technologies Corporation, S5200, etc.). The powder tested by the scanning electron microscope is obtained in the same manner as described above.

[0274] The major axis and minor axis of titanium oxide used as a raw material can also be measured from a SEM image obtained using a scanning electron microscope.

[0275] When the substrate is a paper containing titanium oxide, the coating layer is transferred to a transparent adhesive tape (309SN, manufactured by 3M Co., Ltd.) that does not contain titanium oxide or inorganic pigments to prepare an ash sample. Specifically, a pressure-bonding roller with a roller mass of 2 kg (manufactured by Yasuda Seiki Co., Ltd., No. 349, etc.) is used to adhere the adhesive tape to the upper layer of the coating layer. After that, after being immersed in a copper ethylenediamine solution (manufactured by Merck) for cellulose viscosity measurement for 24 hours, the adhesive tape containing the coating layer is thoroughly cleaned with ion exchange water. Wipe off the moisture of the obtained adhesive tape containing the coating layer and dry it in a dryer at 60°C for 1 hour. After that, it is burned in a muffle furnace at 525°C to prepare ash for particle size measurement, and the major and minor diameters are measured in the same way as above.

[0276] (Thermoplastic resin)

[0277] The thermoplastic resin used in the coating layer functions as a binder. The thermoplastic resin used in the coating layer is not particularly limited, but a water-dilutable thermoplastic resin is preferred from the viewpoint of being preferably applied as an aqueous coating liquid.

[0278] Examples of the water-dilutable resin include water-soluble, emulsion-type, and dispersion-type resins.

[0279] The water-dilutable thermoplastic resin may be a natural resin or a synthetic resin, for example, starch derivatives, casein, shellac, polyvinyl alcohol and its derivatives, acrylic resins, maleic acid resins, polyurethane resins, polyester resins, styrene-butadiene resins, vinyl chloride resins, and polyolefin resins.

[0280] More specifically, examples of acrylic resins include acrylic resins obtained by copolymerizing (meth)acrylic acid and its alkyl ester or styrene as monomer components, styrene-maleic acid resins, styrene-acrylic acid-maleic acid resins, water-soluble polyurethane resins, and water-soluble polyester resins.

[0281] Among these, from the viewpoint of the stability of the coating liquid and the solvent resistance of the coating layer, it is preferably selected from at least one of starch derivatives, casein, shellac, polyvinyl alcohol and its derivatives, acrylic resins, and maleic acid resins, more preferably selected from at least one of starch derivatives, polyvinyl alcohol, polyvinyl alcohol derivatives, acrylic resins, and maleic acid resins, further preferably selected from at least one of starch derivatives, polyvinyl alcohol, polyvinyl alcohol derivatives, and acrylic resins, and further preferably selected from at least one of polyvinyl alcohol, polyvinyl alcohol derivatives, and acrylic resins.

[0282] These resins may be used alone or in combination of two or more.

[0283] The content of the thermoplastic resin in the solid component of the coating liquid is preferably 5 mass % or more, more preferably 15 mass % or more, further preferably 25 mass % or more, further preferably 40 mass % or more, further preferably 45 mass % or more, and is preferably 99 mass % or less, more preferably 97 mass % or less, further preferably 95 mass % or less, further preferably 93 mass % or less.

[0284] The coating layer may contain other components in addition to the titanium oxide and the thermoplastic resin. Other components include extender pigments other than titanium oxide, film-forming agents, pigment dispersants, pigment dispersion resins, anti-blocking agents, wetting agents, viscosity modifiers, pH modifiers, defoamers, general surfactants, etc.

[0285] Examples of extender pigments other than titanium oxide include aluminum hydroxide, barium sulfate, calcium carbonate, and amorphous silica.

[0286] The coating liquid is preferably an aqueous coating liquid, and examples of the aqueous medium used include water or a mixture of water and a water-miscible solvent.

[0287] As the water-miscible solvent, lower alcohols, polyols, and their alkyl ethers or alkyl esters can be mentioned. Specifically, lower alcohols such as methanol, ethanol, n-propanol, isopropanol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, glycerol and other polyols, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monoacetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monoacetate, diethylene glycol monomethyl ether, dipropylene glycol monomethyl ether and the like can be mentioned.

[0288] The solid content concentration of the coating liquid is not particularly limited, but is preferably 5% by mass or more, more preferably 6% by mass or more, and further preferably 8% by mass or more, and is preferably 60% by mass or less, more preferably 40% by mass or less, further preferably 30% by mass or less, and further preferably 20% by mass or less, from the viewpoint of obtaining the desired coating layer thickness, making the coating liquid have a viscosity that is easy to apply, and the viewpoint of ease of drying.

[0289] Regarding the viscosity of the coating liquid, from the viewpoints of coating suitability, obtaining the desired coating layer thickness, and ease of drying, based on the measurement of Zahn Cup No. 3, it is preferably 10 seconds or more, more preferably 15 seconds or more, and further preferably 17 seconds or more, and is preferably 40 seconds or less, more preferably 30 seconds or less, and further preferably 25 seconds or less.

[0290] The coating liquid is obtained by mixing the above-mentioned various materials with an aqueous medium. It should be noted that titanium oxide, thermoplastic resin, water, and a water-miscible solvent as required, a pigment dispersant, a pigment dispersible resin, etc. may be mixed and kneaded before mixing with the aqueous medium, and water, a water-miscible solvent as required, and the remainder of a prescribed material may be further added thereto and mixed.

[0291] The coating liquid can be obtained by mixing and dispersing the above-mentioned components in a homomixer, a high-speed stirrer such as Labomix, or a disperser such as a triple roll mill or a bead mill.

[0292] The coating liquid may be applied to the substrate by any method, but not limited to, flexographic printing, inkjet printing, gravure printing, screen printing, pad printing, spraying, or the like.

[0293] <Paper base material>

[0294] In the second printed material, a paper substrate was used as the substrate.

[0295] As the raw material pulp constituting the paper base material, the same raw material pulp as that in the paper sheet medium in the first printed matter described above can be exemplified.

[0296] As for the raw material pulp, wood pulp and deinked pulp are preferred from the viewpoint of easy availability. As for the raw material pulp, chemical pulp is also preferred from the viewpoint of uniformity of texture among wood pulps, kraft pulp is more preferred, and at least one selected from kraft pulp of broadleaf trees such as eucalyptus and acacia and kraft pulp of coniferous trees such as pine and cedar is further preferred, and at least one selected from bleached kraft pulp (LBKP) of broadleaf trees and bleached kraft pulp (NBKP) of coniferous trees is further preferred.

[0297] In the second printed material, the length-weighted average fiber length of the pulp constituting the paper substrate is 0.6 mm or more, preferably 0.65 mm or more, and 3.5 mm or less, preferably 2.5 mm or less, and more preferably 1.3 mm or less, from the viewpoint of suppressing coating unevenness and improving print clarity.

[0298] If the length-weighted average fiber length of the pulp constituting the paper substrate is 3.5 mm or less, the pulps are densely entangled with each other, the pores of the paper substrate are reduced, and when a coating layer is provided, coating unevenness is suppressed, so that a printed material with excellent visibility can be obtained, which is preferred.

[0299] Furthermore, if the length-weighted average fiber length of the pulp constituting the paper base is 0.6 mm or more, the strength of the paper base is improved and paper dust is reduced, thereby preferably suppressing the falling off of the printed portion.

[0300] The length-weighted average fiber length of the pulp constituting the paper substrate was measured according to the method described in Examples.

[0301] In the second printed material, the average fiber width of the pulp constituting the paper substrate is preferably 14.0 μm or more, more preferably 15.0 μm or more, further preferably 15.5 μm or more, further preferably 16.0 μm or more, and is preferably 35.0 μm or less, more preferably 33.0 μm or less, further preferably 31.0 μm or less.

[0302] If the average fiber width of the pulp constituting the paper substrate is 35.0 μm or less, the pulps are densely entangled with each other, thereby reducing the pores of the paper substrate, and when a coating layer is provided, uneven coating is suppressed, and a printed matter with excellent visibility is obtained, which is preferred. In addition, if the average fiber width is 14.0 μm or more, the strength of the paper substrate is improved, and paper dust is reduced, so that the falling off of the printed part can also be suppressed, which is preferred.

[0303] The average fiber width of the pulp constituting the paper substrate can be measured by the method described in Examples.

[0304] In the second printed matter, the ratio of the number of fine fibers with a fiber length of less than 0.2 mm in the pulp constituting the paper substrate is preferably 4% or more, more preferably 5% or more, further preferably 6% or more, and is preferably 40% or less, more preferably 30% or less, further preferably 20% or less, and further preferably 16% or less.

[0305] If the ratio of the number of fine fibers is 40% or less, the strength of the paper substrate can be ensured, which is preferred. In addition, if the ratio of the number of fine fibers is 4% or more, the fine fibers are arranged in the form of filling the gaps between the fibers, the porosity of the paper substrate is reduced, and when a coating layer is provided, uneven coating is suppressed, which is preferred.

[0306] The ratio of the number of fine fibers having a fiber length of 0.2 mm or less in the pulp constituting the paper substrate is calculated as follows: the paper substrate is dissociated by the method described in the Examples, and the fiber length of the obtained pulp slurry is measured using a fiber length measuring device (e.g., Valmet, Model FS-5, with UHD base unit). Fibers having a fiber length of 0.2 mm or less and a fiber width of 75 μm or less are regarded as fine fibers, and the ratio of the number of fine fibers relative to the measured number of pulp is calculated.

[0307] In addition to the above-mentioned pulp, the paper base material may also contain fillers, sizing agents, drying enhancers, paper wet strength agents (e.g., polyamide polyamine epichlorohydrin), yield improvers (e.g., aluminum sulfate), filterability improvers, pH adjusters, softeners, antistatic agents, defoamers, dyes / pigments, and other known internal additives for papermaking, as needed.

[0308] Examples of the filler include kaolin, talc, titanium oxide, heavy calcium carbonate, light calcium carbonate, calcium sulfite, gypsum, calcined kaolin, white carbon, amorphous silica, delaminated kaolin, diatomaceous earth, magnesium carbonate, aluminum hydroxide, calcium hydroxide, magnesium hydroxide, and zinc hydroxide.

[0309] Examples of the sizing agent include rosin-based, alkyl ketene dimer-based, alkenyl succinic anhydride-based, styrene-acrylic, higher fatty acid-based, and petroleum resin-based sizing agents.

[0310] In papermaking of the paper substrate, a known wet papermaking machine, such as a fourdrinier papermaking machine, a gap-wire papermaking machine, a cylinder papermaking machine, a short-wire papermaking machine, etc., can be appropriately selected and used. Next, the paper layer formed by the papermaking machine is conveyed to a felt and dried in a dryer. A multi-stage drum dryer can also be used as a pre-dryer before drying in the dryer.

[0311] The paper substrate obtained as described above may be subjected to a surface treatment by calendering to achieve uniform thickness and contour. For the calendering treatment, a known calendering machine may be appropriately selected and used.

[0312] The paper substrate may be appropriately selected from conventionally known paper substrates such as liner paper, kraft paper, premium paper, and coated paper.

[0313] In the second printed matter, the basis weight of the paper substrate is preferably 30 g / m2 from the viewpoint of strength of the printed matter and suppression of printing unevenness. 2 More preferably 40g / m 2 More preferably 50g / m 2 More preferably 60g / m 2 More than, and preferably 300g / m 2 Below, more preferably 240g / m 2 Below, more preferably 180g / m 2 the following.

[0314] In the second printed matter, the thickness of the paper substrate is not particularly limited, but from the viewpoint of strength of the printed matter and suppression of printing unevenness, it is preferably 30 μm or more, more preferably 50 μm or more, further preferably 70 μm or more, further preferably 80 μm or more, and is preferably 300 μm or less, more preferably 250 μm or less, further preferably 200 μm or less, further preferably 150 μm or less.

[0315] 〔Raman intensity〕

[0316] In the second printed matter of the present invention, the printed area refers to the area (portion) containing the discolored titanium oxide in the printable area, preferably the area (portion) printed by ultraviolet laser. The non-printed area refers to the area (portion) not printed in the printable area.

[0317] The ratio of the Raman intensity of titanium oxide in the printed area to the Raman intensity of titanium oxide in the non-printed area (Raman intensity in the printed area / Raman intensity in the non-printed area) is 0.70 or less. By making the Raman intensity ratio within the above range, a printed material with excellent visibility can be obtained.

[0318] Regarding the above Raman intensity ratio (Raman intensity of the printed area / Raman intensity of the non-printed area), when rutile titanium oxide is used as titanium oxide, the Raman intensity derived from titanium oxide is 447±3 cm -1 In addition, when anatase titanium oxide is used as titanium oxide, the Raman intensity derived from titanium oxide is compared with 516±3 cm -1 The maximum Raman intensity in the wavenumber range.

[0319] In addition, when rutile titanium oxide and anatase titanium oxide coexist, the Raman intensity derived from rutile titanium oxide is used for comparison.

[0320] The printed matter of the present invention preferably has a non-printing area in white and a printing area in black.

[0321] The preferred range of brightness in the Munsell color system of the non-printed area and the printed area is the same as that of the first printed matter.

[0322] In order to obtain the color in the above-mentioned Munsell colorimetric system, it is preferred to appropriately adjust the content of titanium oxide in the coating layer, the thickness of the coating layer, and their ratio, the characteristics of the paper substrate (the length-weighted average fiber length of the pulp constituting the paper substrate), and the irradiation conditions of the ultraviolet laser (such as average power, repetition frequency, wavelength, etc.).

[0323] The second printed matter of the present invention is suitable for use in packaging, labels, adhesive tapes, and the like.

[0324] Examples of packaging bodies include inner lining paper of corrugated cardboard (especially the outermost inner lining paper), outer boxes, milk bags, liquid containers for beverages such as paper cups (preferably liquid paper containers for beverages), food trays, and skin packaging. Examples of labels include label paper, adhesive labels, and adhesive sheets. Examples of adhesive tapes include adhesive tapes and kraft paper tapes.

[0325] like Figure 5 As shown, a liquid container 10 as an example of a package has, for example, a printed area 20 on its surface. The printed area 20 is irradiated with ultraviolet laser light to print characters such as a date.

[0326] 〔Transparent resin layer〕

[0327] The second printed matter of the present invention is preferably a printing medium further including a transparent resin layer on the coating layer.

[0328] That is, it is preferable to use a printing medium in which a transparent resin layer is further provided in advance on a coating layer containing a predetermined amount or more of titanium oxide.

[0329] The inventors have found that the above-described configuration can provide a printed image with a high print density and a clearer image. The detailed reason for this is not clear, but it is partially presumed as follows.

[0330] It is believed that when titanium oxide is heated by irradiation with ultraviolet laser, the surrounding water vaporizes instantly, causing the discolored titanium oxide to separate from the coating layer. It is believed that by pre-arranging a transparent resin layer on the coating layer, the separation of the discolored titanium oxide is suppressed, and the printing density becomes higher. It is further believed that smoke is generated due to the vaporization of the above-mentioned water and the separation of titanium oxide and paper dust, but the amount of this smoke is also suppressed.

[0331] When the coating layer and the substrate as the lower layer contain moisture, it is particularly preferred to have a transparent resin layer in view of the high effect of providing a transparent resin layer. When the substrate is a paper substrate as in the present embodiment, it is particularly preferred to have a transparent resin layer.

[0332] The preferred range of the total light transmittance of the transparent resin layer is the same as the preferred range of the transparent resin layer in the first printed material, and the measuring method is also the same.

[0333] The resin constituting the transparent resin layer, the lamination method, and the thickness are the same as those of the transparent resin layer in the first printed material, and the preferred ranges are also the same.

[0334] [Method for producing the second printed matter]

[0335] The second method for producing a printed article of the present invention comprises the steps of: irradiating a recording medium with ultraviolet rays to discolor an irradiated area, thereby performing printing, wherein the printable area of ​​the recording medium has a coating layer containing titanium oxide on a paper substrate, the length-weighted average fiber length of the pulp constituting the paper substrate is 0.6 mm or more and 3.5 mm or less, and the content of titanium oxide in the coating layer is 0.6 g / m 2 Above and 30g / m 2 Hereinafter, the content of titanium oxide in the coating layer is denoted as Ag / m 2 When the thickness of the coating layer is B μm, A / B is greater than or equal to 0.01 and less than or equal to 2.00.

[0336] As the recording medium used in the method for producing the second printed matter of the present invention, the same recording medium as the recording medium in the second printed matter can be exemplified, and the preferred range is also the same. In the method for producing the second printed matter of the present invention, as long as the titanium oxide content of the coating layer in at least the ultraviolet laser irradiation area is 0.6 g / m 2 Above and 30g / mm 2 The titanium oxide content in the non-irradiated region is not particularly limited, but the titanium oxide is preferably contained in the entire coating layer.

[0337] The ultraviolet laser irradiation is preferably performed so that the ratio of the Raman intensity derived from titanium oxide in the printed area to the Raman intensity derived from titanium oxide in the non-printed area becomes 0.70 or less.

[0338] The Raman intensities of the printed area and the non-printed area are as described above in the second print.

[0339] [Ultraviolet laser irradiation conditions]

[0340] The irradiation conditions of the ultraviolet laser (wavelength, average power, repetition frequency, spot diameter, scanning speed, and line pitch of the ultraviolet laser) are the same as those in the method for producing the first printed matter, and the preferred ranges are also the same.

[0341] [Method for producing the second printed matter]

[0342] The method for producing the second printed matter of the present invention can be performed in various ways.

[0343] Various embodiments to which the second printed matter manufacturing method of the present invention can be applied are exemplified below, but the second printed matter manufacturing method of the present invention is not limited to the embodiments described below. The printed information is not particularly limited, but is preferably variable information.

[0344] The method for producing the second printed matter of the present invention is preferably performed online.

[0345] (1) Direct printing on packaging

[0346] A first embodiment of the second printed matter manufacturing method of the present invention is a method for printing information on a package having a coating layer containing titanium oxide, comprising the steps of directly printing on a package moving or intermittently stopped on a packaging production line under ultraviolet laser.

[0347] The first method for producing printed matter is to prepare a package by using a recording medium, and directly print it with an ultraviolet laser. The recording medium has a coating layer containing titanium oxide on a paper substrate, and the coating layer contains 0.6 g / m 2 Above and 30g / m 2 The ratio of the content of titanium oxide to the thickness of the coating layer is 0.01 to 2.00, and the length-weighted average fiber length of the pulp constituting the paper substrate is 0.6 mm to 3.5 mm. It should be noted that at least the outermost layer of the printed area of ​​the package body is made of the above-mentioned recording medium.

[0348] In addition, as the packaging body, corrugated cardboard, boxes, etc. can be exemplified, and it is preferable to directly print the side surface or the upper surface of the packaging body with an ultraviolet laser.

[0349] In addition, the packaging line may have a coating (applying) mechanism. Examples of the coating mechanism include a contact printer, a letterpress printer, and a spray coater.

[0350] This method includes the following steps: a step of applying a coating layer by a coating mechanism while the package is moving on the packaging line; and a step of directly printing the package with an ultraviolet laser while the package is moving on the packaging line or while it is stopped intermittently.

[0351] (2) Printing of labels

[0352] The second embodiment of the method for producing the second printed article of the present invention is a method for printing information on a label having a coating layer containing titanium oxide. The coating layer of the recording medium constituting the printing surface of the label contains 0.6 g / m 2 Above and 30g / m 2In addition, the label has a coating layer on a paper substrate, the length-weighted average fiber length of the pulp constituting the paper substrate is 0.6 mm or more and 3.5 mm or less, and the content of titanium oxide in the coating layer is Ag / m 2 When the thickness of the coating layer is B μm, A / B is greater than or equal to 0.01 and less than or equal to 2.00.

[0353] The printed label is preferably affixed to the package using a label affixing device. Various label affixing devices have been proposed as label affixing devices. It should be noted that, in this case, a coating layer is provided on the surface to be irradiated with ultraviolet rays.

[0354] As the first label sticking device, an adhesive is applied to the label base paper wound into a roll and then affixed to an article. More specifically, the following roll labeling machine can be exemplified, which comprises: a cutting unit that cuts each sheet of the label base paper wound into a roll into a predetermined length; an adhesive conveying unit that receives the label base paper cut by the cutting unit by a label base paper holder coated with an adhesive, and makes the adhesive adhere to the back of the label base paper; and an attaching unit that receives the label base paper (label) to which the adhesive is applied by the adhesive conveying unit and affixes it to an article such as a container, wherein a rotating conveying unit having a label holding surface on the outer surface is provided between the cutting unit and the adhesive conveying unit, and an example of which can be given is Japanese Patent Publication No. 6-64637.

[0355] In addition, there can be exemplified a roller labeling machine having a cutting unit for cutting each label base paper wound into a roll into a predetermined length, a delivery roller for delivering to a pasting roller, and an adhesive roller for applying glue to the label base paper held by the pasting roller; a method without the aforementioned delivery roller.

[0356] The ultraviolet laser irradiation is preferably performed before the label base paper wound into a roll is cut into a predetermined length, or after being cut and before being handed over to the next roll, etc. According to the method of the roll labeling machine, the surface or back side of the label base paper wound into a roll becomes the surface or back side when attached to the package body, and therefore, the ultraviolet laser irradiation is performed accordingly.

[0357] The second label sticking device uses an adhesive label roll as a label. In this case, at least the surface opposite to the surface to which the adhesive is applied and to which the ultraviolet laser is irradiated has a coating layer.

[0358] When using an adhesive label roll with release paper, for example, the following adhesion device can be exemplified, which has: a release paper separation unit for separating the adhesive label from the release paper; a handover roller for receiving the adhesive label separated from the release paper; and an adhesive roller for sucking the adhesive label by the handover roller and sticking it to the article (package). Preferably, the irradiation based on ultraviolet laser is performed before separating the release paper, or after the release paper is separated and before being loaded on the adhesive roller.

[0359] In addition, the following apparatus can be exemplified: an apparatus having a mechanism for attaching an adhesive label roll with a release paper, separating the adhesive label from the release paper, having a mechanism for attaching the label immediately after the detachment, and an apparatus for printing by ultraviolet laser until the attached adhesive label roll is separated from the release paper. The above-mentioned adhesive label attaching method is also called one-way attaching.

[0360] Furthermore, the following label sticking device can be exemplified: it has a mechanism for installing an adhesive label roll with release paper, separating the release paper from the adhesive label, and has a mechanism for sticking the adhesive label to an article (package), and the aforementioned sticking mechanism is a syringe method, an air jet method, or a robot arm method. The irradiation based on ultraviolet laser is preferably performed until the adhesive label roll with release paper after installation is separated from the release paper.

[0361] As labels, linerless adhesive labels may also be used. Linerless adhesive labels are labels without release paper, and compared with the case of using an adhesive label roll with release paper, they have the following characteristics: one roll has more labels, there is no release paper, and therefore it is cheap. When using linerless adhesive labels, a coating layer is formed on the surface opposite to the surface to which the adhesive is applied and irradiated with ultraviolet laser.

[0362] As a label sticking device using a linerless adhesive label, the following device can be exemplified: a device having a mechanism for installing a linerless label roll, a cutting mechanism for cutting each linerless label one by one, and a sticking mechanism for sticking the cut linerless label to an article (package), wherein the sticking mechanism is a barrel type or a robot arm type. Printing based on irradiation of ultraviolet laser is preferably performed between the mechanism for installing the linerless label roll and the cutting mechanism, or during the period when the cut linerless label is transported to the sticking mechanism.

[0363] For the third label attachment device, a 0.6 g / m 2 Above and 30g / m 2 The following printing medium with a titanium oxide coating layer was attached to an article (package) and then printed under ultraviolet laser.

[0364] As a method of attaching the label, refer to the above-mentioned first device and second device.

[0365] (3) Printing on adhesive tape

[0366] The third embodiment of the method for producing the second printed matter of the present invention is an embodiment in which the recording medium is an adhesive tape. In this case, a coating layer is provided on the opposite side of the surface to which the adhesive is applied.

[0367] That is, the method for producing printed matter of the third embodiment comprises the steps of affixing the adhesive tape made of the recording medium to an article (package), and printing with an ultraviolet laser before or after the affixing step.

[0368] Alternatively, a printing device in which a printing device based on ultraviolet laser is installed in a corrugated cardboard wrapping machine may be used. Specifically, the printing device has a mechanism for installing a tape winding device, a conveyor for conveying corrugated cardboard, a mechanism for folding a baffle of the corrugated cardboard, a mechanism for attaching the tape to wrap the corrugated cardboard, and a mechanism for printing on the tape under ultraviolet laser during or after attaching the tape.

[0369] The second printed article and the method for producing the second printed article of the present invention are not limited to the above-described embodiment, and can be used for various applications requiring printing.

[0370] [Second Laser Printing Printing Medium]

[0371] The second laser printing medium of the present invention has a printable area that can be printed using ultraviolet laser, the printable area of ​​the printing medium has a coating layer containing titanium oxide on a substrate, the length-weighted average fiber length of the pulp constituting the paper substrate is 0.6 mm or more and 3.5 mm or less, and the content of titanium oxide in the coating layer is 0.6 g / m 2 Above and 30g / m 2 Hereinafter, the content of titanium oxide in the coating layer is denoted as Ag / m 2 When the thickness of the coating layer is B μm, A / B is 0.01 or more and 2.00 or less. The second laser-printable printing medium of the present invention can be printed by irradiating it with ultraviolet laser light.

[0372] Preferred embodiments of the second laser printable printing medium are the same as preferred embodiments of the recording medium of the second printed matter, and preferred embodiments of the printing method for the second laser printable printing medium are the same as the method for producing the second printed matter.

[0373] [Third Printing]

[0374] The third printed matter of the present invention (hereinafter, simply referred to as the "third printed matter") has a printed area containing discolored titanium oxide on at least a portion of a sheet medium, the sheet medium having a printable area containing titanium oxide, the printable area of ​​the sheet medium containing a laminated layer of titanium oxide on a paper substrate, and the content of titanium oxide in the laminated layer is 0.1 g / m 2The above-mentioned content of titanium oxide in the aforementioned laminated layer is greater than 1 mass % and less than 45 mass %, the thickness of the aforementioned laminated layer is greater than 10 μm and less than 200 μm, and the ratio of the Raman intensity of titanium oxide originating from the printed area to the Raman intensity of titanium oxide originating from the non-printed area is less than 0.70.

[0375] According to the present invention, a printed article having a printed area containing discolored titanium oxide can be provided. In addition, the printed article of the present invention has excellent clarity of printing and excellent solvent resistance.

[0376] The detailed reasons for obtaining the above effects are not clear, but part of them are considered as follows. It is considered that in the present invention, the titanium oxide content on the paper substrate is 0.1 g / m 2 The above laminated layer serves as a sheet medium for a printable area. The print area contains discolored titanium oxide, and the ratio of the Raman intensity of the titanium oxide in the print area to the Raman intensity of the titanium oxide in the non-printing area is made to be 0.70 or less, thereby obtaining a print with excellent visibility. For the discoloration of the aforementioned titanium oxide, it is believed that the ionic valence of the titanium oxide contained in the laminated layer changes from 4 valences to 3 valences, resulting in oxygen deficiency, thereby changing from white to black, thereby becoming visible. Furthermore, the aforementioned change in ionic valence can be detected as a change in Raman intensity, and a print area with high visibility is obtained by making the ratio of the Raman intensity of the titanium oxide in the print area to the Raman intensity of the titanium oxide in the non-printing area below a specific value. It is believed that the ionic valence of titanium oxide changes when irradiated with light energy equivalent to the band gap of titanium oxide. The band gap of titanium oxide varies depending on the crystal system, and is generally around 3.0 to 3.2 eV, and the wavelength of light corresponding to it is below 420 nm. Therefore, even if a laser beam having a wavelength exceeding 420 nm (eg, 532 nm, 1064 nm, or 10600 nm) is used, it is difficult to perform printing due to the change in ion valence of titanium oxide as in the present invention.

[0377] In addition, it is considered that the laminate layer develops color due to titanium oxide contained in the laminate layer, and therefore has excellent solvent resistance.

[0378] It should be noted that the color change of titanium oxide is preferably performed by irradiation with ultraviolet laser. At this time, smoke may be generated by irradiation with ultraviolet laser. It is believed that when titanium oxide is heated by irradiation with ultraviolet laser, the surrounding moisture is instantly vaporized, so that the discolored titanium oxide and the resin of the laminated layer are separated from the sheet medium, and smoke is believed to be generated along with this separation. It is believed that in this embodiment, the above-mentioned smoke is suppressed by making the content of titanium oxide in the laminated layer within a specific range.

[0379] Furthermore, when a laminate layer is provided on a paper substrate and a printed matter is produced by irradiation with an ultraviolet laser, the obtained printed matter has a problem of reduced tensile strength and elongation at break. This is believed to be due to the degradation of the resin of the laminate layer and the paper substrate by irradiation with an ultraviolet laser. It is believed that by setting the thickness of the laminate layer within a specific range, the reduction in tensile strength and elongation at break of the printed matter can be suppressed.

[0380] In this embodiment, the printable area refers to the area (portion) where the titanium oxide contained in the laminate layer changes color, preferably the titanium oxide in the portion irradiated by the ultraviolet laser changes from white to black, thereby enabling printing. The printing area refers to the portion of the printable area where the titanium oxide actually changes color, preferably the portion that changes color by irradiation with the ultraviolet laser, i.e., the portion irradiated with the ultraviolet laser. In addition, the non-printing area refers to the area (portion) where the titanium oxide does not change color, such as the area (portion) that is not irradiated with the ultraviolet laser, in the printable area.

[0381] Hereinafter, the present invention will be described in further detail.

[0382] 〔Sheet Media〕

[0383] In the third printed material, the sheet medium to be printed has a printable region containing titanium oxide, and at least a portion of the printable region has a print region containing discolored titanium oxide.

[0384] The sheet medium has a laminate layer containing titanium oxide on a paper substrate. The laminate layer only needs to be formed on at least one side of the paper substrate, and may be formed on both sides, but the sheet medium preferably has the laminate layer on only one side.

[0385] <Lamination layer>

[0386] For the laminate layer as the printable area, the content of titanium oxide was 0.1 g / m 2 In the above, the content of titanium oxide in the laminate layer is 1 mass % or more and 45 mass % or less, and the thickness of the laminate layer is 10 μm or more and 200 μm or less.

[0387] The content of titanium oxide in the laminate layer was 0.1 g / m2 from the viewpoint of obtaining a sufficient printing density. 2 Above, preferably 0.2g / m 2 More preferably 0.3 g / m 2 More preferably 0.5 g / m 2 More preferably 1.0 g / m 2 More preferably 1.2 g / m 2From the viewpoint of maximizing the printing density and suppressing the cost increase caused by containing more than the required amount of titanium oxide, 200 g / m2 is preferred. 2 Below, more preferably 120g / m 2 Below, more preferably 50g / m 2 Below, more preferably 30g / m 2 Below, more preferably 20g / m 2 the following.

[0388] It should be noted that as long as at least the printable area of ​​the sheet medium contains titanium oxide in the above content, there may be a portion without a laminate layer in the non-printed area, and there may be a portion with a titanium oxide content of less than 0.1 g / m 2 From the viewpoint of ease of manufacture, it is preferred that the content of titanium oxide on the paper substrate be 0.1 g / m 2 The above laminated layers.

[0389] The content of titanium oxide in the laminated layer is 1.0 mass % or more, preferably 1.5 mass % or more, more preferably 2.0 mass % or more, further preferably 4.0 mass % or more, and 45 mass % or less, preferably 35 mass % or less, and further preferably 30 mass % or less, from the viewpoints of obtaining sufficient printing density, maximizing printing density, suppressing cost increase caused by containing more titanium oxide than required, making the concentration of titanium oxide in the laminated layer within an appropriate range to suppress scattering of titanium oxide when irradiated with ultraviolet laser, and suppressing smoke generation.

[0390] The thickness of the lamination layer is not less than 10 μm, preferably not less than 12 μm, and more preferably not less than 20 μm, from the viewpoint of obtaining sufficient printing concentration, ease of lamination, and suppressing the reduction of tensile strength and elongation at break due to ultraviolet laser irradiation. Moreover, from the viewpoint of maximizing the printing concentration and suppressing the overall thickness of the sheet medium and obtaining a printed material with flexibility, it is not more than 200 μm, preferably not more than 150 μm, more preferably not more than 100 μm, and further preferably not more than 50 μm.

[0391] The thickness of the laminate layer was measured from an electron microscope (SEM) observation image of a cross section of the sheet medium.

[0392] The laminate layer is preferably formed of a film of a thermoplastic resin containing titanium oxide.

[0393] (Titanium Oxide)

[0394] Titanium oxide is preferably encapsulated in a thin film of a thermoplastic resin, and the laminate layer is more preferably obtained by adding titanium oxide to a laminate layer raw material and forming the resultant into a thin film.

[0395] Examples of the titanium oxide contained in the laminate layer include the same ones as those used in the first printed material, and the preferred crystal structure and shape are also the same.

[0396] From the viewpoint of obtaining a sheet medium having excellent surface smoothness, the particle size of titanium oxide when the titanium oxide is amorphous or spherical is preferably within the same range as that of the titanium oxide used in the first printed material.

[0397] The particle size of titanium oxide contained in the laminate layer can also be calculated by burning the laminate layer in a muffle furnace and obtaining an SEM image of the obtained ash using a scanning electron microscope (SEM, manufactured by Hitachi High-Technologies Corporation, SU3800, etc.).

[0398] The particle size of titanium oxide in the laminate layer is calculated from an SEM image obtained by a scanning electron microscope (SEM, manufactured by Hitachi High-Technologies Corporation, S5200, etc.) of ash obtained by burning a sheet medium or a printed matter in a muffle furnace.

[0399] For the sample of ash content tested in scanning electron microscope, it is applied to an ultrasonic homogenizer (Yamato Scientific Co., Ltd. system, LUH150, etc.) with a power of 50W for 5 minutes, and dispersed in ethanol to obtain 0.01 mass % slurry, 0.1mL is cast into an aluminum dish, dried at 60 ° C, and can be made. Visually select those that can be clearly distinguished from adjacent particles, and the major diameter of one particle is used as the particle diameter. At this time, even if the primary particles are mixed with the secondary particles in the aggregated state and can be clearly distinguished, they are counted as one particle respectively, and the average diameter of 100 randomly selected particles is used as the particle diameter. The magnification during SEM image observation can be appropriately selected according to the particle diameter of titanium oxide, preferably about 20,000 times.

[0400] In addition, the average particle diameter of the titanium oxide particles used as a raw material can be measured by the same method as the measurement method in the first printed material.

[0401] When the titanium oxide is needle-shaped, the preferred ranges of the major axis, minor axis, and aspect ratio (major axis / minor axis) of the titanium oxide are preferably the same ranges as those of the titanium oxide used in the first printed material.

[0402] The major and minor axes of titanium oxide contained in the laminated layer can be measured by treating the ash obtained by burning the laminated layer in a muffle furnace in the same manner as described above and measuring it based on an SEM image obtained by a scanning electron microscope (SEM, manufactured by Hitachi High-Technologies Corporation, S5200, etc.). The powder tested by the scanning electron microscope is obtained by the same method as described above.

[0403] The major axis and minor axis of titanium oxide used as a raw material can also be measured from a SEM image obtained using a scanning electron microscope.

[0404] (Thermoplastic resin)

[0405] The thermoplastic resin used in the laminating layer is not particularly limited as long as it can encapsulate titanium oxide and can be laminated on a paper substrate, and can be appropriately selected from known thermoplastic resins.

[0406] Specifically, polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polylactic acid, and polybutylene succinate; polyolefin resins such as polyvinyl chloride, polyvinylidene chloride, polybutene, polybutadiene, ethylene-vinyl acetate copolymers, polyethylene, polypropylene, ethylene-propylene copolymers, and polymethylpentene; polycarbonate; polyurethane; polyamide; polyacrylonitrile; poly(meth)acrylate, etc. are exemplified. Among these, polyolefins such as polyethylene, polypropylene, and ethylene-propylene copolymers; polyesters such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polylactic acid, and polybutylene succinate are preferred; polyethylene, polypropylene, polyethylene terephthalate, polylactic acid, and polybutylene succinate are more preferred; polyethylene and polypropylene are further preferred; and polyethylene is further preferred.

[0407] These resins may be used alone or in combination of two or more.

[0408] The laminate layer can be produced by appropriately selecting from conventionally known production methods, for example, a method appropriately selected from melt extrusion, melt casting, calendaring, and the like.

[0409] The thin film can be prepared by mixing titanium oxide with the above-mentioned resin so that the content of titanium oxide in the printed area of ​​the laminate layer is within the above-mentioned range.

[0410] <Paper base material>

[0411] In the third printed matter, the sheet medium has the above-mentioned laminate layer on the paper base material.

[0412] As the raw material pulp constituting the paper base material, the same raw material pulp as that in the paper sheet medium in the first printed matter described above can be exemplified.

[0413] As for the raw material pulp, wood pulp and deinked pulp are preferred from the viewpoint of easy availability. Also, as for the raw material pulp, among wood pulps, chemical pulp is preferred from the viewpoint of uniformity of texture, kraft pulp is more preferred, and at least one selected from kraft pulp of broadleaf trees such as eucalyptus and acacia and kraft pulp of coniferous trees such as pine and cedar is further preferred, and at least one selected from bleached kraft pulp (LBKP) of broadleaf trees and bleached kraft pulp (NBKP) of coniferous trees is further preferred.

[0414] In the third printed matter, in addition to the above-mentioned pulp, the paper base material may contain fillers, sizing agents, drying enhancers, paper wet strength agents (such as polyamide polyamine epichlorohydrin), yield improvers (such as aluminum sulfate), filterability improvers, pH adjusters, softeners, antistatic agents, defoamers, dyes / pigments, and other known internal additives for papermaking, as needed.

[0415] Examples of the filler include kaolin, talc, titanium oxide, heavy calcium carbonate, light calcium carbonate, calcium sulfite, gypsum, calcined kaolin, white carbon, amorphous silica, delaminated kaolin, diatomaceous earth, magnesium carbonate, aluminum hydroxide, calcium hydroxide, magnesium hydroxide, and zinc hydroxide.

[0416] Examples of the sizing agent include rosin-based, alkyl ketene dimer-based, alkenyl succinic anhydride-based, styrene-acrylic, higher fatty acid-based, and petroleum resin-based sizing agents.

[0417] In the third printed matter, in the papermaking of the paper substrate, a known wet papermaking machine, such as a fourdrinier papermaking machine, a gap-type papermaking machine, a cylinder-type papermaking machine, a short-net papermaking machine, etc., can be appropriately selected and used. Next, the paper layer formed by the papermaking machine is conveyed to a felt and dried in a dryer. A multi-stage drum dryer can be used as a pre-dryer before drying in the dryer.

[0418] The paper substrate obtained as described above may be subjected to a surface treatment by calendering to achieve uniform thickness and contour. For the calendering treatment, a known calendering machine may be appropriately selected and used.

[0419] The paper substrate may be appropriately selected from conventionally known paper substrates such as liner paper, kraft paper, premium paper, and coated paper.

[0420] <Lamination>

[0421] The method of laminating the laminating layer to the paper substrate is not particularly limited and can be appropriately selected from known methods. Specifically, the paper substrate and the laminating layer can be laminated by heat lamination, dry lamination, wet lamination, extrusion lamination, etc. In addition, the laminating layer and the paper substrate can be attached by means of an adhesive layer. Among these, extrusion lamination is preferred from the viewpoint of not requiring a process of attaching the laminating layer to the paper substrate and a manufacturing process.

[0422] 〔Raman intensity〕

[0423] In the third printed matter of the present invention, the printed area refers to the area (portion) containing the discolored titanium oxide in the printable area, preferably the area (portion) printed by ultraviolet laser. The non-printed area refers to the area (portion) not printed in the printable area.

[0424] The ratio of the Raman intensity of titanium oxide in the printed area to the Raman intensity of titanium oxide in the non-printed area (Raman intensity in the printed area / Raman intensity in the non-printed area) is 0.70 or less. By making the Raman intensity ratio within the above range, a printed material with excellent visibility can be obtained.

[0425] Regarding the above Raman intensity ratio (Raman intensity of the printed area / Raman intensity of the non-printed area), when rutile titanium oxide is used as titanium oxide, the Raman intensity derived from titanium oxide is 447±3 cm -1 In addition, when anatase titanium oxide is used as titanium oxide, the Raman intensity derived from titanium oxide is compared with 516±3 cm -1 The maximum Raman intensity in the wavenumber range.

[0426] In addition, when rutile titanium oxide and anatase titanium oxide coexist, the Raman intensity derived from rutile titanium oxide is used for comparison.

[0427] The printed matter of the present invention preferably has a non-printing area in white and a printing area in black.

[0428] The preferred range of brightness in the Munsell color system of the non-printed area and the printed area is the same as that of the first printed matter.

[0429] In order to obtain the color in the above-mentioned Munsell color system, it is preferred to appropriately adjust the content of titanium oxide in the laminate layer, the thickness of the laminate layer, and the irradiation conditions of the ultraviolet laser (such as average power, repetition frequency, wavelength, etc.).

[0430] The third printed matter of the present invention is suitable for use in packaging, labels, adhesive tapes, and the like.

[0431] Examples of packaging bodies include inner lining paper of corrugated cardboard (especially the outermost inner lining paper), outer boxes, milk bags, liquid containers for beverages such as paper cups (preferably liquid paper containers for beverages), food trays, and skin packaging. Examples of labels include label paper, adhesive labels, and adhesive sheets. Examples of adhesive tapes include adhesive tapes and kraft paper tapes.

[0432] like Figure 5 As shown, a liquid container 10 as an example of a package has, for example, a printed area 20 on its surface. The printed area 20 is irradiated with ultraviolet laser light to print characters such as a date.

[0433] [Third method for producing printed matter]

[0434] The third method for producing a printed article of the present invention comprises the steps of irradiating a printable area of ​​a sheet medium with an ultraviolet laser to change the color of the irradiated area, thereby printing, wherein the printable area of ​​the sheet medium has a laminate layer containing titanium oxide on a paper substrate, and the content of titanium oxide in the laminate layer is 0.1 g / m 2 In the above, the content of titanium oxide in the laminate layer is 1 mass % or more and 45 mass % or less, and the thickness of the laminate layer is 10 μm or more and 200 μm or less.

[0435] As the sheet medium used in the method for producing the third printed article of the present invention, the same sheet medium as that in the third printed article can be exemplified, and the preferred range is the same. In the method for producing the third printed article of the present invention, as long as the titanium oxide content of the laminate layer in at least the ultraviolet laser irradiation area is 0.1 g / m 2 The titanium oxide content in the non-irradiated area is not particularly limited. Preferably, the titanium oxide is encapsulated in the entire laminate layer. In addition, the laminate layer is preferably formed on at least one side of the sheet substrate. Therefore, in the non-irradiated area, the titanium oxide content in the laminate layer is preferably 0.1 g / m 2 above.

[0436] The ultraviolet laser irradiation is preferably performed so that the ratio of the Raman intensity derived from titanium oxide in the printed area to the Raman intensity derived from titanium oxide in the non-printed area becomes 0.70 or less.

[0437] The Raman intensities of the printed area and the non-printed area are as described above in the third print.

[0438] [Ultraviolet laser irradiation conditions]

[0439] The irradiation conditions of the ultraviolet laser (wavelength, average power, repetition frequency, spot diameter, scanning speed, and line pitch of the ultraviolet laser) are the same as those in the method for producing the first printed matter, and the preferred ranges are also the same.

[0440] [Third method for producing printed matter]

[0441] The third method for producing a printed matter of the present invention can be performed in various ways.

[0442] Various embodiments of the method for producing a third printed material of the present invention are exemplified below, but the method for producing a printed material of the present invention is not limited to the embodiments described below. The information to be printed is not particularly limited, but variable information is preferred.

[0443] The method for producing a printed matter of the present invention is preferably performed in-line.

[0444] (1) Direct printing on packaging

[0445] A first embodiment of the third method for producing a printed article of the present invention is a method for printing information on a package having a laminate layer containing titanium oxide, comprising the step of directly printing on a package moving or intermittently stopped on a packaging line under ultraviolet laser.

[0446] In the method for producing a printed article according to the first embodiment, a package is prepared by using a sheet medium, and direct printing is performed using an ultraviolet laser. The laminate layer of the sheet medium contains 0.1 g / m 2 of titanium oxide. 2 In the above, the content of titanium oxide in the laminate layer is 1 mass % or more and 45 mass % or less, and the thickness of the laminate layer is 10 μm or more and 200 μm or less. It should be noted that at least the outermost layer of the package body is made of the sheet medium.

[0447] In addition, as the packaging body, corrugated cardboard, boxes, etc. can be exemplified, and it is preferable to directly print the side surface or the upper surface of the packaging body with an ultraviolet laser.

[0448] (2) Printing of labels

[0449] The second embodiment of the method for producing the third printed article of the present invention is a method for printing information on a label having a laminate layer containing titanium oxide. The laminate layer of the sheet medium constituting the printing surface of the label contains 0.1 g / m 2 In the above, the content of titanium oxide in the laminate layer is 1 mass % or more and 45 mass % or less, and the thickness of the laminate layer is 10 μm or more and 200 μm or less.

[0450] The printed label is preferably affixed to the package body using a label affixing device. Various label affixing devices have been proposed as label affixing devices. It should be noted that, in this case, a laminate layer is provided on the surface to be irradiated with ultraviolet rays.

[0451] As the first label sticking device, an adhesive is applied to the label base paper wound into a roll and then affixed to an article. More specifically, the following roll labeling machine can be exemplified, which comprises: a cutting unit that cuts each sheet of the label base paper wound into a roll into a predetermined length; an adhesive conveying unit that receives the label base paper cut by the cutting unit by a label base paper holder coated with an adhesive, and makes the adhesive adhere to the back of the label base paper; and an attaching unit that receives the label base paper (label) to which the adhesive is applied by the adhesive conveying unit and affixes it to an article such as a container, wherein a rotating conveying unit having a label holding surface on the outer surface is provided between the cutting unit and the adhesive conveying unit, and an example of which can be given is Japanese Patent Publication No. 6-64637.

[0452] In addition, there can be exemplified a roller labeling machine having a cutting unit for cutting each sheet of label paper wound into a roll into a specified length, a delivery roller for delivering to a pasting roller, and an adhesive roller for applying glue to the label paper held by the pasting roller; a method without the aforementioned delivery roller.

[0453] The ultraviolet laser irradiation is preferably performed before the label base paper wound into a roll is cut into a predetermined length, or after being cut and before being handed over to the next roll, etc. According to the method of the roll labeling machine, the surface or back side of the label base paper wound into a roll becomes the surface or back side when attached to the package body, and therefore, the ultraviolet laser irradiation is performed accordingly.

[0454] The second label sticking device uses an adhesive label roll as a label. In this case, at least the surface opposite to the surface to which the adhesive is applied and to which the ultraviolet laser is irradiated has a lamination layer.

[0455] When using an adhesive label roll with release paper, for example, the following adhesion device can be exemplified, which has: a release paper separation unit for separating the adhesive label from the release paper; a handover roller for receiving the adhesive label separated from the release paper; and an adhesion roller for sucking the adhesive label by the handover roller and affixing it to an article (package). Preferably, the irradiation based on ultraviolet laser is performed before separating the release paper, or after the release paper is separated and before being loaded on the adhesion roller.

[0456] In addition, the following apparatus can be exemplified: an apparatus having a mechanism for attaching an adhesive label roll with a release paper, separating the adhesive label from the release paper, having a mechanism for attaching the label immediately after the detachment, and an apparatus for printing by ultraviolet laser until the attached adhesive label roll is separated from the release paper. The above-mentioned adhesive label attaching method is also called one-way attaching.

[0457] Furthermore, the following label sticking device can be exemplified: it has a mechanism for installing an adhesive label roll with release paper, separating the release paper from the adhesive label, and has a mechanism for sticking the adhesive label to an article (package), and the aforementioned sticking mechanism is a syringe method, an air jet method, or a robot arm method. The irradiation based on ultraviolet laser is preferably performed until the adhesive label roll with release paper after installation is separated from the release paper.

[0458] As labels, linerless adhesive labels may also be used. Linerless adhesive labels are labels without release paper, and compared with the case of using an adhesive label roll with release paper, they have the following characteristics: one roll has more labels and there is no release paper, so they are cheap. When using linerless adhesive labels, a laminate layer is formed on the surface opposite to the surface provided with adhesive and irradiated with ultraviolet laser.

[0459] As a label sticking device using a linerless adhesive label, the following device can be exemplified: a device having a mechanism for installing a linerless label roll, a cutting mechanism for cutting each linerless label one by one, and a sticking mechanism for sticking the cut linerless label to an article (package), wherein the sticking mechanism is a barrel type or a robot arm type. Printing based on irradiation of ultraviolet laser is preferably performed between the mechanism for installing the linerless label roll and the cutting mechanism, or during the period when the cut linerless label is transported to the sticking mechanism.

[0460] For the third label attaching device, a label having a titanium oxide content of 0.1 g / m 2 The sheet medium of the above-mentioned laminated layer is attached to an article (package) and then printed under ultraviolet laser.

[0461] As a method of attaching the label, refer to the above-mentioned first device and second device.

[0462] (3) Printing on adhesive tape

[0463] The third embodiment of the method for producing the third printed matter of the present invention is an embodiment in which the sheet medium is an adhesive tape. In this case, a laminate layer is provided on the surface opposite to the surface to which the adhesive is applied.

[0464] That is, the method for producing printed matter of the third embodiment includes the steps of affixing the adhesive tape made of the sheet medium to an article (package), and printing with ultraviolet laser before or after the affixing step.

[0465] Alternatively, a printing device in which a printing device based on ultraviolet laser is installed in a corrugated cardboard wrapping machine may be used. Specifically, the printing device has a mechanism for installing a tape winding device, a conveyor for conveying corrugated cardboard, a mechanism for folding a baffle of the corrugated cardboard, a mechanism for attaching the tape to wrap the corrugated cardboard, and a mechanism for printing on the tape under ultraviolet laser during or after attaching the tape.

[0466] The printed matter and the method for producing the printed matter of the present invention are not limited to the above-mentioned embodiments, and can be used for various applications requiring printing.

[0467] [Third Laser Printing Printing Medium]

[0468] The third laser printing medium of the present invention is a laser printing medium comprising a sheet medium having a printable area that can be printed using an ultraviolet laser, wherein the printable area of ​​the sheet medium has a laminate layer containing titanium oxide on a paper substrate, and the content of titanium oxide in the laminate layer is 0.1 g / m 2 The content of titanium oxide in the laminate layer is 1 mass % to 45 mass %, and the thickness of the laminate layer is 10 μm to 200 μm. The third laser-markable printing medium of the present invention can be printed by irradiating it with ultraviolet laser.

[0469] A preferred embodiment of the third laser printable print medium is the same as a preferred embodiment of the sheet medium in the third printed matter, and a preferred embodiment of the printing method for the laser printable print medium is the same as the manufacturing method of the third printed matter.

[0470] Example

[0471] The following examples and comparative examples are given to further specifically describe the features of the present invention. The materials, dosages, ratios, processing contents, processing steps, etc. shown in the following examples may be appropriately changed without departing from the gist of the present invention. Therefore, the scope of the present invention should not be limited to the specific examples shown below.

[0472] Embodiment 1 to Embodiment 3

[0473] [Manufacturing of paper media]

[0474] [Example 1-1 to Example 1-13, Comparative Examples 1-1 to 1-2]

[0475] Bleached kraft pulp (LBKP, whiteness 86%) was beaten to 400 mL of CSF to prepare a 3% suspension. 0.5 parts by mass of aluminum sulfate was added to 100 parts by mass of the pulp to dilute it, and titanium oxide was added so that the content in the paper sheet medium became the content (mass %) described in Table 1-1. Furthermore, 0.8 parts by mass of polyepichlorohydrin-based paper wet strength agent WS4024 (produced by Seiko PMC Co., Ltd.) was added to 100 parts by mass of the pulp, and the paper was formed into a sheet in a wet paper machine to produce a paper sheet medium having a unit mass and thickness as shown in Table 1-1.

[0476] The prepared paper sheet medium was dissociated again and the fiber length was measured to be 0.67 mm, the fiber width was 16.5 μm, and the fine fiber content was 6.9%.

[0477] In addition, rutile type titanium oxide and anatase type titanium oxide were used as titanium oxide, and the types of titanium oxide used are shown in Table 1-1.

[0478] [Examples 1-14]

[0479] A paper sheet medium was prepared in the same manner as in Example 1-2.

[0480] 100 parts by mass of a styrene block copolymer (a triblock copolymer of styrene-hydrogenated isoprene-styrene) (Septon 2063, manufactured by Kuraray Co., Ltd.), 70 parts by mass of a styrene tackifier (FTR8100, manufactured by Mitsui Chemicals, Inc.), and 50 parts by mass of a paraffin oil (Diana Process Oil PW-90, manufactured by Idemitsu Kosan Co., Ltd.) were dissolved in toluene and stirred until uniform to obtain a toluene solution of an adhesive. Thereafter, the adhesive was applied to a biaxially stretched polypropylene film (FOA, manufactured by Futamura Chemical Co., Ltd.) having a thickness of 30 μm using a knife coater so that the film thickness after drying was 20 μm, and then the toluene solvent was dried at 100° C. for 3 minutes, and the obtained adhesive film was attached to the above-mentioned paper sheet to obtain a printing medium.

[0481] The paper medium was removed, and the total light transmittance of the transparent resin layer was measured in accordance with JIS K 7361-1:1997. The result was 80% or more.

[0482] [Examples 1-15]

[0483] A paper sheet medium was prepared in the same manner as in Example 1-2.

[0484] Polyethylene pellets (Novate (registered trademark) LC522 manufactured by Japanpolyethylene Corporation) were introduced into a single screw extruder (50C150 manufactured by Toyo Seiki Seisaku-sho Co., Ltd.) and melted at 320° C. Thereafter, the pellets were melt-laminated on a corona-treated paper sheet in such a manner that the thickness of the resin became 20 μm, and then rapidly cooled while being clamped by a cooling roll whose temperature was adjusted to 20° C., thereby obtaining a sheet medium laminate having a laminated layer.

[0485] The paper medium was removed, and the total light transmittance of the transparent resin layer was measured in accordance with JIS K 7361-1:1997. The result was 80% or more.

[0486] [Examples 1-16]

[0487] Unbleached conifer kraft pulp (NUKP, whiteness 21.4%) was beaten to 550 mL of CSF to prepare a 3% suspension. 0.5 parts by mass of aluminum sulfate and 0.1 parts by mass of yellow coloring pigment (Yellow RS-5, manufactured by Mikoku Pigments Co., Ltd.) were added to 100 parts by mass of the pulp and diluted, and titanium oxide was added so that the content in the paper sheet medium became the content (mass %) described in Table 1-1. Furthermore, 0.8 parts by mass of polyepichlorohydrin-based paper wet strength agent WS4024 (manufactured by Seiko PMC Co., Ltd.) was added to 100 parts by mass of the pulp, and the paper sheet medium having the mass per unit area and thickness described in Table 1-1 was prepared.

[0488] In addition, rutile titanium oxide was used as titanium oxide, and the types of titanium oxide used are shown in Table 1-1.

[0489] [Comparative Examples 1-3 and 1-4]

[0490] In Comparative Example 1-3, a portable inkjet printer (MOBILEJETMINI, manufactured by Yamazaki Sangyo Co., Ltd.) was used to provide a printed area on printing paper (KB39-7, manufactured by KOKUYO Co., Ltd.). In addition, as the inkjet ink, water-absorbing raw material manufactured by Yamazaki Sangyo Co., Ltd. was used.

[0491] In Comparative Example 1-4, a print area was provided on a thermal label (Lesprit general purpose thermal label manufactured by SATO HOLDINGS CORPORATION) using a thermal printer (Lesprit T8 manufactured by SATO HOLDINGS CORPORATION).

[0492] (Examples: 2-1, 2-5, 2-8, 2-11 to 2-13, Comparative Example: 2-3)

[0493] Bleached kraft pulp of broadleaf trees (LBKP, whiteness 86.0%, eucalyptus material 100%) was beaten to 400 mL of CSF to prepare a 3% suspension. After adding 0.5 parts by mass of aluminum sulfate to 100 parts by mass of the pulp and diluting, titanium oxide was added so that the content in the paper sheet medium became the content (mass %) described in Table 1-2. Furthermore, 0.8 parts by mass of polyepichlorohydrin-based paper wet strength agent WS4024 (produced by Seiko PMC Co., Ltd.) was added to 100 parts by mass of the pulp, and the paper sheet medium having the mass per unit area and thickness described in Table 1-2 was prepared.

[0494] (Example: 2-2)

[0495] Hardwood bleached kraft pulp (LBKP, brightness 86.0%, eucalyptus material 100%) was beaten to a CSF of 400 mL to prepare a 3 mass % suspension.

[0496] Conifer kraft pulp (NBKP, brightness 84.4%) was beaten to a CSF of 700 mL to prepare a 3 mass % suspension.

[0497] Then, pulp was mixed at a ratio of LBKP:NBKP=65:35 (whiteness of the mixed pulp was 85.0%), and 0.5 parts by mass of aluminum sulfate was added to 100 parts by mass of the pulp to dilute it, and titanium oxide was added so that the content in the paper sheet medium became the content (mass %) described in Table 1-2. Furthermore, 0.8 parts by mass of polyepichlorohydrin-based paper wet strength agent WS4024 (produced by Seiko PMC Co., Ltd.) was added to 100 parts by mass of the pulp, and the paper was formed into a sheet in a wet paper machine to produce paper sheet media having the mass per unit area and thickness described in Table 1-2.

[0498] In Example 2-12, a transparent resin layer was provided in the same manner as in Example 1-15.

[0499] (Examples: 2-3, 2-4, 2-6, 2-7, 2-9, 2-10)

[0500] Conifer kraft pulp (NBKP, whiteness 84.4%) was beaten to 700 mL of CSF to prepare a 3% suspension. 0.5 parts by mass of aluminum sulfate was added to 100 parts by mass of the pulp to dilute it, and titanium oxide was added so that the content in the paper sheet medium became the content (mass %) described in Table 1-2. Furthermore, 0.8 parts by mass of polyepichlorohydrin-based paper wet strength agent WS4024 (produced by Seiko PMC Co., Ltd.) was added to 100 parts by mass of the pulp, and the paper was formed into a sheet in a wet paper machine to produce a paper sheet medium with a unit mass and thickness shown in Table 1-2.

[0501] In Examples 2-4, 2-7, and 2-10, a transparent resin layer was provided in the same manner as in Example 1-15.

[0502] (Example 2-14)

[0503] The bleached kraft pulp (LBKP, whiteness 86.0%) used in Example 2-1 was dehydrated in a disposable pulper, and after being made into sheets, it was beaten in a manner that the CSF became 400 mL to prepare a 3% by mass suspension. It should be noted that the dehydration in the pulper is carried out on the net of the pulper, so the fine fibers can be reduced by selecting the mesh size of the net. After adding 0.5 parts by mass of aluminum sulfate to 100 parts by mass of the pulp and diluting it, titanium oxide was added in a manner that the content in the paper sheet medium became the content (mass %) recorded in Table 1-2. Furthermore, 0.8 parts by mass of polyepichlorohydrin-based paper wet strength agent WS4024 (produced by Seiko PMC Co., Ltd.) was added to 100 parts by mass of the pulp, and formed into sheets in a wet papermaking machine to produce paper sheet media with the unit area mass and thickness shown in Table 1-2.

[0504] (Example 2-15)

[0505] The hardwood bleached kraft pulp (LBKP, brightness 86.0%, eucalyptus material 100%) used in Example 2-1 was beaten to a CSF of 400 mL to prepare a 3 mass % suspension.

[0506] The powder pulp was prepared by mechanically pulverizing dry flakes of LBKP (bleached hardwood kraft pulp) in a chopper (manufactured by Horai Co., Ltd., HA8 2542 30E, screen size 0.24 mm).

[0507] Then, the pulp was mixed at a ratio of LBKP: pulverized pulp = 70:30 to prepare a 3% suspension. After adding 0.5 parts by mass of aluminum sulfate to 100 parts by mass of the pulp and diluting, titanium oxide was added so that the content in the paper sheet medium became the content (mass %) described in Table 1-2. Furthermore, 0.8 parts by mass of polyepichlorohydrin-based paper wet strength agent WS4024 (produced by Seiko PMC Co., Ltd.) was added to 100 parts by mass of the pulp, and the paper was formed into a sheet in a wet paper machine to produce a paper sheet medium having a unit mass and thickness as shown in Table 1-2.

[0508] (Example 2-16)

[0509] A bleached kraft pulp of a broadleaf tree (LBKP, whiteness 85.0%, acacia material 100%) different from that used in Example 2-1 was beaten in a CSF of 400 mL to prepare a 3% suspension. After adding 0.5 parts by mass of aluminum sulfate to 100 parts by mass of the pulp and diluting, titanium oxide was added so that the content in the paper sheet medium became the content (mass %) described in Table 1-2. Furthermore, 0.8 parts by mass of polyepichlorohydrin-based paper wet strength agent WS4024 (produced by Seiko PMC Co., Ltd.) was added to 100 parts by mass of the pulp, and the mixture was formed into a sheet in a wet paper machine to produce a paper sheet medium having a unit mass and thickness as shown in Table 1-2.

[0510] (Example 2-17)

[0511] Coniferous bleached kraft pulp (NBKP, whiteness 85.0%, pine material 100%) different from that used in Example 2-2 was beaten to 700 mL of CSF to prepare a 3% suspension. 0.5 parts by mass of aluminum sulfate was added to 100 parts by mass of the pulp to dilute it, and titanium oxide was added so that the content in the paper sheet medium became the content (mass %) described in Table 1-2. Furthermore, 0.8 parts by mass of polyepichlorohydrin-based paper wet strength agent WS4024 (produced by Seiko PMC Co., Ltd.) was added to 100 parts by mass of the pulp, and the paper was formed into a sheet in a wet paper machine to produce a paper sheet medium having a unit mass and thickness as shown in Table 1-2.

[0512] (Comparative Example: 2-1)

[0513] A 3% suspension was prepared by using unbeaten hemp pulp (whiteness 85.0%) (CSF 700 mL). After adding 0.5 parts by mass of aluminum sulfate to 100 parts by mass of the pulp and diluting, titanium oxide was added so that the content in the paper sheet medium became the content (mass %) described in Table 1-2. Furthermore, 0.8 parts by mass of polyepichlorohydrin-based paper wet strength agent WS4024 (produced by Seiko PMC Co., Ltd.) was added to 100 parts by mass of the pulp, and the paper was formed into a sheet in a wet paper machine to produce a paper sheet medium having a unit mass and thickness as shown in Table 1-2.

[0514] (Comparative Example 2-2)

[0515] A bleached kraft pulp of a broadleaf tree (LBKP, whiteness 86.0%, tamarisk material) different from that used in Example 2-1 was beaten in a CSF of 300 mL to prepare a 3% suspension. 0.5 parts by mass of aluminum sulfate was added to 100 parts by mass of the pulp and diluted, and titanium oxide was added so that the content in the paper sheet medium became the content (mass %) described in Table 1-2. Furthermore, 0.8 parts by mass of polyepichlorohydrin-based paper wet strength agent WS4024 (produced by Seiko PMC Co., Ltd.) was added to 100 parts by mass of the pulp, and the paper was formed into a sheet in a wet paper machine to produce a paper sheet medium having a unit mass and thickness as shown in Table 1-2.

[0516] (Comparative Example 2-4)

[0517] Using the paper medium used in Example 2-1, a 10 mm square marking was performed using an infrared laser (MD-F3200 manufactured by Keyence Corporation). The irradiation conditions are as follows.

[0518] Wavelength: 1090nm

[0519] Repetition frequency: 60kHz

[0520] ·Spot diameter = 40μm

[0521] Scanning speed: 2000mm / sec

[0522] ·Focal distance: 300mm (focusing is performed using the height correction included with the device)

[0523] Line spacing: 200μm

[0524] Power: 3W

[0525] As a result, printing cannot be performed.

[0526] (Comparative Example 2-5)

[0527] Using the paper sheet medium used in Example 2-1, a 10 mm square marking was performed using a green laser (MD-S9910A manufactured by Keyence Corporation). The irradiation conditions are as follows.

[0528] Wavelength: 532nm

[0529] Repetition frequency: 60kHz

[0530] ·Spot diameter = 40μm

[0531] Scanning speed: 2000mm / sec

[0532] ·Focal distance: 300mm (focusing is performed using the height correction included with the device)

[0533] Line spacing: 200μm

[0534] Power: 3W

[0535] As a result, printing cannot be performed.

[0536] (Comparative Example 2-6)

[0537] Using the paper sheet medium used in Example 2-1, a 10 mm square marking was performed using a CO2 laser (ML-Z9610 manufactured by Keyence Corporation). The irradiation conditions are as follows.

[0538] Wavelength: 10600nm

[0539] ·Spot diameter = 40μm

[0540] Scanning speed: 2000mm / sec

[0541] ·Focal distance: 300mm (focusing is performed using the height correction included with the device)

[0542] Line spacing: 200μm

[0543] Power: 3W

[0544] As a result, printing cannot be performed.

[0545] (Examples 3-1 to 3-25, and Comparative Examples 3-1, 3-3, and 3-4)

[0546] <Masterbatch production method>

[0547] 50 parts of the resin were put into a kneader and kneaded at 120°C to 140°C (PE, PP) and 270°C (PET). After the mixture was melted, 50 parts of titanium oxide were added and kneaded for 10 minutes. After that, the mixture was extruded in a single screw extruder and a pelletized masterbatch was prepared using a thermal cutting device.

[0548] <Film forming method>

[0549] The obtained masterbatch and resin were fed into an extruder so as to have the titanium oxide content shown in Table 2, and a coat hanger type T die was used. The extruder was used to perform melt extrusion at a resin temperature of 120°C to 140°C (PE, PP) and 280°C (PET), and a voltage of 7 kV was applied to the pinning wire, and the film was quenched on a casting roll whose temperature was adjusted to 20°C to obtain an unstretched sheet. The obtained unstretched sheet was stretched in a roll longitudinal stretching machine to obtain a uniaxially stretched film with a thickness of 30 to 70 μm.

[0550] (Comparative Example 3-2)

[0551] The sheet medium was prepared with reference to Example 6 of Japanese Patent Publication No. 11-020316. Specifically, titanium oxide was added to 100 parts by mass of acrylic rubber (manufactured by UNIMATEC CO., LTD., PA312) in such a manner that the titanium oxide content in Table 2 was obtained, 1 part by mass of stearic acid and 0.5 part by mass of wax (Sangnok) were added, and kneaded in a kneader for 10 minutes, then kneaded with two 10-inch rolls, taken out from the rolls at once and cooled, and then heated with rolls again, and 3 parts by mass of zinc dimethyldithiocarbamate were added thereto to prepare a composition. The composition was press-cured at 195°C for 3 minutes with a pressure of 110 tons, and then oven-cured (secondary vulcanization) was performed at 165°C for 6 hours to obtain a vulcanized sheet with a thickness of 2 mm.

[0552] (Comparative Example 3-5 to Comparative Example 3-6)

[0553] In Comparative Example 3-5, a portable inkjet printer (MOBILEJET MINI, manufactured by Yamazaki Sangyo Co., Ltd.) was used to provide a printing area on an inkjet OHP film (IT-120PF45-035, manufactured by KOKUYO Co., Ltd.). In addition, as an inkjet ink, a non-water-absorbing raw material manufactured by Yamazaki Sangyo Co., Ltd. was used.

[0554] In Comparative Example 3-6, a printed area was thermally provided on a polyester film (manufactured by LINTEC Corporation, FD-5810-45) using a thermal printer (manufactured by SATO HOLDINGS CORPORATION, Lesprit T8).

[0555] 〔Titanium oxide〕

[0556] The details of titanium oxide used in Examples and Comparative Examples are as follows.

[0557] <Rutile Titanium Oxide>

[0558] · Amorphous, average particle size = 0.2 μm (measured value obtained by a laser diffraction / scattering particle size distribution analyzer) (manufactured by Ishihara Sangyo Co., Ltd., R780)

[0559] Amorphous, average particle size = 4.3 μm (measured value obtained by a laser diffraction / scattering particle size distribution analyzer) (manufactured by Ishihara Sangyo Co., Ltd., PER410)

[0560] Needle-shaped, long diameter = 1.7 μm, short diameter = 0.1 μm (manufactured by Ishihara Sangyo Co., Ltd., FTL100)

[0561] Needle-shaped, long diameter = 10 μm, short diameter = 0.5 μm (manufactured by Ishihara Sangyo Co., Ltd., FTL400)

[0562] <Anatase titanium oxide>

[0563] ·Amorphous, average particle size 0.1 μm (manufactured by Ishihara Sangyo Co., Ltd., A100)

[0564] 〔Resin〕

[0565] The details of the resins used in Examples and Comparative Examples are as follows.

[0566] Polyethylene: Novate (registered trademark) LC522 (manufactured by Japan Polyethylene Corporation)

[0567] ·Polypropylene: Made by Sumitomo Chemical Co., Ltd., FS2011DG3

[0568] ·Polyethylene terephthalate: UNITIKA LTD., SA-8339P

[0569] ·Acrylic rubber (manufactured by UNIMATEC CO., LTD., PA312)

[0570] [Ultraviolet laser irradiation conditions-1 (Examples 1-1 to 1-16 (Examples 1-1 to 1-16 are also collectively referred to as Example 1, and the same applies hereinafter), Comparative Examples 1-1, 1-2, Examples 3-1 to 3-25, Comparative Examples 3-1 to 3-4)]

[0571] The obtained printing medium was subjected to ultraviolet laser (AVIA266-3000 manufactured by Coherent) for Figure 1 The barcode shown was printed and a 10 mm square mark was made. The irradiation conditions were as follows.

[0572] Wavelength: 355nm

[0573] Repetition frequency: 50kHz

[0574] Pulse amplitude: 25ns

[0575] Spot diameter: 104μm

[0576] Scanning speed: 4000mm / sec

[0577] Focus distance: 250mm

[0578] Line spacing: 150μm

[0579] In addition, the power is set to the value shown in Table 1 and Table 2.

[0580] [Ultraviolet laser irradiation conditions-2 (Examples 2-1 to 2-17, Comparative Examples 2-1 to 2-3)]

[0581] The obtained printing medium was marked with an ultraviolet laser (MD-U1020C manufactured by Keyence Corporation). Figure 1 The barcode shown is printed and is 10mm square.

[0582] The irradiation conditions are as follows.

[0583] Wavelength: 355nm

[0584] Repetition frequency: 40kHz

[0585] ·Spot diameter = 40μm

[0586] Scanning speed: 3000mm / sec

[0587] ·Focal distance: 300mm (focusing is performed using the height correction included with the device)

[0588] Line spacing: 40μm

[0589] In addition, the power was set to the value shown in Table 1.

[0590] [Measurement / Evaluation]

[0591] The properties of the pulp used were measured as follows.

[0592] 〔CSF〕

[0593] Canadian standard freeness (CSF) is measured according to JIS P 8121-2:2012.

[0594] 〔Whiteness〕

[0595] The whiteness of the pulp used was measured in accordance with JIS P 8212:1998.

[0596] In addition, the following evaluations were performed on the sheet media or printed materials that were starved.

[0597] [Measurement of length-weighted average fiber length, average fiber width, and amount of fine fibers]

[0598] When the sheet medium is a paper sheet medium, the printing medium obtained in the examples and comparative examples is cut into 40 cm squares, immersed in ion exchange water, adjusted to a concentration of 2%, and immersed for 24 hours. After immersion for 24 hours, a standard disintegrator (manufactured by Kumagai Riki Kogyo Co., Ltd.) is used to treat until the undissociated fibers disappear, and the pulp is dissociated into fibers. In the case of a transparent resin layer, the dissociated slurry (dispersion of pulp fibers) after the transparent resin layer is removed is classified, and a fiber length measuring machine (model FS-5 with UHD base unit, manufactured by Valmet) is used to measure the "length load average fiber length (ISO)", "microfiber amount", and "fiber width".

[0599] In addition, "length load average fiber length (ISO)" is the length-weighted average fiber length calculated by selecting fibers having a length of 0.2 mm or more and 7.6 mm or less.

[0600] The “fine fiber amount” refers to the ratio of the number of fine fibers having a fiber width of 75 μm or less and a length of 0.08 mm or more and 0.20 mm or less in the disintegrated pulp fibers.

[0601] The “fiber width” is a length-load average fiber width calculated by selecting fibers having a width of 10 μm or more and 75 μm or less.

[0602] In addition, when only a small amount of paper sheet media can be secured, the pulp can be disintegrated into fibers using a manual disintegrator (Dasher, Valmet) that processes the paper sheet media by piston motion. The piston motion is continued until the undisintegrated fibers disappear. However, if the disintegration is not complete, the piston motion is set to 10,000 times as the upper limit, and the pulp slurry obtained thereafter is subjected to measurement.

[0603] 〔Weight per unit area, paper thickness〕

[0604] The mass per unit area of ​​the paper sheet media used in Examples and Comparative Examples was measured in accordance with JIS P 8124: 2011. The thickness of the paper sheet media used in Examples and Comparative Examples was measured in accordance with JIS P 8118:2014.

[0605] 〔Thickness of thin film medium〕

[0606] The thickness of the thin film media in Examples and Comparative Examples was measured in accordance with JIS P 8118:2014.

[0607] 〔Raman spectrum-1〕

[0608] Regarding Example 1, Comparative Example 1, Example 3, and Comparative Example 3, Raman spectra were measured by the following method.

[0609] <Measurement conditions>

[0610] The measurement conditions of Raman spectroscopy are as follows, but when damage is visible in the printed material under the laser used in the measurement, when the fluorescence is strong, etc., the following measurement conditions such as laser power and irradiation time can be appropriately changed. Among them, the Raman intensity of the printed area and the non-printed area adopts the value measured under the same conditions.

[0611] · Device: inVia Raman microscope QUONTOR manufactured by Renishaw

[0612] Excitation laser: 532nm

[0613] Laser power: 50mW (power 100%)

[0614] Laser power: 5%

[0615] ·Measurement mode: Confocal mode

[0616] ·Irradiation time: 2.0 seconds

[0617] Cumulative times: 10 times

[0618] Laser spot diameter: 2.5μm

[0619] Objective lens: 20 times

[0620] <Measurement method>

[0621] The measurement was performed by the following method.

[0622] (1) Using a standard sample (single crystal silicon, manufactured by Renishaw), the Raman shift position was calibrated (520.5 cm for single crystal silicon). -1 ).

[0623] (2) Place the sheet sample on the sample stand and, if necessary, set a clamp so that the sheet remains flat.

[0624] (3) Under the device Figure 2 As shown, observe with the focus aligned (set so that the focus becomes the minimum under the simulated laser). When measuring the printed area, measure so that the darkest part that can be visually confirmed is close to the center of the guide plate displayed during measurement. When measuring the non-printing area, measure at a distance of 300μm or more from the printed area.

[0625] (4) The obtained Raman spectrum was subjected to baseline correction (smart correction) using the processing software (Wire 5.2 manufactured by Renishaw) attached to the device. The baseline was corrected using polynomial 11 of the processing software.

[0626] (5) Reading 447±3cm for rutile titanium oxide -1 The maximum value (maximum intensity) of the wave number range is 516±3cm for anatase titanium oxide. -1 The maximum value (maximum intensity) of the wavenumber range is taken and the Raman intensity ratio is calculated according to the following formula.

[0627] Raman intensity ratio = maximum intensity of the printed area ÷ maximum intensity of the non-printed area

[0628] (6) 10 locations were measured in each of the printing area (printing portion) and the non-printing area (non-printing portion), and the average value was used as the measurement result.

[0629] 〔Raman Spectroscopy-2〕

[0630] Regarding Example 2 and Comparative Example 2, Raman spectra were measured by the following method.

[0631] <Measurement conditions and measurement methods>

[0632] The measurement conditions and method of Raman spectroscopy are as described above. However, when damage is visible in the printed material under the laser used in the measurement, when the fluorescence is strong, the following measurement conditions such as laser power and irradiation time can be appropriately changed. Among them, the Raman intensity of the printed area and the non-printed area adopts the value measured under the same conditions.

[0633] From the viewpoint of suppressing fluctuations in the measured value, it is preferred to measure within a range where the count of the Raman intensity in the printed area is 10,000 or less. Therefore, the measurement conditions are appropriately changed and the measurement is performed so that the count of the Raman intensity in the printed area is within a range of 10,000 or less. In addition, the measurement is performed 10 times under the following measurement conditions, and the values ​​deviating by more than the mean value ± 2SD (standard deviation) are excluded, and the average is again taken as the average value of the Raman intensity.

[0634] 〔Print clarity〕

[0635] The obtained print ( Figure 1 The clarity of printing of a printed matter (a printed matter with a barcode printed on it) was evaluated based on the following evaluation criteria.

[0636] A color close to the printed color was selected visually using the Munsell table (a color specification produced by Japan Color Research Co., Ltd.), and the clarity was evaluated based on the following criteria.

[0637] A: Brightness is 4 or less in the Munsell scale (no color)

[0638] B: Brightness in the Munsell scale (no color) is 5 to 6

[0639] C: Brightness 7 to 8 in the Munsell scale (no color)

[0640] D: Brightness is 9 or above in the Munsell scale (no color)

[0641] [Solvent resistance]

[0642] The obtained print ( Figure 1 The solvent resistance of the printed matter (a barcode printed on the printed matter) was evaluated according to the following evaluation criteria.

[0643] The printed material was immersed in 100% acetone (manufactured by Kanto Chemical) and allowed to stand for 15 minutes. The printed material was then taken out, the solvent was wiped off with tissue paper, and the solvent resistance was visually evaluated according to the following evaluation criteria.

[0644] A: No blurring or falling off of the print was observed before and after immersion (no change).

[0645] B: Blurring and peeling of the printing were visible before and after immersion.

[0646] 〔Smoke output〕

[0647] When irradiating the 10 mm square mark with ultraviolet laser light, it was observed whether smoke was observed, and the amount of smoke was evaluated by the following method.

[0648] <Judgment Criteria>

[0649] 0: No smoke can be visually detected

[0650] 1: Slight smoke can be observed visually, but the amount of smoke is very small

[0651] 2: Smoke can be visually confirmed, but the amount of smoke is small.

[0652] 3: The smoke can be easily confirmed by visual inspection, and the amount of smoke is large

[0653] [Evaluation of strength reduction]

[0654] The deterioration of tensile strength was evaluated by the following method.

[0655] The obtained printing medium was marked with a 15 cm square using an ultraviolet laser (MD-U1020C manufactured by Keyence Corporation).

[0656] The irradiation conditions are as follows.

[0657] Wavelength: 355nm

[0658] Repetition frequency: 40kHz

[0659] ·Spot diameter = 40μm

[0660] Scanning speed: 3000mm / sec

[0661] ·Focal distance: 300mm (focusing is performed using the height correction included with the device)

[0662] Line spacing: 40μm

[0663] The power is set to the value shown in Table 2.

[0664] Thereafter, strips having a width of 15 mm and a length of 150 mm were cut out and subjected to a tensile test to measure the tensile strength in accordance with JIS P8113:2006.

[0665] When there is a difference in direction among the sheets in the stretched film, the test pieces are taken out from the same direction.

[0666] The test was similarly conducted before laser printing, and the intensity reduction rate was calculated as follows.

[0667] Decline rate = 100-(tensile strength after printing ÷ tensile strength before printing × 100)

[0668] <Judgment Criteria>

[0669] 0: The decline rate is less than 1%

[0670] 1: The decline rate is more than 1% and less than 5%

[0671] 2: The decline rate is more than 5% and less than 10%

[0672] 3: The decline rate is more than 10% and less than 15%

[0673] 4: The decline rate is more than 15% and less than 20%

[0674] 〔Titanium oxide content〕

[0675] <Preparation of test pieces>

[0676] The printable area of ​​the print medium was cut into an appropriate size to prepare a sample (test piece), and the cut area and mass were recorded.

[0677] <Dissolution of test piece>

[0678] A mixed solvent of nitric acid: hydrofluoric acid = 50:5 (volume %) and a test piece were placed in a Teflon (registered trademark) container of an autoclave apparatus (manufactured by CEM Japan, MARS5), and the autoclave treatment was performed at 210°C for 120 minutes to dissolve the test piece. The mass of the test piece can be appropriately changed, and when the test piece remains after dissolution, the ratio of nitric acid to hydrofluoric acid, the treatment temperature, the treatment time, etc. can be appropriately changed.

[0679] After the test piece is dissolved, the volume is accurately adjusted with ultrapure water.

[0680] <Measurement of the amount of titanium oxide in a solution>

[0681] (1) The ICP apparatus and measurement conditions are as follows.

[0682] ICP apparatus: ICP-OEC apparatus (manufactured by Rigaku Corporation, CIROS1-20)

[0683] Determination conditions:

[0684] Carrier gas: Argon

[0685] Argon gas flow rate 0.9L / min

[0686] Plasma gas flow rate 14L / min

[0687] Plasma power 1400W

[0688] Pump speed: 2

[0689] ·Measurement wavelength Ti: 334.941nm

[0690] (2) Preparation of standard curve

[0691] A universal mixed standard solution (manufactured by SPEX, XSTC-622B) was accurately measured to have the following concentrations, and subjected to measurement under the above-mentioned measurement conditions to measure the intensity at 334.941 nm corresponding to the emission wavelength of titanium atoms.

[0692] ·Concentrations for standard curve preparation: 0ppm, 0.01ppm, 0.05ppm, 0.1ppm, 0.5ppm, 1.0ppm, 3.0ppm, 5.0ppm

[0693] (3) Determination of titanium oxide content in the solution

[0694] The solution in which the test piece was dissolved was diluted with ultrapure water so as to fall within the above-mentioned standard curve, and subjected to ICP measurement.

[0695] (4) Calculation method of titanium oxide content

[0696] The titanium oxide content was calculated by the following formula: It should be noted that the molecular weight of titanium oxide ÷ the molecular weight of titanium ≈ 1.669.

[0697] Titanium oxide content (g / m 2 )=ICP determination concentration (ppm)×dilution ratio×fixed volume (L)×1.669×1000÷area (m 2 )

[0698] Titanium oxide content (mass %) = ICP measurement concentration (ppm) × dilution ratio × fixed volume (L) × 1.669 ÷ test piece mass (mg) × 100

[0699] 〔Titanium oxide particle size〕

[0700] The particle size of titanium oxide added to paper and film is calculated from an SEM image obtained by a scanning electron microscope (SEM, manufactured by Hitachi High-Technologies Corporation, S5200, etc.) of ash obtained by burning a sheet medium or printed matter in a muffle furnace.

[0701] Specifically, the ash content was obtained under the same conditions as in the measurement of the above-mentioned "Titanium oxide content".

[0702] The sample of ash content tested in scanning electron microscope is made as follows: applied to an ultrasonic homogenizer (Yamato Scientific Co., Ltd. system, LUH150, etc.) with a power of 50W for 5 minutes, and dispersed in ethanol to obtain 0.01% by mass slurry, 0.1mL is cast into an aluminum dish, and after drying at 60°C, the aluminum dish is cut into a suitable size for testing in SEM to make. Visually select those that can be clearly distinguished from adjacent particles, and use the major diameter of one particle as the particle size. At this time, even if the primary particles are mixed with the secondary particles in the aggregated state and can be clearly distinguished, they are counted as one particle respectively, and the average diameter of 100 randomly selected particles is used as the particle size. The magnification during SEM image observation is appropriately selected according to the particle size of titanium oxide, and is set to about 20,000 times.

[0703] In the case of needle-shaped particles, the average diameter of the short diameter of 100 particles whose long diameters were measured was taken as the short diameter.

[0704] When particles other than titanium oxide are included, particles containing titanium element are measured using an energy dispersive X-ray analyzer attached to a SEM (manufactured by Horiba, Ltd., EMAX, etc.).

[0705] 〔Determination of whiteness〕

[0706] The whiteness of the printed medium having the obtained paper sheet medium was measured.

[0707] The whiteness of the paper sheet medium was measured using a spectroscopic whiteness colorimeter (manufactured by SUGA TEST INSTRUMENTS CO., LTD.) according to the method described in JIS P 8148:2018.

[0708] [Table 1-1]

[0709]

[0710] [Table 1-2]

[0711]

[0712] [Table 2-1]

[0713]

[0714] [Table 2-2]

[0715]

[0716] As shown in Tables 1 and 2, by directly printing a printing medium having a sheet medium containing a specific amount of titanium oxide or more under ultraviolet laser light, a printed product having excellent print clarity and excellent solvent resistance was obtained. In addition, in Examples 1-14 and 1-15 having a transparent resin layer, an image having excellent print clarity was obtained compared to Example 1-2 having no transparent resin layer.

[0717] In addition, when the sheet medium is paper, by setting the length-weighted average fiber length and average fiber width of the pulp constituting the paper and the unit area mass of the aforementioned paper to a specific range, an image with better print clarity is obtained, and smoke generation during irradiation with ultraviolet laser is suppressed.

[0718] When the sheet medium is a film, by setting the thickness of the film to a specific range and using the film as a specific resin film, an image with better print clarity can be obtained and a decrease in intensity due to irradiation with ultraviolet laser light can be suppressed.

[0719] On the other hand, when a printing medium having a sheet medium whose content of titanium oxide is lower than a specific amount is used, sufficient print clarity cannot be obtained.

[0720] In addition, as shown in Comparative Examples 1-3, 1-4, 3-5, and 3-6, conventional inkjet and thermal labels did not provide sufficient solvent resistance. Furthermore, as shown in Comparative Examples 2-4 to 2-6, printing was not possible under irradiation with infrared laser, green laser, and CO2 laser.

[0721] Example 4 and Example 5

[0722] The materials and the like used in the following examples are as follows.

[0723] [Base material]

[0724] <Paper>

[0725] Paper A: corrugated paper liner (manufactured by Oji Materia Co., Ltd., OFK-EM170, mass per unit area 170 g / m 2 , paper thickness 205μm, whiteness 15%)

[0726] Paper B: Paper B was prepared according to the method of Example 1 of Japanese Patent Application Laid-Open No. 2019-099923, with a titanium oxide content of 3 g / m 2 The content of titanium oxide was changed in the manner of . As titanium oxide, amorphous rutile titanium oxide (particle size = 0.2 μm, R780 manufactured by Ishihara Sangyo Co., Ltd.) was used. The properties of the obtained paper are as follows: unit area mass 80 g / m 2 , thickness 120μm, whiteness 84.9%.

[0727] Paper C: Paper C was prepared according to the method of Example 1 of Japanese Patent Application Publication No. 2019-099923, with a titanium oxide content of 30 g / m 2 The type and content of titanium oxide were changed in the same manner. Amorphous rutile titanium oxide (particle size = 0.2 μm, R780 manufactured by Ishihara Sangyo Co., Ltd.) was used as titanium oxide. The properties of the obtained paper were as follows: mass per unit area 100 g / m 2 , thickness 120μm, whiteness 84.9%.

[0728] Paper D: Corrugated paper liner (paper A) and corrugated paper core paper (manufactured by Oji Materia Co., Ltd., OND-EM160, mass per unit area 160 g / m 2 , paper thickness 210μm), and a corrugated sheet with A groove on both sides was made by a corrugating mill with a corrugating roller having a flute height of 4.5mm and a flute number of 34 layers / 30cm. It should be noted that the corrugated paper adhesive used to bond the liner base paper to the core base paper is a starch paste of a commonly used single-can method.

[0729] Paper 1: Hardwood bleached kraft pulp (LBKP, whiteness 86.0%) was beaten to 400 mL of CSF to prepare a 3% suspension. 0.5 parts by mass of aluminum sulfate was added to 100 parts by mass of the pulp to dilute it, and then 0.8 parts by mass of polyepichlorohydrin-based paper wet strength agent WS4024 (produced by Seiko PMC Co., Ltd.) was added to 100 parts by mass of the pulp, and the mixture was formed into a sheet in a wet papermaking machine to prepare a paper substrate. The properties of the obtained paper 1 are as follows: Weight per unit area 70 g / m 2 , thickness 90μm, whiteness 86%.

[0730] Paper 2: Hardwood bleached kraft pulp (LBKP, brightness 86.0%) was beaten to a CSF of 400 mL to prepare a 3 mass % suspension. Conifer bleached kraft pulp (NBKP, brightness 84.0%) was beaten to a CSF of 700 mL to prepare a 3 mass % suspension.

[0731] Then, pulp was mixed at a ratio of LBKP:NBKP=65:35, and a paper base was prepared in the same manner as Paper 1. The properties of the obtained Paper 2 were as follows: Weight per unit area 70 g / m 2 , thickness 93μm, whiteness 85.6%.

[0732] Paper 3: Conifer kraft pulp (NBKP, whiteness 84.4%) was beaten to a CSF of 700 mL to prepare a 3% suspension. 0.5 parts by mass of aluminum sulfate was added to 100 parts by mass of the pulp to dilute it, and then 0.8 parts by mass of polyepichlorohydrin-based paper wet strength agent WS4024 (produced by Seiko PMC Co., Ltd.) was added to 100 parts by mass of the pulp, and the mixture was formed into a sheet in a wet paper machine to prepare a paper substrate. The properties of the obtained paper 3 are as follows: Weight per unit area 70 g / m 2 , thickness 95μm, whiteness 84.3%.

[0733] ·Paper 4: The hardwood bleached kraft pulp (LBKP, whiteness 86.0%) used in Paper 1 was beaten to 400 mL of CSF to prepare a 3% suspension. Powder pulp was prepared by mechanically crushing dry sheets of LBKP (bleached hardwood kraft pulp) in a shredder (manufactured by Horai Co., Ltd., HA82542 30E, screen 0.24 mm). Thereafter, the pulp was mixed at a ratio of LBKP: powder pulp = 70:30 (mass ratio), and a paper base was prepared in the same manner as Paper 1. The properties of the obtained Paper 4 are as follows: Weight per unit area 70 g / m 2 , thickness 86μm, whiteness 86.1%.

[0734] Paper 5: LBKP and powder pulp prepared in the same manner as Paper 4 were mixed at a ratio of LBKP: powder pulp = 70:10 (mass ratio), and a paper base was prepared in the same manner as Paper 1. The properties of the obtained Paper 5 are as follows: Weight per unit area 70 g / m 2 , thickness 89μm, whiteness 85.3%.

[0735] Paper 6: The bleached kraft pulp (LBKP) of hardwood used in Paper 1 was used, dehydrated in a disposable pulper, and after being made into sheets, the paper was beaten in such a way that the CSF became 400 mL to prepare a 3% by mass suspension. The paper substrate was prepared in the same manner as Paper 1. It should be noted that the dehydration in the pulper is carried out on the net of the pulper, so by selecting the mesh size of the net, it is possible to reduce fine fibers. The properties of the obtained Paper 6 are as follows: Weight per unit area 70 g / m 2 , thickness 90μm, whiteness 85.5%.

[0736] Paper 7: Unbleached kraft pulp (LUKP) from broadleaf trees was beaten to a CSF of 400 mL to prepare a 3% by mass suspension. A paper substrate was prepared in the same manner as Paper 1. The properties of the obtained Paper 7 were as follows: Weight per unit area 70 g / m 2 , thickness 90μm, whiteness 35%.

[0737] Paper 8: Unbeaten hemp pulp (CSF 700 mL) was used to prepare a 3% by mass suspension. A paper substrate was prepared in the same manner as Paper 1. The properties of the obtained Paper 8 were as follows: Weight per unit area 70 g / m 2 , thickness 95μm, whiteness 85.1%.

[0738] Paper 9: The hardwood bleached kraft pulp (LBKP, brightness 86.0%) used in Paper 1 was used and beaten to a CSF of 200 mL to prepare a 3% by mass suspension. A paper substrate was prepared in the same manner as Paper 1. The properties of the obtained Paper 9 are as follows: Weight per unit area 70 g / m 2 , thickness 85μm, whiteness 85.5%.

[0739] [Examples 4-1 to 4-5, Comparative Example 4-4]

[0740] As the coating liquid, KW050 AQP67 White DM manufactured by Toyo Ink Co., Ltd. was used.

[0741] The coating liquid contained amorphous titanium oxide (rutile type, average particle size = 0.2 μm (measured value obtained by a laser diffraction / scattering particle size distribution meter)) as titanium oxide and acrylic resin as thermoplastic resin. The content of titanium oxide in the coating liquid was 45% by mass, and the content of acrylic resin was 15% by mass.

[0742] The coating liquid was applied onto the substrates shown in Table 3 using a printing tester (K ​​Lox Proofer manufactured by RK Print Coat Instruments Ltd.) so that the content of titanium oxide would be the value shown in Table 3.

[0743] [Example 4-6, Comparative Example 4-1]

[0744] [Preparation of coating solution]

[0745] <Binder solution>

[0746] 10 parts by mass of polyvinyl alcohol (Exceval (registered trademark) RS-2817SB manufactured by Kuraray Co., Ltd.) was added to 90 parts by mass of ion exchange water and heated to 90° C. to dissolve the resultant 10% by mass polyvinyl alcohol aqueous solution as binder solution 1 .

[0747] <Titanium oxide>

[0748] As titanium oxide, amorphous rutile titanium oxide (particle size = 0.2 μm (measured value obtained by a laser diffraction / scattering particle size distribution analyzer), R780 manufactured by Ishihara Sangyo Co., Ltd.) was used.

[0749] <Preparation of coating solution>

[0750] 10 parts of titanium oxide were added to 90 parts of the binder solution 1, and the mixture was stirred at 1000 rpm for 5 minutes using a homomixer to prepare a coating liquid.

[0751] <Formation of coating layer>

[0752] A printing medium was prepared in the same manner as in Example 4-1 except that paper A was used as the substrate and the coating was performed so that the coating amount of titanium oxide became the value described in Table 3.

[0753] [Examples 4-7, 4-12 to 4-16]

[0754] <Titanium oxide>

[0755] As titanium oxide, amorphous rutile titanium oxide (particle size = 0.2 μm (measured value obtained by a laser diffraction / scattering particle size distribution analyzer), R780 manufactured by Ishihara Sangyo Co., Ltd.) was used.

[0756] <Preparation of coating solution>

[0757] 20 parts of the titanium oxide were added to 80 parts of the binder solution 1, and the mixture was stirred at 1000 rpm for 5 minutes using a homomixer to prepare a coating liquid.

[0758] <Formation of coating layer>

[0759] A printing medium was prepared in the same manner as in Example 4-1 except that the paper substrate described in Table 3 was used as the substrate and the coating was performed so that the coating amount of titanium oxide became the value described in Table 3.

[0760] [Examples 4-8]

[0761] <Titanium oxide>

[0762] As titanium oxide, amorphous anatase-type titanium oxide (average particle size = 0.2 μm (measured value obtained by a laser diffraction / scattering particle size distribution analyzer), A100 manufactured by Ishihara Sangyo Co., Ltd.) was used.

[0763] <Preparation of coating solution>

[0764] 20 parts of the titanium oxide were added to 80 parts of the binder solution 1, and the mixture was stirred at 1000 rpm for 5 minutes using a homomixer to prepare a coating liquid.

[0765] <Formation of coating layer>

[0766] A printing medium was prepared in the same manner as in Example 4-1 except that the paper substrate described in Table 3 was used as the substrate and the coating was performed so that the coating amount of titanium oxide became the value described in Table 3.

[0767] [Examples 4-9 to 4-11]

[0768] <Titanium oxide>

[0769] As titanium oxide, the following titanium oxide was used.

[0770] PER410 manufactured by Ishihara Sangyo Co., Ltd.: average particle size 4.3 μm (measured value obtained by a laser diffraction / scattering particle size distribution analyzer), amorphous (Examples 4-9)

[0771] ·Ishihara Sangyo Co., Ltd., FTL100: average major diameter = 1.7 μm, average minor diameter = 0.1 μm, needle-shaped (Examples 4-10)

[0772] ·Ishihara Industry Co., Ltd., FTL400: average major diameter = 10.0 μm, average minor diameter = 0.5 μm, needle-shaped (Example 4-11)

[0773] <Preparation of coating solution>

[0774] 20 parts of titanium oxide were added to 80 parts of the binder solution 1, and the mixture was stirred at 1000 rpm for 5 minutes using a homomixer to prepare a coating liquid.

[0775] <Formation of coating layer>

[0776] A printing medium was prepared in the same manner as in Example 4-1 except that the paper substrate described in Table 3 was used as the substrate and the coating was performed so that the coating amount of titanium oxide became the value described in Table 3.

[0777] [Example 4-17]

[0778] <Titanium oxide>

[0779] As titanium oxide, amorphous rutile titanium oxide (particle size = 0.2 μm (measured value obtained by a laser diffraction / scattering particle size distribution analyzer), manufactured by Ishihara Sangyo Co., Ltd., R780) was used.

[0780] <Preparation of coating solution>

[0781] 20 parts of the titanium oxide were added to 80 parts of the binder solution 1, and the mixture was stirred at 1000 rpm for 5 minutes using a homomixer to prepare a coating liquid.

[0782] <Formation of coating layer>

[0783] A printing medium was prepared in the same manner as in Example 4-1 except that the paper substrate described in Table 3 was used as the substrate and the coating was performed so that the coating amount of titanium oxide became the value described in Table 3.

[0784] <Production of transparent resin layer>

[0785] 100 parts by mass of a styrene block copolymer (a triblock copolymer of styrene-hydrogenated isoprene-styrene) (Septon 2063, manufactured by Kuraray Co., Ltd.), 70 parts by mass of a styrene tackifier (FTR8100, manufactured by Mitsui Chemicals, Inc.), and 50 parts by mass of a paraffin oil (Diana Process Oil PW-90, manufactured by Idemitsu Kosan Co., Ltd.) were dissolved in toluene and stirred until uniform to obtain a toluene solution of an adhesive. Thereafter, the solution was applied to a biaxially stretched polypropylene film (FOA, manufactured by Futamura Chemical Co., Ltd.) having a thickness of 30 μm using a knife coater so that the film thickness after drying was 30 μm, and then the solvent toluene was dried at 100° C. for 3 minutes, and the obtained adhesive film was adhered to a paper sheet to obtain a paper sheet medium.

[0786] The paper sheet was removed, and the total light transmittance of the transparent resin layer was measured in accordance with JIS K 7361-1:1997. The total light transmittance was 80% or more.

[0787] [Example 4-18]

[0788] <Titanium oxide>

[0789] As titanium oxide, amorphous rutile titanium oxide (particle size = 0.2 μm (measured value obtained by a laser diffraction / scattering particle size distribution analyzer), R780 manufactured by Ishihara Sangyo Co., Ltd.) was used.

[0790] <Preparation of coating solution>

[0791] 20 parts of the titanium oxide were added to 80 parts of the binder solution 1, and the mixture was stirred at 1000 rpm for 5 minutes using a homomixer to prepare a coating liquid.

[0792] <Formation of coating layer>

[0793] A printing medium was prepared in the same manner as in Example 4-1 except that the film described in Table 3 was used as a substrate and the coating was performed so that the coating amount of titanium oxide became the value described in Table 3.

[0794] <Formation of coating layer>

[0795] Polyethylene pellets (Novate (registered trademark) LC522 manufactured by Japanpolyethylene Corporation) were introduced into a twin-screw extruder (HMT100 manufactured by Hitachi Zosen Corporation) and melted at 320° C. Thereafter, the pellets were melt-laminated on a corona-treated paper sheet in such a manner that the thickness of the resin became 20 μm, and then rapidly cooled while being clamped by a cooling roll whose temperature was adjusted to 20° C., to obtain a sheet medium laminate having a laminated layer.

[0796] The paper sheet was removed, and the total light transmittance of the transparent resin layer was measured in accordance with JIS K 7361-1:1997. The total light transmittance was 80% or more.

[0797] [Comparative Example 4-2]

[0798] A printing area was provided on printing paper (KB39-7, manufactured by KOKUYO Co., Ltd.) using a portable inkjet printer (MOBILEJET MINI, manufactured by Yamazaki Sangyo Co., Ltd.). As the inkjet ink, water-absorbing raw material, manufactured by Yamazaki Sangyo Co., Ltd., was used.

[0799] [Comparative Example 4-3]

[0800] A printing area was provided on a thermal label (Lesprit general purpose thermal label manufactured by SATO HOLDINGS CORPORATION) using a thermal printer (Lesprit T8 manufactured by SATO HOLDINGS CORPORATION).

[0801] [Examples 5-1 to 5-15, Comparative Examples 5-1 to 5-5]

[0802] (Manufacturing of coating liquid)

[0803] As titanium oxide, R780 (particle size: 0.2 μm) manufactured by Ishihara Sangyo Co., Ltd. was used.

[0804] As the thermoplastic resin, an ethylene-acrylic acid-based adhesive (manufactured by Michelman Japan Co., Ltd., MP498345N, solid content concentration 50%) was used.

[0805] <Manufacturing of coating liquid 1>

[0806] 100 parts by mass of the titanium oxide and 200 parts by mass of the ethylene-acrylic acid-based binder (solid content concentration 50%) were mixed, and diluted with water so that the viscosity of the coating liquid was 20 seconds as measured by a Zahn cup No. 3, to prepare a coating liquid 1.

[0807] <Manufacturing of coating liquid 2>

[0808] 100 parts by mass of the titanium oxide and 2300 parts by mass of the ethylene-acrylic acid-based binder (solid content concentration 50%) were mixed, and diluted with water so that the viscosity of the coating liquid was 20 seconds as measured by a Zahn cup No. 3, to prepare a coating liquid 2.

[0809] <Production of coating liquid 3>

[0810] 100 parts by mass of the titanium oxide and 467 parts by mass of the ethylene-acrylic acid-based binder (solid content concentration 50%) were mixed, and diluted with water so that the viscosity of the coating liquid was 20 seconds as measured by a Zahn cup No. 3, to prepare a coating liquid 3.

[0811] <Production of coating liquid 4>

[0812] 100 parts by mass of the titanium oxide and 300 parts by mass of the ethylene-acrylic acid-based binder (solid content concentration 50%) were mixed, and diluted with water so that the viscosity of the coating liquid was 20 seconds as measured by a Zahn cup No. 3, to prepare a coating liquid 4.

[0813] <Manufacturing of coating liquid 5>

[0814] 100 parts by mass of the titanium oxide and 133 parts by mass of the ethylene-acrylic acid-based binder (solid content concentration 50%) were mixed, and diluted with water so that the viscosity of the coating liquid was 20 seconds as measured by a Zahn cup No. 3, to prepare a coating liquid 5.

[0815] <Production of coating liquid 6>

[0816] 100 parts by mass of the titanium oxide and 50 parts by mass of the ethylene-acrylic acid-based binder (solid content concentration 50%) were mixed, and diluted with water so that the viscosity of the coating liquid was 20 seconds as measured by a Zahn cup No. 3, to prepare a coating liquid 6.

[0817] (Production of Recording Medium)

[0818] The paper substrates listed in Table 3 were used as paper substrates, and the coating liquids listed in Table 3 were used to prepare coating layers in the amounts listed in Table 3.

[0819] For Examples 5 to 10, after forming the coating layer, a transparent resin layer was provided as follows.

[0820] Polyethylene pellets (Novate (registered trademark) LC522 manufactured by Japanpolyethylene Corporation) were introduced into a single screw extruder (50C150 manufactured by Toyo Seiki Seisaku-sho Co., Ltd.) and melted at 320° C. Thereafter, the resin was melt-laminated on the corona-treated coating layer so that the thickness of the resin became 20 μm, and then rapidly cooled while being sandwiched between cooling rolls adjusted to 20° C., thereby obtaining a recording medium having a laminated layer.

[0821] The paper substrate was removed, and the total light transmittance of the transparent resin layer was measured in accordance with JIS K 7361-1:1997. The total light transmittance was 80% or more.

[0822] For Examples 5 to 11, after forming the coating layer, a transparent resin layer was provided as follows.

[0823] An ethylene-acrylic acid-based adhesive (ethylene-acrylic acid copolymer ionomer, manufactured by Michelman, MP498345NS, solid content 50% by mass) was applied on the coating layer of the paper sheet using a gravure coater so that the resin thickness became 10 μm.

[0824] [Comparative Examples 5-6]

[0825] In Comparative Example 5-6, a laminate layer containing titanium oxide was formed on a paper substrate to produce a recording medium.

[0826] The following materials were used.

[0827] Polyethylene (PE): Novate (registered trademark) LC522 (manufactured by Japan Polyethylene Corporation)

[0828] Titanium oxide: particle size = 0.2 μm, manufactured by Ishihara Sangyo Co., Ltd., R780

[0829] The method of laminating the paper substrate and the laminating layer is as follows.

[0830] <Masterbatch production method>

[0831] According to Japanese Patent Application Laid-Open No. 2015-96568, the following steps were followed to produce the device.

[0832] 60 parts of resin and 40 parts of titanium oxide were mixed in a tumble mixer (TM-65S manufactured by EISHIN Co., Ltd.) at 45 rpm for 1 hour, and then melt-kneaded in a twin-screw extruder (TEX30XCT manufactured by Nippon Steel Works, Ltd., L / D=42) at a screw speed of 250 rpm and a barrel temperature of 280°C. The mixture was extruded into a strand, cooled in a water tank, and pelletized into columns with an average shaft diameter of 2.0 mm and an average shaft length of 3.0 mm using a pelletizer to obtain a masterbatch.

[0833] <Lamination method>

[0834] The above masterbatch and resin were added to a single-screw extruder (50C150, manufactured by Toyo Seiki Seisaku-sho, Ltd.) in such a manner that titanium oxide became 0.3% by mass, and the resin was melted at 320°C in such a manner that the thickness became as shown in the table, and layered on corona-treated paper 1, and then rapidly cooled while being clamped with a cooling roller whose temperature was adjusted to 20°C, to obtain a recording medium having a laminated layer.

[0835] [Comparative Examples 5-7]

[0836] Using the recording medium used in Example 5-2, a 10 mm square marking was performed using an infrared laser (MD-F3200 manufactured by Keyence Corporation). The irradiation conditions are as follows.

[0837] Wavelength: 1090nm

[0838] Repetition frequency: 60kHz

[0839] ·Spot diameter = 40μm

[0840] Scanning speed: 2000mm / sec

[0841] ·Focal distance: 300mm (focusing is performed using the height correction included with the device)

[0842] Line spacing: 200μm

[0843] Power: 3W

[0844] As a result, printing cannot be performed.

[0845] (Comparative Examples 5-8)

[0846] Using the paper sheet medium used in Example 5-2, a 10 mm square marking was performed using a green laser (MD-S9910A manufactured by Keyence Corporation). The irradiation conditions are as follows.

[0847] Wavelength: 532nm

[0848] Repetition frequency: 60kHz

[0849] ·Spot diameter = 40μm

[0850] Scanning speed: 2000mm / sec

[0851] ·Focal distance: 300mm (focusing is performed using the height correction included with the device)

[0852] Line spacing: 200μm

[0853] Power: 3W

[0854] As a result, printing cannot be performed.

[0855] (Comparative Examples 5-9)

[0856] Using the paper medium used in Example 5-2, a 10 mm square marking was performed using a CO2 laser (ML-Z9610 manufactured by Keyence Corporation). The irradiation conditions are as follows.

[0857] Wavelength: 10600nm

[0858] ·Spot diameter = 40μm

[0859] Scanning speed: 2000mm / sec

[0860] ·Focal distance: 300mm (focusing is performed using the height correction included with the device)

[0861] Line spacing: 200μm

[0862] Power: 3W

[0863] As a result, printing cannot be performed.

[0864] [Ultraviolet laser irradiation conditions-1]

[0865] Regarding Example 4 and Comparative Examples 4-1 and 4-2, the obtained sheet medium was subjected to ultraviolet laser (AVIA266-3000 manufactured by Coherent Corporation). Figure 1 The barcode shown was printed and a 10 mm square mark was printed. The irradiation conditions were as follows.

[0866] Wavelength: 355nm

[0867] Repetition frequency: 50kHz

[0868] Pulse amplitude: 25ns

[0869] Spot diameter: 104μm

[0870] Scanning speed: 4000mm / sec

[0871] Focus distance: 250mm

[0872] Line spacing: 150μm

[0873] In addition, the power is set to the value shown in Table 3.

[0874] [Ultraviolet laser irradiation conditions-2]

[0875] For Example 5 and Comparative Example 5, the obtained recording medium was marked with an ultraviolet laser (MD-U1020C manufactured by Keyence Corporation). Figure 1 The barcode shown is printed and is 10mm square.

[0876] The irradiation conditions are as follows.

[0877] Wavelength: 355nm

[0878] Repetition frequency: 40kHz

[0879] ·Spot diameter = 40μm

[0880] Scanning speed: 3000mm / sec

[0881] ·Focal distance: 300mm (focusing is performed using the height correction included with the device)

[0882] Line spacing: 40μm

[0883] In addition, the power is set to the value shown in Table 3.

[0884] [Measurement / Evaluation]

[0885] The properties of the pulp used were measured as follows.

[0886] 〔CSF〕

[0887] Canadian standard freeness (CSF) is measured according to JIS P 8121-2:2012.

[0888] 〔Whiteness〕

[0889] The whiteness of the pulp used was measured in accordance with JIS P 8212:1998.

[0890] In addition, the following evaluations were performed on the obtained recording medium (printing medium) or printed matter.

[0891] [Measurement of the length-weighted average fiber length, average fiber width, and ratio of the number of fine fibers]

[0892] The printing medium obtained in the examples and comparative examples was cut into 40 cm squares, immersed in ion exchange water, adjusted to a concentration of 2%, and then immersed for 24 hours. After immersion for 24 hours, a standard disintegrator (manufactured by Kumagai Riki Kogyo Co., Ltd.) was used to treat until the undisintegrated fibers disappeared, and the pulp was disintegrated into fibers. In the case of a transparent resin layer, the disintegrated slurry (dispersion of pulp fibers) after the transparent resin layer was removed was classified, and a fiber length measuring machine (model FS-5 with UHD base unit, manufactured by Valmet) was used to measure the "length load average fiber length (ISO)", "microfiber number ratio", and "average fiber width".

[0893] In addition, "length load average fiber length (ISO)" is the length-weighted average fiber length calculated by selecting fibers having a length of 0.2 mm or more and 7.6 mm or less.

[0894] The “microfiber number ratio” is the microfiber number ratio of microfibers having a fiber width of 75 μm or less and a length of 0.08 mm or more and 0.20 mm or less in the disintegrated pulp fibers.

[0895] The “average fiber width” is a length-load average fiber width calculated by selecting fibers having a width of 10 μm or more and 75 μm or less.

[0896] In addition, when only a small amount of paper sheet media can be secured, the pulp can be disintegrated into fibers using a manual disintegrator (Dasher, Valmet) that processes the paper sheet media by piston motion. The piston motion is continued until the undisintegrated fibers disappear. However, if the disintegration is not complete, the piston motion is set to 10,000 times as the upper limit, and the pulp slurry obtained thereafter is subjected to measurement.

[0897] 〔Weight per unit area, paper thickness〕

[0898] The mass per unit area of ​​the paper substrate used in Examples and Comparative Examples was measured in accordance with JIS P 8124: 2011. The thickness of the paper sheet media in Examples and Comparative Examples was measured in accordance with JIS P 8118:2014.

[0899] The obtained printed matter was evaluated as follows. The results are shown in Table 3 below.

[0900] 〔Raman spectrum-1〕

[0901] Regarding Example 4 and Comparative Examples 4-1 and 4-4, Raman spectra were measured by the following method: Raman spectra were measured for printed materials on which barcodes were printed.

[0902] <Measurement conditions>

[0903] The measurement conditions of Raman spectroscopy are as follows, but when damage is visible in the printed material under the laser used in the measurement, when the fluorescence is strong, etc., the following measurement conditions such as laser power and irradiation time can be appropriately changed. Among them, the Raman intensity of the printed area and the non-printed area adopts the value measured under the same conditions.

[0904] · Device: inVia Raman microscope QUONTOR manufactured by Renishaw

[0905] Excitation laser: 532nm

[0906] Laser power: 50mW (power 100%)

[0907] Laser power: 5%

[0908] ·Measurement mode: Confocal mode

[0909] ·Irradiation time: 2.0 seconds

[0910] Cumulative times: 10 times

[0911] Laser spot diameter: 2.5μm

[0912] Objective lens: 20 times

[0913] <Measurement method>

[0914] The measurement was performed by the following method.

[0915] (1) Using a standard sample (single crystal silicon, manufactured by Renishaw), the Raman shift position was calibrated (520.5 cm for single crystal silicon). -1 ).

[0916] (2) Place the sheet sample on the sample stand and, if necessary, set a clamp so that the sheet remains flat.

[0917] (3) Under the device, such as Figure 3Observe with the focus as shown (set so that the focus becomes the minimum under the simulated laser). When measuring the printed area, measure so that the darkest part that can be visually confirmed is close to the center of the guide plate displayed during measurement. When measuring the non-printed area, measure at a distance of 300μm or more from the printed area.

[0918] (4) The obtained Raman spectrum was subjected to baseline correction (smart correction) using the processing software (Wire 5.2 manufactured by Renishaw) included with the device. The baseline was corrected using polynomial 11 in the processing software.

[0919] (5) Reading 447±3cm for rutile titanium oxide -1 The maximum value (maximum intensity) of the wave number range is 516±3cm for anatase titanium oxide. -1 The maximum value (maximum intensity) of the wavenumber range is taken and the Raman intensity ratio is calculated according to the following formula.

[0920] Raman intensity ratio = maximum intensity of the printed area ÷ maximum intensity of the non-printed area

[0921] (6) 10 locations were measured in each of the printing area (printing portion) and the non-printing area (non-printing portion), and the average value was used as the measurement result.

[0922] 〔Raman Spectroscopy-2〕

[0923] Regarding Example 5 and Comparative Example 5, Raman spectra were measured by the following method.

[0924] <Measurement conditions and measurement methods>

[0925] The measurement conditions and method of Raman spectroscopy are as described above. However, when damage is visible in the printed material under the laser used in the measurement, when the fluorescence is strong, the following measurement conditions such as laser power and irradiation time can be appropriately changed. Among them, the Raman intensity of the printed area and the non-printed area adopts the value measured under the same conditions.

[0926] From the viewpoint of suppressing fluctuations in the measured value, it is preferred to measure within a range where the count of the Raman intensity in the printed area is 10,000 or less. Therefore, the measurement conditions are appropriately changed and the measurement is performed so that the count of the Raman intensity in the printed area is within a range of 10,000 or less. In addition, the measurement is performed 10 times under the following measurement conditions, and the values ​​deviating by more than the mean value ± 2SD (standard deviation) are excluded, and the average is again taken as the average value of the Raman intensity.

[0927] 〔Print clarity〕

[0928] The print clarity of the obtained printed matter (barcode printing) was evaluated according to the following evaluation criteria.

[0929] A color close to the printed color was selected visually using the Munsell table (a color specification produced by Japan Color Research Co., Ltd.), and the clarity was evaluated based on the following criteria.

[0930] A: Brightness is 4 or less in the Munsell scale (no color)

[0931] B: Brightness in the Munsell scale (no color) is 5 to 6

[0932] C: Brightness 7 to 8 in the Munsell scale (no color)

[0933] D: Brightness is 9 or above in the Munsell scale (no color)

[0934] [Solvent resistance]

[0935] The solvent resistance of the obtained printed matter was evaluated according to the following evaluation criteria.

[0936] The printed material was immersed in 100% acetone (manufactured by Kanto Chemical Co., Ltd.) and allowed to stand for 15 minutes. The printed material was then taken out, the solvent was wiped off with tissue paper, and the solvent resistance was visually evaluated according to the following evaluation criteria.

[0937] A: No blurring or falling off of the print was observed before and after immersion (no change).

[0938] B: Blurring and peeling of the printing were visible before and after immersion.

[0939] 〔Uneven printing〕

[0940] Using the 10 mm squares printed in the Examples and Comparative Examples, printing unevenness was visually evaluated according to the following evaluation criteria.

[0941] A: Print unevenness is 0

[0942] B: There are more than 1 and less than 3 printing unevenness

[0943] C: There are more than 4 and less than 5 places where printing is uneven

[0944] D: There are more than 6 and less than 10 places of uneven printing

[0945] E: There are more than 11 uneven prints

[0946] 〔Smoke output〕

[0947] The amount of smoke generated when a square of 10 mm square was marked by irradiation with ultraviolet laser was evaluated by the following method.

[0948] <Judgment Criteria>

[0949] 0: No smoke can be visually detected

[0950] 1: Slight smoke can be observed visually, but the amount of smoke is very small

[0951] 2: Smoke can be visually confirmed, but the amount of smoke is small.

[0952] 3: The smoke can be easily confirmed by visual inspection, and the amount of smoke is large

[0953] [Content of titanium oxide in coating layer]

[0954] 1. When the printing medium contains a non-printable area

[0955] <Preparation of test pieces>

[0956] The printable area and the non-printable area (area without a coating layer) of the print medium were cut into appropriate sizes to prepare samples (test pieces), and the cut areas were recorded.

[0957] <Dissolution of test piece>

[0958] A mixed solvent of nitric acid: hydrofluoric acid = 50:5 (volume %) and a test piece were placed in a Teflon (registered trademark) container of an autoclave apparatus (manufactured by CEM Japan, MARS5), and the autoclave treatment was performed at 210°C for 120 minutes to dissolve the test piece. The area of ​​the test piece can be appropriately changed, and when the test piece is dissolved and remains, the ratio of nitric acid and hydrofluoric acid, the treatment temperature, the treatment time, etc. can be appropriately changed.

[0959] After the test piece is dissolved, the volume is accurately adjusted with ultrapure water.

[0960] <Measurement of the amount of titanium oxide in a solution>

[0961] (1) The ICP apparatus and measurement conditions are as follows.

[0962] ICP apparatus: ICP-OEC apparatus (manufactured by Rigaku Corporation, CIROS1-20)

[0963] Determination conditions:

[0964] Carrier gas: Argon

[0965] Argon gas flow rate 0.9L / min

[0966] Plasma gas flow rate 14L / min

[0967] Plasma power 1400W

[0968] Pump speed: 2

[0969] ·Measurement wavelength Ti: 334.941nm

[0970] (2) Preparation of standard curve

[0971] A universal mixed standard solution (manufactured by SPEX, XSTC-622B) was accurately measured to have the following concentrations, and subjected to measurement under the above-mentioned measurement conditions to measure the intensity at 334.941 nm corresponding to the emission wavelength of titanium atoms.

[0972] ·Concentrations for standard curve preparation: 0ppm, 0.01ppm, 0.05ppm, 0.1ppm, 0.5ppm, 1.0ppm, 3.0ppm, 5.0ppm

[0973] (3) Determination of titanium oxide content in the solution

[0974] The solution in which the test piece was dissolved was diluted with ultrapure water so as to fall within the above-mentioned standard curve, and subjected to ICP measurement.

[0975] (4) Calculation method of titanium oxide content

[0976] The titanium oxide content was calculated by the following formula: It should be noted that the molecular weight of titanium oxide ÷ the molecular weight of titanium ≈ 1.669.

[0977] Titanium oxide content (g / m 2 )=ICP determination concentration (ppm)×dilution ratio×fixed volume (L)×1.669×1000÷area (m 2 )

[0978] The titanium oxide content in the coating layer was determined by subtracting the titanium oxide content in the non-printable region from the titanium oxide content in the printable region.

[0979] 2. The printing medium does not contain non-printable areas

[0980] <Preparation of test pieces>

[0981] Two recording media were cut into appropriate sizes, and the cut areas were recorded.

[0982] One of the cut test pieces was ground using a grinding machine (manufactured by Sagawa Seisakusho Co., Ltd., grinding stone size ), only the coating layer (coating layer) was cut off and removed as a reference sample.

[0983] It is suitable to observe the cross section using an electron microscope so as not to over-cut excessively.

[0984] <Subsequent processing>

[0985] The same treatment as 1. was carried out, and the difference between the titanium oxide contents of the two sheets was taken as the titanium oxide content of the coating layer.

[0986] 〔Titanium oxide particle size〕

[0987] The particle size of titanium oxide contained in the coating layer is calculated from an SEM image obtained by a scanning electron microscope (SEM, manufactured by Hitachi High-Technologies Corporation, S5200, etc.) of ash obtained by burning a recording medium or a printed matter in a muffle furnace.

[0988] Specifically, when the substrate does not contain titanium oxide, the ash content is obtained under the same conditions as in the measurement of the above-mentioned "Titanium oxide content".

[0989] The sample of ash content tested in scanning electron microscope is made as follows: applied to an ultrasonic homogenizer (Yamato Scientific Co., Ltd. system, LUH150, etc.) with a power of 50W for 5 minutes, dispersed in ion exchange water, and after obtaining 0.01% by mass slurry, 0.1mL is cast on an aluminum dish and dried at 60°C to make it. The particles that can be clearly distinguished from the adjacent particles are visually selected, and the major diameter of one particle is used as the particle size. At this time, even if the primary particles are mixed with the secondary particles in the aggregated state and can be clearly distinguished, they are counted as one particle respectively, and the average diameter of 100 randomly selected particles is used as the particle size. The magnification during SEM image observation is appropriately selected according to the particle size of titanium oxide, and is set to about 20,000 times. In addition, in the case of particles other than titanium oxide, the energy dispersive X-ray analyzer attached to SEM (manufactured by Horiba, Ltd., EMAX, etc.) is used to measure the particles containing titanium element.

[0990] In the case of needle-shaped particles, the average diameter of the short diameter of 100 particles whose long diameters were measured was taken as the short diameter.

[0991] In addition, in the case of paper whose substrate contains titanium oxide, the coating layer is transferred to a transparent adhesive tape (manufactured by 3M Co., Ltd., 309SN) that does not contain titanium oxide or inorganic pigments to prepare an ash sample. Specifically, a belt crimping roller with a roller mass of 2 kg (manufactured by Yasuda Seiki Co., Ltd., No. 349, etc.) is used to adhere the adhesive tape to the upper layer of the coating layer. After that, after being immersed in a copper ethylenediamine solution (manufactured by Merck) for measuring cellulose viscosity for 24 hours, the adhesive tape containing the coating layer is thoroughly cleaned with ion exchange water. Wipe off the moisture of the obtained adhesive tape containing the coating layer and dry it in a dryer at 60°C for 1 hour. After that, it is burned in a muffle furnace at 525°C to prepare ash for measuring the particle size, and the major and minor diameters are measured in the same way as above.

[0992] In the case of a film containing titanium oxide on the substrate, the coating layer is transferred to a transparent adhesive tape (3M Co., Ltd., 309SN) that does not contain titanium oxide to prepare an ash sample. Specifically, a 2kg belt pressure roller (Yasuda Seiki Co., Ltd., No. 349, etc.) is used to adhere the adhesive tape to the upper layer of the coating layer, and the adhesive tape is peeled off from the film after adhesion to move the coating layer. After that, it is burned in a muffle furnace at 525°C to prepare ash for particle size measurement, and the major and minor diameters are measured in the same way as above.

[0993] 〔Thickness of coating layer〕

[0994] The thickness of the coating layer was measured based on image data obtained by a scanning electron microscope.

[0995] (1) Preparation of measurement samples

[0996] The sample was embedded in a photocurable resin (Toagosei Co., Ltd., D-800), and the cross section of the printed medium was exposed using an ultramicrotome. A diamond knife was used for cutting at room temperature.

[0997] The cut cross section was subjected to gold vapor deposition to a thickness of about 20 nm and then measured using a scanning electron microscope.

[0998] (2) Measurement equipment / conditions

[0999] Measuring device: S-3600 (manufactured by Hitachi High-Technologies Corporation)

[1000] Measurement conditions: magnification 2000 times,

[1001] The type of scanning microscope is not limited to the above, but a type that displays a scale is used.

[1002] (3) Measurement method

[1003] Using the energy dispersive X-ray spectrometer attached to the scanning electron microscope, after confirming that the observed coating contains titanium, image data is obtained at a magnification of 2000 times. After printing the obtained image data on printing paper, the thickness of the coating layer of the object (the length of the boundary from the boundary with other layers) is measured with a ruler, and the actual thickness of the coating layer is measured by comparing with the scale. Image data of 5 parts randomly selected from a sample in one measurement is obtained, and the thickness of the thickest and thinnest parts of the coating layer is measured from the image data of one part, and the average of a total of 10 parts is taken as the thickness of the coating layer.

[1004] [Table 3-1]

[1005] Table 3-1

[1006]

[1007] [Table 3-2]

[1008] Table 3-2

[1009]

[1010] *: In Examples 4-17 and 4-18, a printing medium having a transparent resin layer is used.

[1011] [Table 3-3]

[1012] Table 3-3

[1013]

[1014] *: Use printing media with a transparent resin layer on the coating layer

[1015] [Table 3-4]

[1016] Table 3-4

[1017]

[1018] According to the results in Table 3, the titanium oxide content was 0.6 g / m 2 Above and 30g / m 2 The following is a recording medium with a coating layer having A / B in a specific range, and printing is performed by ultraviolet laser in a manner such that the ratio of the Raman intensity of the printing area to the non-printing area is 0.7 or less, thereby obtaining a print having a clear (excellent visibility) and excellent solvent resistance. In addition, in this case, uneven printing is suppressed, and the amount of smoke generated when irradiating the ultraviolet laser is suppressed.

[1019] On the other hand, the content of titanium oxide is less than 0.6 g / m 2 In Comparative Examples 4-1 and 5-2, no clear image was obtained. The content of titanium oxide exceeded 30 g / m 2 In Comparative Example 5-1, uneven printing occurred and a large amount of smoke was generated. In addition, the printed matter obtained by conventional inkjet printing and thermal labels had poor solvent resistance. Furthermore, in Comparative Example 4-4, in which the Raman intensity ratio exceeded 0.7, sufficient print clarity was not obtained.

[1020] In Comparative Example 5-3, where the length-weighted average fiber length of the paper substrate exceeded 3.5 mm, and in Comparative Example 5-4, where the length-weighted average fiber length of the paper substrate was less than 0.6 mm, uneven printing occurred. In Comparative Example 5-5, where A / B exceeded 2.00, uneven printing occurred and the amount of smoke was large. Furthermore, in Comparative Example 5-6, which was laminated, sufficient print clarity was not obtained.

[1021] Furthermore, as shown in Comparative Examples 5-7 to 5-9, printing could not be performed under irradiation with infrared laser, green laser and CO 2 laser.

[1022] Example 6 and Example 7

[1023] [Material]

[1024] Various materials used in Examples are as follows.

[1025] 〔Paper base〕

[1026] Paper substrate A: bleached cowhide, mass per unit area = 70 g / m 2 , Paper thickness = 110 μm (manufactured by Oji Materia Co., Ltd.)

[1027] Paper substrate B: corrugated paper liner, mass per unit area = 280 g / m 2 , Paper thickness = 326 μm, LB grade (manufactured by OjiMateria Co., Ltd.)

[1028] Paper substrate C: produced according to the following procedure.

[1029] <Method for producing paper substrate C>

[1030] Hardwood bleached kraft pulp (LBKP, brightness 84%) was beaten to a CSF of 400 mL to prepare a 3 mass % suspension.

[1031] Conifer kraft pulp (NBKP, brightness 84%) was beaten to a CSF of 700 mL to prepare a 3 mass % suspension.

[1032] Then, the pulp was mixed at a ratio of LBKP:NBKP=65:35, and 0.5 parts by mass of aluminum sulfate was added to 100 parts by mass of the pulp to dilute it. Then, 0.8 parts by mass of polyepichlorohydrin-based paper wet strength agent WS4024 (produced by Seiko PMC Co., Ltd.) was added to 100 parts by mass of the pulp, and the mixture was formed into a sheet with a weight of 70 g / m2 in a wet paper machine. 2 and a paper substrate having a thickness of 86 μm.

[1033] Paper substrate D: prepared according to the following steps.

[1034] <Method for producing paper substrate D>

[1035] Hardwood bleached kraft pulp (LBKP) was beaten to a CSF of 400 mL to prepare a 3% suspension. 0.5 parts by mass of aluminum sulfate was added to 100 parts by mass of the pulp to dilute it, and 0.8 parts by mass of polyepichlorohydrin-based paper wet strength agent WS4024 (produced by Seiko PMC Co., Ltd.) was added to 100 parts by mass of the pulp, and the mixture was formed into a sheet with a wet paper machine to produce a sheet with a unit area weight of 30 g / m 2 and a paper substrate having a thickness of 42 μm.

[1036] 〔Resin〕

[1037] Polyethylene (PE): Novate (registered trademark) LC522 (manufactured by Japan Polyethylene Corporation)

[1038] Polypropylene (PP): PH943B (manufactured by SunAllomer Ltd.)

[1039] Polylactic acid (PLA): REVODE190 (manufactured by Zhejiang Hisun Biomaterials Co., Ltd.)

[1040] · Polyethylene terephthalate (PET): UNITIKA LTD., SA-8339P

[1041] Polybutylene succinate (PBS): ZM9B02 (manufactured by Mitsubishi Chemical Corporation)

[1042] 〔Titanium oxide〕

[1043] Amorphous, average particle size = 0.2 μm (measured value obtained by a laser diffraction / scattering particle size distribution analyzer), rutile type: R780 (manufactured by Ishihara Sangyo Co., Ltd.)

[1044] Amorphous, average particle size = 4.3 μm (measured value obtained by a laser diffraction / scattering particle size distribution analyzer), rutile type: PER410 (manufactured by Ishihara Sangyo Co., Ltd.)

[1045] Needle-shaped, long diameter = 1.7 μm, short diameter = 0.1 μm, rutile type: FTL100 (manufactured by Ishihara Sangyo Co., Ltd.)

[1046] Needle-shaped, long diameter = 10 μm, short diameter = 0.5 μm, rutile type: FTL400 (manufactured by Ishihara Sangyo Co., Ltd.)

[1047] Amorphous, average particle size = 0.2 μm (measured value obtained by a laser diffraction / scattering particle size distribution analyzer), anatase type: A100 (manufactured by Ishihara Sangyo Co., Ltd.)

[1048] [Examples 6-1 to 6-16, Comparative Examples 6-3 to 6-4, Examples 7-1 to 7-11, Comparative Examples 7-1, 7-2, 7-4, 7-5]

[1049] The method of laminating the base material and the laminating layer is as follows.

[1050] <Masterbatch production method>

[1051] According to Japanese Patent Application Laid-Open No. 2015-96568, the following steps were followed to produce the device.

[1052] 60 parts of resin and 40 parts of titanium oxide were mixed in a tumble mixer (TM-65S manufactured by EISHIN Co., Ltd.) at 45 rpm for 1 hour, and then melt-kneaded in a twin-screw extruder (TEX30XCT manufactured by Nippon Steel Works, Ltd., L / D=42) at a screw speed of 250 rpm and a barrel temperature of 280°C. The mixture was extruded into a strand, cooled in a water tank, and pelletized into columns with an average shaft diameter of 2.0 mm and an average shaft length of 3.0 mm using a pelletizer to obtain a masterbatch.

[1053] <Lamination method>

[1054] The above-mentioned masterbatch and resin are fed into a single-screw extruder (50C150, manufactured by Toyo Seiki Seisaku-sho, Ltd.) in such a manner that the titanium oxide becomes the ratio as shown in Table 4, and after melt-laminated on the corona-treated paper substrate described in Table 4 in such a manner that the resin thickness becomes as shown in Table 4, it is rapidly cooled while being clamped with a cooling roller whose temperature is adjusted to 20°C, to obtain a sheet medium having a laminated layer.

[1055] In addition, the resins were melted at the following temperatures.

[1056] Polyethylene: 320℃

[1057] Polypropylene: 300°C

[1058] PET: 300℃

[1059] Polylactic acid: 230℃

[1060] PBS: 250°C

[1061] Comparative Example 7-3

[1062] 4.3 parts of titanium oxide (R780 manufactured by Ishihara Sangyo, rutile titanium oxide, amorphous, average particle size = 0.27 μm) and 100 parts of ethylene-acrylic acid type binder (ethylene-acrylic acid copolymer ionomer, Michelman, MP498345N.S, solid content 50% by mass) were mixed, and stirred for 5 minutes using a homomixer (HOMODISPER 2.5 manufactured by Primix) to prepare a coating liquid with a solid content concentration of 8% by mass.

[1063] The coating liquid was applied on a paper substrate using a gravure coater so that the content of titanium oxide became the value shown in the table, and then dried.

[1064] Comparative Example 7-6

[1065] Using the paper medium used in Example 7-5, a 10 mm square mark was made using an infrared laser (MD-F3200 manufactured by Keyence Corporation). The irradiation conditions were as follows:

[1066] Wavelength: 1090nm

[1067] Repetition frequency: 60kHz

[1068] Scanning speed: 2000mm / sec

[1069] ·Focal distance: 300mm (focusing is performed using the height correction included with the device)

[1070] Line spacing: 200μm

[1071] Power: 3W

[1072] As a result, printing cannot be performed.

[1073] (Comparative Example 7-7)

[1074] Using the paper sheet medium used in Example 7-5, a 10 mm square marking was performed using a green laser (MD-S9910A manufactured by Keyence Corporation). The irradiation conditions are as follows.

[1075] Wavelength: 532nm

[1076] Repetition frequency: 60kHz

[1077] ·Spot diameter = 40μm

[1078] Scanning speed: 2000mm / sec

[1079] ·Focal distance: 300mm (focusing is performed using the height correction included with the device)

[1080] Line spacing: 200μm

[1081] Power: 3W

[1082] As a result, printing cannot be performed.

[1083] (Comparative Examples 7-8)

[1084] Using the paper medium used in Example 7-5, a 10 mm square marking was performed using a CO2 laser (ML-Z9610 manufactured by Keyence Corporation). The irradiation conditions are as follows.

[1085] Wavelength: 10600nm

[1086] ·Spot diameter = 40μm

[1087] Scanning speed: 2000mm / sec

[1088] ·Focal distance: 300mm (focusing is performed using the height correction included with the device)

[1089] Line spacing: 200μm

[1090] Power: 3W

[1091] As a result, printing cannot be performed.

[1092] [Ultraviolet laser irradiation conditions-1]

[1093] For Example 6 and Comparative Example 6, the obtained sheet medium was subjected to ultraviolet laser (AVIA266-3000 manufactured by Coherent Corporation). Figure 1 The barcode shown was printed, or a 10 mm square mark was made. The irradiation conditions were as follows.

[1094] Wavelength: 355nm

[1095] Repetition frequency: 50kHz

[1096] Pulse amplitude: 25ns

[1097] Spot diameter: 104μm

[1098] Scanning speed: 4000mm / sec

[1099] Focus distance: 250mm

[1100] Line spacing: 150μm

[1101] In addition, the power is set to the value shown in Table 4.

[1102] [Ultraviolet laser irradiation conditions-2]

[1103] For Example 7 and Comparative Example 7, the obtained recording media were marked using an ultraviolet laser (MD-U1020C manufactured by Keyence Corporation). Figure 1 Printing of barcode as shown, or 10mm square.

[1104] The irradiation conditions are as follows.

[1105] Wavelength: 355nm

[1106] Repetition frequency: 40kHz

[1107] ·Spot diameter = 40μm

[1108] Scanning speed: 2000mm / sec

[1109] ·Focal distance: 300mm (focusing is performed using the height correction included with the device)

[1110] Line spacing: 40μm

[1111] In addition, the power is set to the value shown in Table 4.

[1112] [Comparative Example 6-1]

[1113] A printing area was provided on printing paper (KB39-7 manufactured by KOKUYO Co., Ltd.) using a portable inkjet printer (MOBILEJET MINI manufactured by Yamazaki Sangyo Co., Ltd.).

[1114] As the inkjet ink, an ink for water-absorbing raw materials (manufactured by Yamazaki Sangyo Co., Ltd.) was used.

[1115] [Comparative Example 6-2]

[1116] A printing area was provided on a thermal label (Lesprit general purpose thermal label manufactured by SATO HOLDINGS CORPORATION) using a thermal printer (Lesprit T8 manufactured by SATO HOLDINGS CORPORATION).

[1117] [Measurement / Evaluation]

[1118] The properties of the pulp used were measured as follows.

[1119] 〔CSF〕

[1120] Canadian standard freeness (CSF) is measured according to JIS P 8121-2:2012.

[1121] 〔Whiteness〕

[1122] The whiteness of the pulp used was measured in accordance with JIS P 8212:1998.

[1123] The obtained printed materials were evaluated as follows.

[1124] 〔Raman spectrum-1〕

[1125] Regarding Example 6 and Comparative Example 6, Raman spectra were measured by the following method.

[1126] <Measurement conditions>

[1127] The measurement conditions of Raman spectroscopy are as follows, but when damage is visible in the printed material under the laser used in the measurement, when the fluorescence is strong, etc., the following measurement conditions such as laser power and irradiation time can be appropriately changed. Among them, the Raman intensity of the printed area and the non-printed area adopts the value measured under the same conditions.

[1128] · Device: inVia Raman microscope QUONTOR manufactured by Renishaw

[1129] Excitation laser: 532nm

[1130] Laser power: 50mW (power 100%)

[1131] Laser power: 5%

[1132] ·Measurement mode: Confocal mode

[1133] ·Irradiation time: 2.0 seconds

[1134] Cumulative times: 10 times

[1135] Laser spot diameter: 2.5μm

[1136] Objective lens: 20 times

[1137] <Measurement method>

[1138] The measurement was performed by the following method.

[1139] (1) Using a standard sample (single crystal silicon, manufactured by Renishaw), the Raman shift position was calibrated (520.5 cm for single crystal silicon). -1 ).

[1140] (2) Place the sheet sample on the sample stand and, if necessary, set a clamp so that the sheet remains flat.

[1141] (3) Under the device, such as Figure 4As shown, observe with the focus on (set so that the focus becomes the minimum under the simulated laser). When measuring the printed area, measure so that the darkest part that can be visually confirmed is close to the center of the guide plate displayed during measurement. When measuring the non-printed area, measure at a distance of 300μm or more from the printed area.

[1142] (4) The obtained Raman spectrum was subjected to baseline correction (smart correction) using the processing software (Wire 5.2 manufactured by Renishaw) attached to the device. The baseline was corrected using polynomial 11 of the processing software.

[1143] (5) Reading 447±3cm for rutile titanium oxide -1 The maximum value (maximum intensity) of the wave number range is 516±3cm for anatase titanium oxide. -1 The maximum value (maximum intensity) of the wavenumber range is taken and the Raman intensity ratio is calculated according to the following formula.

[1144] Raman intensity ratio = maximum intensity of the printed area ÷ maximum intensity of the non-printed area

[1145] (6) 10 locations were measured in each of the printing area (printing portion) and the non-printing area (non-printing portion), and the average value was used as the measurement result.

[1146] 〔Raman Spectroscopy-2〕

[1147] Regarding Example 7 and Comparative Example 7, Raman spectra were measured by the following method.

[1148] <Measurement conditions and measurement methods>

[1149] The measurement conditions and method of Raman spectroscopy are as described above. However, when damage is visible in the printed material under the laser used in the measurement, when the fluorescence is strong, the following measurement conditions such as laser power and irradiation time can be appropriately changed. Among them, the Raman intensity of the printed area and the non-printed area adopts the value measured under the same conditions.

[1150] From the viewpoint of suppressing fluctuations in the measured value, it is preferred to measure within a range where the count of the Raman intensity in the printed area is 10,000 or less. Therefore, the measurement conditions are appropriately changed and the measurement is performed so that the count of the Raman intensity in the printed area is within a range of 10,000 or less. In addition, the measurement is performed 10 times under the following measurement conditions, and the values ​​deviating by more than the mean value ± 2SD (standard deviation) are excluded, and the average is again taken as the average value of the Raman intensity.

[1151] 〔Print clarity〕

[1152] The print clarity of the obtained printed matter was evaluated based on the following evaluation criteria.

[1153] A color close to the printed color was selected visually using the Munsell table (a color specification produced by Japan Color Research Co., Ltd.), and the clarity was evaluated based on the following criteria.

[1154] A: Brightness is 4 or less in the Munsell scale (no color)

[1155] B: Brightness in the Munsell scale (no color) is 5 to 6

[1156] C: Brightness 7 to 8 in the Munsell scale (no color)

[1157] D: Brightness is 9 or above in the Munsell scale (no color)

[1158] [Solvent resistance]

[1159] The solvent resistance of the obtained printed matter was evaluated according to the following evaluation criteria.

[1160] The printed material was immersed in 100% acetone (manufactured by Kanto Chemical) and allowed to stand for 15 minutes. The printed material was then taken out, the solvent was wiped off with tissue paper, and the solvent resistance was visually evaluated according to the following evaluation criteria.

[1161] A: No blurring or falling off of the print was observed before and after immersion (no change).

[1162] B: Blurring and peeling of the printing were visible before and after immersion.

[1163] [Decrease rate of tensile strength and elongation at break]

[1164] The deterioration (decreasing rate) of tensile strength and elongation at break were evaluated by the following method.

[1165] The obtained recording medium was marked in a 15 cm square using an ultraviolet laser (MD-U1020C manufactured by Keyence Corporation).

[1166] The irradiation conditions are as follows.

[1167] Wavelength: 355nm

[1168] Repetition frequency: 40kHz

[1169] ·Spot diameter = 40μm

[1170] Scanning speed: 3000mm / sec

[1171] ·Focal distance: 300mm (focusing is performed using the height correction included with the device)

[1172] Line spacing: 40μm

[1173] Power: 80% (2W) (2.5W at 100% power)

[1174] Then, a strip having a width of 15 mm and a length of 150 mm was taken out so that the longitudinal direction of the paper became the length, and subjected to a tensile test. The tensile strength and elongation at break were measured in accordance with JIS P 8113:2006.

[1175] The test was similarly conducted before laser printing, and the decrease rates of tensile strength and elongation at break were calculated as follows.

[1176] Tensile strength reduction rate = 100-(tensile strength after printing ÷ tensile strength before printing × 100)

[1177] Decrease rate of elongation at break = 100-(elongation at break after printing ÷ elongation at break before printing × 100)

[1178] <Judgment Criteria>

[1179] 0: The decline rate is 0% or more and 1% or less

[1180] 1: The decline rate is more than 1% and less than 5%

[1181] 2: The decline rate is more than 5% and less than 10%

[1182] 3: The decline rate is more than 10% and less than 15%

[1183] 4: The decline rate is more than 15% and less than 20%

[1184] 〔Smoke output〕

[1185] The smoke emission when marking a 10 mm square was measured in the following manner.

[1186] <Judgment Criteria>

[1187] 0: No smoke can be visually detected

[1188] 1: Slight smoke can be observed visually, but the amount of smoke is very small

[1189] 2: Smoke can be visually confirmed, but the amount of smoke is small

[1190] 3: The smoke can be easily confirmed by visual inspection, and the amount of smoke is large

[1191] 〔Titanium oxide content〕

[1192] <Pretreatment>

[1193] The paper substrate was pre-treated to separate the laminate layer from the paper substrate. After the printable area cut into an appropriate size was immersed in a copper ethylenediamine solution (manufactured by Merck) for cellulose viscosity measurement for 3 hours, the laminate layer was peeled off from the paper substrate and thoroughly washed with ion exchange water. After that, the moisture of the laminate layer was wiped off and dried in a dryer at 60°C for 1 hour to obtain a laminate layer to be measured.

[1194] The test piece was cut out so that its area could be calculated, and the calculated area was used in the equation described later.

[1195] <Preparation of test pieces>

[1196] The printable area of ​​the pretreated laminate layer and the print medium was cut into appropriate sizes as samples (test pieces), and the cut area and mass were recorded.

[1197] <Dissolution of test piece>

[1198] A mixed solvent of nitric acid: hydrofluoric acid = 50:5 (volume %) and a test piece were placed in a Teflon (registered trademark) container of an autoclave apparatus (manufactured by CEM Japan, MARS5), and the autoclave treatment was performed at 210°C for 120 minutes to dissolve the test piece. The mass of the test piece can be appropriately changed, and when the test piece remains after dissolution, the ratio of nitric acid to hydrofluoric acid, the treatment temperature, the treatment time, etc. can be appropriately changed.

[1199] After the test piece is dissolved, the volume is accurately adjusted with ultrapure water.

[1200] <Measurement of the amount of titanium oxide in a solution>

[1201] (1) The ICP apparatus and measurement conditions are as follows.

[1202] ICP apparatus: ICP-OEC apparatus (manufactured by Rigaku Corporation, CIROS1-20)

[1203] Determination conditions:

[1204] Carrier gas: Argon

[1205] Argon gas flow rate 0.9L / min

[1206] Plasma gas flow rate 14L / min

[1207] Plasma power 1400W

[1208] Pump speed: 2

[1209] ·Measurement wavelength Ti: 334.941nm

[1210] (2) Preparation of standard curve

[1211] A universal mixed standard solution (manufactured by SPEX, XSTC-622B) was accurately measured to have the following concentrations, and subjected to measurement under the above-mentioned measurement conditions to measure the intensity at 334.941 nm corresponding to the emission wavelength of titanium base paper.

[1212] ·Concentrations for standard curve preparation: 0ppm, 0.01ppm, 0.05ppm, 0.1ppm, 0.5ppm, 1.0ppm, 3.0ppm, 5.0ppm

[1213] (3) Determination of titanium oxide content in the solution

[1214] The solution in which the test piece was dissolved was diluted with ultrapure water so as to fall within the above-mentioned standard curve, and subjected to ICP measurement.

[1215] (4) Calculation method of titanium oxide content

[1216] The titanium oxide content was calculated by the following formula: It should be noted that the molecular weight of titanium oxide ÷ the molecular weight of titanium ≈ 1.669.

[1217] Titanium oxide content (g / m 2 )=ICP determination concentration (ppm)×dilution ratio×fixed volume (L)×1.669×1000÷area (m 2 )

[1218] Titanium oxide content (mass %) = ICP measurement concentration (ppm) × dilution ratio × fixed volume (L) × 1.669 ÷ test piece mass (mg) × 100

[1219] 〔Titanium oxide particle size〕

[1220] The particle size of titanium oxide added to paper and film is calculated from an SEM image obtained by a scanning electron microscope (SEM, manufactured by Hitachi High-Technologies Corporation, S5200, etc.) of ash obtained by burning a sheet medium or printed matter in a muffle furnace.

[1221] Specifically, the ash content was obtained under the same conditions as in the measurement of the above-mentioned "Titanium oxide content".

[1222] The sample of ash content tested in scanning electron microscope is made as follows: applied to an ultrasonic homogenizer (Yamato Scientific Co., Ltd. system, LUH150, etc.) with a power of 50W for 5 minutes, and dispersed in ethanol to obtain 0.01% by mass slurry, 0.1mL is cast into an aluminum dish, and after drying at 60°C, the aluminum dish is cut into a suitable size for testing in SEM to make. Visually select those that can be clearly distinguished from adjacent particles, and use the major diameter of one particle as the particle size. At this time, even if the primary particles are mixed with the secondary particles in the aggregated state and can be clearly distinguished, they are counted as one particle respectively, and the average diameter of 100 randomly selected particles is used as the particle size. The magnification during SEM image observation is appropriately selected according to the particle size of titanium oxide, and is set to about 20,000 times.

[1223] In the case of needle-shaped particles, the average diameter of the short diameter of 100 particles whose long diameters were measured was taken as the short diameter.

[1224] When particles other than titanium oxide are included, particles containing titanium element are measured using an energy dispersive X-ray analyzer attached to a SEM (manufactured by Horiba, Ltd., EMAX, etc.).

[1225] [Measurement of thickness of laminated layer]

[1226] The thickness of the laminate layer was measured based on image data obtained by a scanning electron microscope.

[1227] (1) Preparation of measurement samples

[1228] The sample was embedded in a photocurable resin (D-800 manufactured by Toagosei Co., Ltd.), and the cross section of the sheet substrate was exposed using an ultramicrotome. A diamond knife was used for cutting at room temperature.

[1229] The cut cross section was subjected to gold vapor deposition to a thickness of about 20 nm and then measured using a scanning electron microscope.

[1230] (2) Measurement equipment / conditions

[1231] Measuring device: S-3600 (manufactured by Hitachi High-Technologies Corporation)

[1232] Measurement conditions: magnification 2000 times,

[1233] The type of scanning microscope is not limited to the above, but a type that displays a scale is used.

[1234] (3) Measurement method

[1235] Using an energy dispersive X-ray spectrometer attached to a scanning electron microscope, after confirming that the observed laminate contains titanium, image data is obtained at a magnification of 2000 times. After printing the obtained image data on printing paper, the thickness of the laminate of the object (the length of the boundary with other layers) is measured with a ruler, and the actual thickness of the laminate is measured by comparing with the scale. Image data of 5 randomly selected parts of the sample from one measurement is obtained, and the thickness of 10 randomly selected parts from the image data of one part is measured, and the average of the total 50 parts is taken as the layer thickness of the laminate.

[1236] [Measurement of mass per unit area of ​​sheet media]

[1237] The mass per unit area of ​​the sheet medium is measured by the method described in JIS P 8124:2011.

[1238] [Measurement of the thickness of sheet media]

[1239] The mass per unit area of ​​the sheet medium is measured by the method described in JIS P 8118:2014.

[1240] [Table 4-1]

[1241] Table 4-1

[1242]

[1243] [Table 4-2]

[1244] Table 4-2

[1245]

[1246] [Table 4-3]

[1247]

[1248] As shown in Table 4, for the 2 The above-mentioned laminated layer paper substrate having a titanium oxide content of 1 mass % or more and 45 mass % or less and a thickness of the laminated layer of 10 μm or more and 200 μm or less is directly printed under ultraviolet laser, thereby obtaining a printed matter with excellent print clarity and excellent solvent resistance. Furthermore, the deterioration of the tensile strength and elongation at break of the printed matter is suppressed, and the amount of smoke generated when irradiated with ultraviolet laser is also suppressed.

[1249] On the other hand, a titanium oxide content of less than 0.1 g / m 2In Comparative Examples 6-3 and 7-1, which have a laminated layer of sheet media, sufficient print clarity cannot be obtained. In addition, in Comparative Example 6-4, in which the ratio of the Raman intensity of titanium oxide in the printing area to the Raman intensity of titanium oxide in the non-printing area exceeds 0.70, sufficient print clarity cannot be obtained.

[1250] In Comparative Example 7-2, in which the content of titanium oxide in the laminated layer exceeded 45% by mass, a large amount of smoke was generated. In Comparative Example 7-4, in which the content of titanium oxide in the laminated layer was less than 1% by mass, sufficient print clarity was not obtained. In Comparative Examples 7-4 and 7-5, in which the thickness of the laminated layer was less than 10 μm, the deterioration of tensile strength and elongation at break was large.

[1251] In addition, as shown in Comparative Examples 6-1 and 6-2, sufficient solvent resistance was not obtained in the conventional inkjet method and thermal labels. Furthermore, in Comparative Example 7-3, which provided a coating layer containing titanium oxide instead of a laminate layer, the deterioration of tensile strength and elongation at break was significant. In addition, as shown in Comparative Examples 7-6 to 7-8, printing was not possible under infrared laser, green laser and CO2 laser.

[1252] Industrial Applicability

[1253] The first to third printed matter of the present invention has a printed area containing discolored titanium oxide and has excellent visibility. The first to third printed matter of the present invention is suitable for use in packaging, labels, adhesive tapes, etc. printed with variable information such as dates and bar codes. Furthermore, the first to third printed matter manufacturing method of the present invention is suitable for printing variable information on packaging, labels, adhesive tapes, etc. Furthermore, the first to third laser printing printing media of the present invention are suitable for use in the manufacturing method of the above-mentioned printed matter based on ultraviolet laser.

Claims

1. An ultraviolet laser printed article, wherein at least a portion of a recording medium has an ultraviolet laser printed area containing discolored titanium oxide, wherein the recording medium has an ultraviolet laser printable area containing titanium oxide, The ultraviolet laser printable area of ​​the recording medium has a coating layer containing titanium oxide on a paper substrate, The length-weighted average fiber length of the pulp constituting the paper substrate is 0.6 mm or more and 3.5 mm or less, In the pulp constituting the paper substrate, the ratio of the number of fine fibers having a fiber length of 0.2 mm or less is 6% or more and 16% or less, The titanium oxide is at least one selected from rutile titanium oxide and anatase titanium oxide, The content of titanium oxide in the coating layer is 0.6 g / m 2 Above and 30g / m 2 the following, The content of titanium oxide in the coating layer is set to Ag / m 2 , when the thickness of the coating layer is set to B μm, A / B is greater than or equal to 0.01 and less than or equal to 2.00, The ratio of the Raman intensity derived from titanium oxide in the ultraviolet laser printing region to the Raman intensity derived from titanium oxide in the non-printing region is 0.70 or less.

2. The ultraviolet laser printed article according to claim 1, wherein: The coating layer has a thickness of 0.4 μm or more and 30.0 μm or less.

3. The ultraviolet laser printed article according to claim 1 or 2, wherein: The coating layer contains a thermoplastic resin in addition to titanium oxide.

4. The ultraviolet laser printed article according to claim 3, wherein: The thermoplastic resin is selected from the group consisting of starch derivatives, casein, shellac, polyvinyl alcohol, polyvinyl alcohol derivatives, acrylic resins and maleic acid resins.

5. The ultraviolet laser printed article according to claim 1 or 2, wherein: The recording medium is selected from the group consisting of a package, a label, and an adhesive tape.

6. The ultraviolet laser printed article according to claim 1 or 2, wherein: The recording medium further has a transparent resin layer on the coating layer.

7. The ultraviolet laser printed article according to claim 6, wherein: The resin constituting the transparent resin layer is at least one selected from the group consisting of polyethylene, polypropylene, polyethylene terephthalate, polyvinyl alcohol and starch.

8. The ultraviolet laser printed article according to claim 6, wherein: The transparent resin layer is formed by bonding a transparent resin film to a sheet medium via an adhesive layer, or by laminating a transparent resin film on a sheet medium.

9. The ultraviolet laser printed article according to claim 6, wherein: The transparent resin layer has a thickness of 5 μm or more and 100 μm or less.

10. A method for producing a printed matter, comprising the following steps: Printing is performed by irradiating the recording medium with ultraviolet laser light to change the color of the irradiated area. The printable area of ​​the recording medium has a coating layer containing titanium oxide on a paper substrate, The power of the irradiated ultraviolet laser is 0.8W or more. The length-weighted average fiber length of the pulp constituting the paper substrate is 0.6 mm or more and 3.5 mm or less, In the pulp constituting the paper substrate, the ratio of the number of fine fibers having a fiber length of 0.2 mm or less is 6% or more and 16% or less, The titanium oxide is at least one selected from rutile titanium oxide and anatase titanium oxide, The content of titanium oxide in the coating layer is 0.6 g / m 2 Above and 30g / m 2 the following, The content of titanium oxide in the coating layer is set to Ag / m 2 , when the thickness of the coating layer is set to B μm, A / B is greater than or equal to 0.01 and less than or equal to 2.00, in, The step of performing the printing is a step of irradiating with ultraviolet laser light so that the ratio of the Raman intensity derived from titanium oxide in the printed area to the Raman intensity derived from titanium oxide in the non-printed area becomes 0.70 or less.

11. The method for producing a printed matter according to claim 10, wherein: The recording medium is selected from the group consisting of a package, a label, and an adhesive tape.

12. The method for producing a printed matter according to claim 10 or 11, wherein: The printing process is performed online.

13. A laser printing medium having a printable area that can be printed using ultraviolet laser, The printable area of ​​the print medium has a coating layer containing titanium oxide on a paper substrate, The length-weighted average fiber length of the pulp constituting the paper substrate is 0.6 mm or more and 3.5 mm or less, In the pulp constituting the paper substrate, the ratio of the number of fine fibers having a fiber length of 0.2 mm or less is 6% or more and 16% or less, The titanium oxide is at least one selected from rutile titanium oxide and anatase titanium oxide, The content of titanium oxide in the coating layer is 0.6 g / m 2 Above and 30g / m 2 the following, The content of titanium oxide in the coating layer is set to Ag / m 2 When the thickness of the coating layer is B μm, A / B is greater than or equal to 0.01 and less than or equal to 2.00.

Citation Information

Patent Citations

  • Roll labeler

    JP1994064637A

  • Laminate for laser printing and print thereof

    JP1997123607A

  • Marking method for rubber product

    JP1999020316A

  • Adhesive tape

    JP2012057112A

  • Talc master batch and manufacturing method therefor

    JP2015096568A